Migmatites and deep crustal shear zones: a comparative review of their relationship and evolution - Bruna B. Carvalho; Edward W. Sawyer (Lithos, 2026)

Genetic ancestry proportion influences risk of adverse events from tuberculosis treatment in Brazil - Jacqueline A. Piekos; Gustavo Amorim; Felipe Ridolfi; Marcelo Cordeiro-Santos; Afrânio L. Kritski; Marina C. Figueiredo; Bruno B. Andrade; Adalberto R. Santos; David W. Haas; Timothy R. Sterling; Valeria C. Rolla; Digna R. Velez Edwards; et al. (Human Genetics, 2026)
Tuberculosis (TB) treatment is highly effective, but response to therapy varies by geography and population subgroups. We assessed differences in TB treatment response in a representative and heterogeneous Brazilian population. We estimated genetic ancestry according to major genetic ancestry groups (African, European, and Amerindian) in the Regional Prospective Observational Research in Tuberculosis (RePORT)-Brazil cohort using ADMIXTURE software. RePORT-Brazil is an observational prospective cohort study of individuals with newly-diagnosed, culture-confirmed, pulmonary TB. Outcomes attributed to TB treatment included Grade 2 or higher adverse drug reaction (ADR), Grade 3 or higher ADR, hepatic ADR, and failure/recurrence. Genetic ancestry proportions were evaluated as predictors in univariate and multivariable logistic regression models for each outcome, and in stratified models for each genetic ancestry group. There were 930 pulmonary TB patients included in this study. In multivariable models we observed a decreased risk of Grade 2 + ADR when African ancestry proportion increased by 10% (Odds Ratio [OR] 0.41, 95% Confidence Interval [CI] 0.20–0.85) and an increased risk for Grade 2 + ADR with increasing European genetic ancestry (OR 2.33, 95% CI 1.14–4.76). In secondary analyses evaluating the interaction of HIV and genetic ancestry, we observed a statistically significant interaction between HIV and African genetic ancestry, but significantly decreased risk for Grade 2 + ADR with increasing African ancestry proportion. There were no associations with Amerindian genetic ancestry or for other treatment outcomes. In this Brazilian TB cohort, increased toxicity risk was associated with decreased African and increased European ancestry proportion.

Exploring Holocene non-pollen palynomorph data from the Isle of Mull, Scottish Inner Hebrides: Ecological harmonisation and taphonomic complexity - Kevin J. Edwards; James B. Innes; J. Edward Schofield; Heather Sugden; Jeff J. Blackford (Review of Palaeobotany and Palynology, 2026)

Adaptive Variation Amid High Gene Flow Across a Broad Latitudinal Gradient in the Reef‐Building Honeycomb Worm, Sabellaria alveolata - Edward J. Wilson; Antony M. Knights; Louise B. Firth; Charlotte Corporeau; Amelia Curd; Stanislas F. Dubois; Fernando P. Lima; Rui Seabra; Flavia L. D. Nunes (Molecular Ecology, 2026)
Climate change is already altering, and will continue to reshape, the persistence and spatial structure of marine populations. Understanding metapopulation connectivity and local adaptation is therefore critical for identifying both vulnerable populations and those with adaptive resilience. We applied a seascape genomics approach to investigate connectivity patterns and adaptive responses in the honeycomb worm, Sabellaria alveolata —an intertidal ecosystem engineer that supports high biodiversity and provides essential ecological functions. A total of 286 individuals from 17 sites spanning the entire latitudinal range were genotyped to assess population structure and local adaptation. Outlier analyses (BayeScan and OutFlank) identified six adaptive and 2117 neutral SNPs. Neutral SNP analysis revealed low to moderate genetic differentiation, indicating well‐connected populations. Admixture with possible ancestral gene pools in Southern Edge and Biscay populations suggests the persistence of unique genetic diversity. While connectivity is likely driven by natural larval dispersal, human‐mediated transport resulting from support vessels, aquaculture, marine debris and expanding offshore and coastal infrastructure may also facilitate gene flow, shaping observed genetic patterns. Despite this high connectivity, we detected genetic signatures of adaptation to temperature, salinity and net primary productivity, with adaptive SNPs linked to genes involved in molecular and physiological responses to these environmental factors. Our findings suggest that S. alveolata is likely resilient to climate change and other anthropogenic pressures, making it a valuable model for investigating the genetic and physiological underpinnings of marine population resilience.

Neurobehavioral and metabolic consequences of embryonic triphenyl phosphate exposure across the lifespan in zebrafish - Andrew B. Hawkey; Perry Piatos; Zade R. Holloway; Dilanaz Unal; Jonna Boyda; Richard T. Di Giulio; Edward D. Levin (Neurotoxicology and Teratology, 2026)

Factors influencing equine embryo outcomes in OPU‑ICSI systems: Insights from a large‑scale program in Brazil - Vilceu Bordignon; Jose Buratini; Roger I. Cue; Victoria Barrilari; Marcos A. Gonçalves; Gustavo Merlini; Claudia B. Fernandes; Edward Squires; Jose H.F. Pontes; Perla D.C. Fleury (Journal of Equine Veterinary Science, 2026)

Replaceable laser-textured copper foils and Cu–TiO2 composite foils for sustained suppression of microbial contamination on ICU high-touch surfaces - Alexandre M. Emelyanenko; Andrey V. Buglak; Kirill A. Emelyanenko; Edward A. Domblides; Gleb A. Putsman; Daniil V. Filin; Lusine R. Avetisyan; Marina Y. Chernukha; Sergei K. Zyryanov; Ludmila B. Boinovich (Chemical Engineering Journal, 2026)

Animal responses and physiological indicators of stress in late pregnant alpacas on cultivated pastures in the High Peruvian Andes - Diannett Benito López; Laura B. Gualdrón-Duarte; Rassiel Macedo Sucari; Guadalupe Orellana Ligas; Yemi Sanca Uscamayta; Feliciano Rivera Pachiño; Nancy F. Huanca-Marca; Francisco E. Franco; Rubén García-Ticllacuri; Joel Pacheco Curie; Bernardo Roque Huanca; Víctor M. Vélez-Marroquín; et al. (Tropical Animal Health and Production, 2026)

Life Course Dietary Insulinemic and Inflammatory Potential and Risk of Type 2 Diabetes in U.S. Women: A Prospective Cohort Study - Yin Zhang; Mingyang Song; Molin Wang; Emily Riseberg; Dong D. Wang; Deirdre K. Tobias; Fred K. Tabung; A. Heather Eliassen; Stephanie A. Smith-Warner; Qi Sun; Eric B. Rimm; Meir J. Stampfer; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

“Persistent ecological impacts related to West Nile virus revealed using community science and vector surveillance data” - Brock Geary; Adam C. Smith; Lisa Williams; Sean P. Murphy; Brandon P.M. Edwards; Nicole L. Michel; Timothy D. Meehan; Roderick B. Gagne (Biological Conservation, 2026)

Group 2 Herbicides Applied Below Label Rates Constrain the Ornithopus Sativus—Bradyrhizobium Sp. Symbiosis - B. Arthur; TJ Edwards; RJ Harrison; E. Steel; G. O’Hara; RJ Yates (Journal of Crop Health, 2026)
Pasture legumes are crucial to the sustainability of ley farming systems. They provide a disease break for cereals, nutritious feed for livestock and supply biologically fixed nitrogen (N) for subsequent non-leguminous crops. However, there are frequent observations where biological N‑fixation from the pasture phase is significantly less than expected leading to a N-fixation deficit. Previous field experiments have indicated that the application of Group 2 herbicides contributes to this N‑fixation deficit. Pre-emergent and early-season post-emergent herbicides are applied to avoid early-season weed competition. Group 2 herbicides, inhibitors of the acetolactate synthase (ALS), are widely used in the farming systems of the Western Australia Wheatbelt to control weeds. Greenhouse experiments were conducted to quantify the damage of Group 2 herbicides to French serradella ( Ornithopus sativus ) cvs. Fran 2 o and Margurita, inoculated with commercial strain WSM471. Imazethapyr, imazamox and flumetsulam were applied at logarithmic rates to ascertain a dose-response curve and elucidate the tolerance of these cultivars at three different crop stages. Root nodulation of both French serradella cultivars was more sensitive to herbicide damage than above-ground biomass. Imazethapyr applied post-emergent to Fran 2 o reduced nodulation by 50% when applied at 40% of the recommended label rate (140 g ai/ha). In contrast, the above ground biomass was reduced by 50% only after the application of 170% of the recommended label rate of imazethapyr. Imazamox and flumetsulam applied at label rates reduced nodulation of Margurita by 42% and 20% respectively. The implication of this is that although the legume may be observed as unaffected by these herbicides, N‑fixation is being severely affected.

Palynological data from Loch an t’Suidhe, Isle of Mull, Scotland - Kevin J. Edwards; Heather Sugden; James B. Innes; Jeff Blackford; J. Edward Schofield (Palynology, 2026)

Land sparing outperforms land sharing across an elevational gradient in tropical cattle-farming landscapes - Giovanny Pérez; Simon C. Mills; Jacob B. Socolar; Jose M. Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; James. J. Gilroy; David P. Edwards (Biological Conservation, 2026)

Response to Letter to the Editor: “Recurrence and mortality after Pseudomonas aeruginosa bloodstream infection” - Felicity Edwards; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The Queensland Bloodstream Infections (QBSI) study: rationale, protocol development and future directions - Kevin B. Laupland; Felicity Edwards; Patrick N. A. Harris; Adam Irwin; Burcu Isler; Holly Hamilton; Sonali Coulter; Adam G. Stewart (Infectious Diseases, 2026)

Lung function and inflammation in healthy young adults after 6.6 hours of 0.07 ppm ozone exposure - Edward R. Pennington; Jairus C. Pulczinski; Martin W. Case; Jacob S. Griffin; Neil E. Alexis; Ilona Jaspers; Carole Robinette; Ann Chelminski; Andrea Davis; Neena Miller; David B. Peden; Andrew J. Ghio; et al. (Environmental Research, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Lithium-caesium-tantalum pegmatites in the Varuträsk area, Sweden: geological setting, timing, and source-transport-trap characteristics - Joel B. H. Andersson; Edward P. Lynch; Diana Schildger; Heejin Jeon; Martiya Sadeghi; Tobias E. Bauer (Mineralium Deposita, 2026)
This study investigates lithium-caesium-tantalum (LCT) pegmatites and associated pegmatites and granites in the Varuträsk area, northern Sweden, using a mineral systems approach (i.e. source-transport-trap). The research incorporates geological mapping both regionally and underground, analysis of geological structures and host rock competency, 3D modelling, lithogeochemistry, and zircon-monazite U–Pb SIMS geochronology to assess the genesis and controls on the Varuträsk LCT pegmatite system. The findings reveal four phases of intrusive magmatism within a supracrustal package predominantly composed of metagreywacke, metabasalt (amphibolite), and black shale, subjected to two fabric-forming deformation phases and at least two folding phases, pre- and syn-plutonism in association with the Svecokarelian orogeny. Pegmatites are controlled by brittle to brittle-plastic structures that intersect the tectonic fabric of the host rock, with host rock competency, characterized by uniaxial compressive strength, being a key factor determining the intrusion angle of the pegmatite. The earliest magmatic phase in the area is represented by a granodiorite pluton with a zircon 207 Pb/ 206 Pb age of 1885 ± 3.2 Ma, linked to the main Svecokarelian orogenic cycle. A granodiorite-tonalite intrusion related to the Transscandinavian Igneous Belt has a zircon 207 Pb/ 206 Pb age of 1801 ± 1.7 Ma. Three peraluminous S-type granites (plutonic Skellefte suite) yielded zircon 207 Pb/ 206 Pb ages of 1795 ± 1.7 Ma and 1792 ± 1.6 Ma, and a monazite 207 Pb/ 206 Pb age of 1798 ± 4.6 Ma. Small and irregular to elongated bodies of hypabyssal pegmatitic leucogranite with peraluminous characteristics (hypabyssal Skellefte suite), although not dated in this study, form a geochemical continuum with the Varuträsk LCT pegmatite and less evolved regional pegmatites, and are chemically distinct from the larger S-type plutons. A ‘simple’ muscovite pegmatite dyke, representative of the less evolved regional pegmatites in the area, produced a monazite U–Pb crystallisation age of 1780 ± 6.9 Ma. These results suggest that the hypabyssal pegmatitic leucogranites, regional less evolved pegmatites, and the Varuträsk LCT pegmatite represent the final stage (c. 1.78 Ga) of crustal maturation in the orogenic cycle, marginally postdating the regional migmatization and S-type granite plutonism event. However, further research is encouraged in this study to validate the time gap between plutonic and pegmatitic granites in the Varuträsk area. We propose a mineral system model encompassing a c. 1.80 – 1.78 Ga timeframe that involved initial anatexis of metasedimentary rocks to form S-type granite plutons during the late Svecokarelian orogeny. Subsequently, a resolvable younger magmatic event generated granitic pegmatite melts that utilized pre-existing structures as transport pathways. These melts were trapped in structurally favourable, brittle to brittle-plastic sites and the host rock competency influenced the emplacement angle of the pegmatites.

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Emissions assessment of Low Earth Orbit (LEO) broadband megaconstellations; Starlink, OneWeb and Kuiper - Ogutu B. Osoro; Edward J. Oughton; Andrew Wilson; Akhil Rao (Advances in Space Research, 2026)

Calibration of the species threat abatement and restoration metric's threat abatement component in a Costa Rican landscape - Louise Mair; Thomas M. Brooks; Randall R. Jimenez; Nicholas B. W. Macfarlance; Tony Nello; Antonin Vergez; Leon Bennun; Florence Curet; Annie Dakmejian; Edward Ellis; Melibea Gallo; Philip J. K. McGowan; et al. (Conservation Biology, 2026)
Achieving global conservation policy goals requires the ability to set and measure progress toward science‐based targets for biodiversity. The species threat abatement and restoration (STAR) metric was developed to enable actors to set science‐based targets for species. STAR scores quantify the potential contribution of actions to abate threats and restore habitat to reduce species extinction risk in a particular place and can be aggregated and disaggregated among species, threats, and areas of interest. Estimated STAR scores are based on data from the International Union for Conservation of Nature Red List and provide initial information on the species and threats expected to be present in an area. Operationalization of the metric requires verification of the presence of species and the presence and severity of threats in the area to inform calculation of a calibration STAR score. We applied a pilot calibration process for the threat abatement component of STAR (STAR T ) in the San Jose northern subcatchments landscape in Costa Rica. We used specialist knowledge and geospatial analyses of habitat loss to determine the species present and the intensity of threats affecting them in the landscape. Calibration yielded a more even distribution of scores among threats than was apparent from estimated STAR T and identified that reducing the threat from livestock farming and ranching had the greatest potential to reduce species extirpation risk. Calibration also showed that there is an opportunity to prevent the extinction of a critically endangered endemic amphibian, but the species’ presence requires confirmation. The pilot demonstrated how specialist knowledge and geospatial analyses can be combined during calibration to produce a calibrated STAR T score capable of informing science‐based targets for species conservation. Our calibration process can be applied to other areas.

Petrogenesis and Provenance of Unique Amphibole-Bearing Carbonaceous Chondrite Almahata Sitta 202: Further Evidence for a Ceres-Sized, Water-Rich Parent Body - Cyrena A. Goodrich; Victoria E. Hamilton; Michael E. Zolensky; Noriko Kita; Issaku Kohl; Lauren Tafla; Robert J. Macke; Takahiro Hiroi; Yoko Kebukawa; Wayne Buckley; Jacob B. Setera; Justin I. Simon; et al. (Geochimica et Cosmochimica Acta, 2026)

The National Academy of Sciences Biological Effects of Atomic Radiation (BEAR) Genetics Panel recommended no second-generation genetic damage study of the offspring of the atomic bombings in Japan - Edward J. Calabrese; Paul B. Selby (Chemico-Biological Interactions, 2026)

Building a 3D Digital Twin for Geotechnical Monitoring at San Xavier Mine - Nilufer K. B. Akbulut; Angelina Anani; Leonard D. Brown; Edward C. Wellman; Sefiu O. Adewuyi (Rock Mechanics and Rock Engineering, 2026)

Comparison of Six Data Cleaning Methods for Determining Repetitive Head Impact Exposure in Youth Tackle Football - Samantha DeAngelo; Adam Culiver; Enora Le Flao; Nick Shoaf; Durshil Doshi; Ryan Tracy; Nii-Ayi Aryeetey; Anna Quatrale; Carly Smith; Jianing Ma; Jeff Pan; Jingzhen Yang; et al. (Annals of Biomedical Engineering, 2026)
Purpose Instrumented mouthguards (iMGs) are commonly used to quantify head acceleration event (HAE) exposure, but accurate interpretation requires rigorous data cleaning methods. This study compared six data cleaning methods for determining HAE rates and magnitudes, as well as cleaning method validity compared to the 5 th method video verification in youth tackle football. Methods Fifty athletes (ages 8-12) wore Impact Monitoring Mouthguards during games across one season. Six data cleaning methods were applied to HAEs, including uncleaned data, time-windowing, proprietary classification algorithms, video verification, and combinations thereof. Impact rate, peak linear acceleration (PLA), and peak rotational velocity (PRV) were compared across methods using rate ratios, and intra-class correlation coefficients (ICCs), and non-parametric analyses. Results Data cleaning methods significantly influenced HAE rate but had minimal effect on magnitude. The uncleaned dataset produced the highest HAE rate (67.75 per athlete exposure), while the most stringent method (i.e., time-windowed, proprietary algorithm-classified, video-verified data) yielded the lowest (0.70 per athlete exposure). Although the time-windowed, proprietary algorithm-classified data demonstrated high specificity (0.96), it demonstrated low sensitivity (0.37) and positive predictive value (0.39) when compared to video-verified data. Differences in PLA across methods were not significant; only one significant difference in PRV was observed. Conclusions These findings highlight the impact of data cleaning on HAE quantification in youth tackle football. Although video verification remains best practice, it is resource intensive. Time-windowed, algorithm-classified data may serve as an efficient proxy in similar cohorts, though researchers should recognize its limitations. Findings support the need for standardized data cleaning methods and transparent reporting to ensure accurate and comparable HAE exposure estimates.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The effects of tungsten inhalation and continuous administration of angiotensin II on cardiac injury and pulmonary outcomes - Milad MazloumiBakhshayesh; Russell P. Hunter; Brenna Baird; Rui Liu; Anahi Gabriela Jimenez-Campos; Siem Goitom; Edward B. Barr; Guy W. Herbert; Selita N. Lucas; Charlotte M. McVeigh; Jorge Moreno; Yiliang Zhu; et al. (Toxicology and Applied Pharmacology, 2026)

The nucleation and growth of mixed H2O–CO2 bubbles in magmas - Patrick Sullivan; Edward W. Llewellin; Fabian B. Wadsworth; Simone Colucci; Halim Kusumaatmaja (Journal of Volcanology and Geothermal Research, 2026)

Particulate nitrate over the Northwest Atlantic: Insights gained by comparing airborne AMS and PILS measurements - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Eva-Lou Edwards; Johnathan W. Hair; Christopher A. Hostetler; Simon Kirschler; John B. Nowak; Michael Shook; et al. (Atmospheric Environment, 2026)

Recurrence and mortality after Pseudomonas aeruginosa bloodstream infection: a population-based cohort study - Felicity Edwards; Michael Waller; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Soil carbon and fungal functional group dynamics in forest-savanna transitions - Edward J. Primka; Eric B. Duell; Chris B. Zou; Gail W.T. Wilson (Pedobiologia, 2026)

Beyond surface fluxes: Observational and computational needs of multilayer canopy models – A walnut orchard test case - Gordon B. Bonan; Sean P. Burns; Edward G. Patton (Agricultural and Forest Meteorology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Patterns of plastic occurrence during the pre- and post-Super Typhoon Rai (Odette) event in Olango Island Wildlife Sanctuary (OIWS), Philippines - Apple AJ D. Langcamon; Maria Kristina O. Paler; Emiko Fujita; Yutaka Kameda; Mark Edward M. Walton; Martin W. Skov; Jan G. Hiddink; Evelyn B. Taboada (Marine Pollution Bulletin, 2026)

Elevated organic carbon in African Dark Earths is not exclusively attributable to pyrogenic organic matter - Maura P. Slocum; Riley B. Barton; Sasha J. Wagner; Johannes Lehmann; Dawit Solomon; Edward Yeboah; Alain F. Plante (Science of The Total Environment, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Are mangrove ecosystems plastic accumulation zones? - Shaira Kyle M. Tagalog; Maria Kristina O. Paler; Mark Edward M. Walton; Martin W. Skov; Jan G. Hiddink; Evelyn B. Taboada (Science of The Total Environment, 2026)

Embracing dishonesty: How LNT became king - Edward J. Calabrese; Paul B. Selby (Chemico-Biological Interactions, 2026)

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

Subsaturated aerosol hygroscopicity over the northwest Atlantic: Impacts of seasonal factors, offshore location, and clouds - Genevieve Rose Lorenzo; Luke D. Ziemba; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Richard A. Ferrare; Simon Kirschler; John B. Nowak; Michael A. Shook; Kenneth L. Thornhill; Christiane Voigt; et al. (Atmospheric Environment, 2026)

Strong Variation in Land‐Use Change Impacts on Tropical Avian Phylogenetic Diversity Between Ecoregions Highlights the Need to Sample Large Spatial Scales - Giovanny Pérez; Simon C. Mills; Jacob B. Socolar; Jose M. Ochoa Quintero; Robert P. Freckleton; Torbjørn Haugaasen; James J. Gilroy; David P. Edwards (Global Change Biology, 2026)
Forest conversion for agriculture is a major cause of tropical biodiversity loss, but its impacts vary with spatial scale. Higher species turnover in forests than in farmland means that land‐use change causes greater biodiversity loss at broader than at local scales, yet broad‐scale assessments are scarce. Phylogenetic diversity is increasingly prioritised in conservation to protect evolutionary history under global change, yet how deforestation‐driven changes in phylogenetic diversity scale spatially and accumulate in regions of high species turnover remains unclear. We compiled a large field database from across 13 biogeographically diverse regions affected by deforestation for cattle farming, covering most of Colombia, a megadiverse tropical country. Using occupancy models, we estimated bird communities for 1547 (936 observed plus 611 never‐observed) species across ecoregions and nationally in both forest and pasture habitats to quantify changes in phylogenetic diversity metrics and determine whether these impacts are dependent on spatial scale. We found an average loss of 2300 Myr of phylogenetic diversity at the country scale, with most species negatively affected across the phylogeny. Although single regional‐scale relative loss was on average comparable to broader scales, there was high variability between regional units. The latter was especially critical when evaluating metrics of evolutionary distinctiveness, which are key indicators for biodiversity conservation planning. Such underestimation of national‐scale impacts highlights the importance of sampling across multiple regions. Immediate conservation action is needed to safeguard evolutionarily unique species and prevent phylogenetic homogenisation driven by agricultural expansion across spatial scales—a threat often underestimated due to assessments limited to single biogeographic regions.

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Indian summer monsoon variability across the last 9000 years: New evidence from stalagmites of southwestern China - Yanzhen Li; Chunju Huang; Jianghu Lan; David B. Kemp; James G. Ogg; Ashish Sinha; Lvfan Chen; Xiqian Wang; Huiru Tang; Xu Lin; Khalaf H.M. Abdel-Raheem; Rui Zhang; et al. (Global and Planetary Change, 2025)

Linking crystal shape and dynamic undercooling: a new framework for inferring magmatic crystallization histories - Amanda Lindoo; Madeleine C. S. Humphreys; Charlotte Gordon; Martin F. Mangler; Edward W. Llewellin; Richard A. Brooker; Fabian B. Wadsworth; Eshbal Geifman (Contributions to Mineralogy and Petrology, 2025)
Magmas contain crystals exhibiting diverse shapes and sizes, yet the relationship between crystal shape (specifically aspect ratio) and undercooling ( $$Δ T$$ ), the driving force for crystallization, remains poorly constrained. Crystal shape should correlate with undercooling because undercooling governs the growth regime (interface-controlled versus diffusion-controlled) and thus the resulting crystal form. Prior experiments confirm that large nominal undercoolings drive transitions from polyhedral to hopper, skeletal, or dendritic forms. Large undercoolings reflect rapid decompression or cooling, differing from slower cooling rates typical of magmatic intrusions and storage systems. In such slowly cooled environments, crystals remain polyhedral, exhibiting subtle shape variations. Accurately quantifying crystal shape evolution at relatively low undercoolings could provide critical insights into crystallization histories, improving interpretations of the timescales and processes governing magma storage and eruption dynamics. Experimental verification of correlations between aspect ratios of polyhedral crystals and cooling rates remains inconclusive, possibly because nominal undercooling neglects the dynamic evolution of undercooling throughout crystallization. To address this, we introduce average instantaneous undercooling ( $$\overline{{Δ T_{I} }}$$ ), a metric capturing dynamic undercooling history during crystallization. Through controlled cooling experiments and numerical modelling, we demonstrate that higher $$\overline{{Δ T_{I} }}$$ histories produce tabular, high aspect ratio plagioclase crystals, whereas lower $$\overline{{Δ T_{I} }}$$ produces more prismatic crystals with lower aspect ratios. These variations in shape reflect undercooling-driven shifts in the predominant growth mechanism operating on different crystal faces. By quantitatively linking crystal shape to $$\overline{{Δ T_{I} }}$$ , our study provides a new approach for reconstructing crystallization histories in magmas under varying pH2O-T-t conditions.

Congener Conflict: Invasive Barred Owl Landscape Use Across the Range of the Northern Spotted Owl - Julianna M. A. Jenkins; Natalie M. Rugg; Raymond J. Davis; Scott A. Gremel; Aaron Henderson; Edward Henson; Mark Higley; Holly D. Horan; Christopher McCafferty; Thomas Munger; David Press; Suzanne Reffler; et al. (Journal of Biogeography, 2025)
Aim To map the probability of landscape use of invading barred owls ( Strix varia ) across the range of the threatened northern spotted owl ( S. Occidentallis Caurina ) in the Pacific Northwest, USA , identifying environmental drivers of barred owl landscape use to inform targeted management interventions. Location Forests of the Pacific Northwest, USA. Taxon Barred Owl ( Strix varia ). Methods We deployed 4081 autonomous recording units ( ARUs ) within 1027 randomly selected long‐term monitoring sites consisting of 5‐km 2 hexagons in 2023. We processed audio recordings using convolutional neural networks to detect vocalisations. We applied single‐season occupancy models at both ARU station and hexagon scales to estimate barred owl landscape use and assess associations with environmental variables. Using top models, we mapped barred owl landscape use across the full US range of the northern spotted owl, an umbrella species for conservation of the pacific northwest old‐growth forest community. Results Barred owls were widely detected, with naïve occupancy at 86.8% at the 5‐km 2 hexagon scale. We observed regional variation, with the highest landscape use in the Oregon Coast region and lower landscape use in California regions and the Washington Eastern Cascades. Landscape use was positively associated with mature forest characteristics at both broad and fine scales and negatively associated with elevation and climatic water deficit. Cumulative detection probability exceeded 90% after 2 weeks at the hexagon scale and 4 weeks at the station scale, providing guidance for future barred owl monitoring efforts. Main Conclusions Our study reveals extensive, but not ubiquitous, barred owl distribution across the range of the northern spotted owl. The findings offer a decision‐support framework for prioritising targeted management actions, particularly in regions with lower rates of barred owl landscape use. The integration of passive acoustic monitoring and AI‐based detection demonstrates a scalable approach for invasive species monitoring and conservation planning to meet management objectives in dynamic forest landscapes.

Late Quaternary environmental change in eastern Beringia - Alistair J. Monteath; Mary E. Edwards; Duane Froese; Lesleigh Anderson; Benjamin V. Gaglioti; Scott L. Cocker; Julie Brigham-Grette; Matthew J. Wooller; Bruce Finney; Mark B. Abbott (Quaternary Science Reviews, 2025)

Heat stress analysis using RTMA over heatwave regions in India - Ch. Sridevi; M. V. S. Ramarao; Ashish Routray; B. Tarakesh Lakshman; K. B. R. R. Hari Prasad; Suryakanti Dutta; D. Srinivas; Edward Colón; Annette Gibbs; Manuel Pondeca; V. S. Prasad (Theoretical and Applied Climatology, 2025)

Functions and clinical implications of the liver microenvironment in hepatic uveal melanoma metastases - Camille J. Cunanan; Alyssa B. Sanders; Kayla C. Gallant; Rino S. Seedor; Edward J. Hartsough (Cancer and Metastasis Reviews, 2025)
Uveal melanoma (UM) is an aggressive intraocular malignancy in adults arising from the melanocytes of the uveal tract. While primary UM lesions can be successfully treated, ~ 50% of UM patients develop metastases primarily in the liver. Patients with liver metastatic UM (LMUM) have poor prognosis and few therapeutic options. LMUM lesions are unresponsive to standard chemotherapies, targeted therapies, and immune checkpoint inhibitors — an effect at least in part associated with the detoxification function of the liver and the diverse hepatic immunological landscape. Here, we recount the etiology and molecular mechanisms in the development of LMUM, examine the influences of the hepatic tumor microenvironment (TME) on UM liver tropism, and review how the innate and peripheral immune response contributes to LMUM progression and therapeutic efficacy. The unique immunological properties of the liver coupled with the distinct growth patterns of LMUM lesions present significant challenges for developing effective treatments that can overcome this specialized microenvironment. Improved understanding of the interplay between the liver and LMUM is essential for the development of more effective diagnostic techniques and improved therapeutic outcomes.

More fraudulent history of cancer risk assessment: The US National Academy of Sciences Biological Effects of Atomic Radiation (BEAR) I Genetics Panel used falsified data greatly exaggerating hereditary/cancer risks - Edward J. Calabrese; Paul B. Selby (Chemico-Biological Interactions, 2025)

A Scoping Review of Mosquito Vector Range Shifts: Widespread Expansions and Evidence Gaps in Climate Attribution - Kelsey Lyberger; Anna Rose Robinson; Lisa Couper; Isabel Delwel; Caroline Glidden; Crystal Qian; Aja Burslem; Faith Fernandez; Benjamen Gao; Gabriella Garcia; Julio Gomez; Kristen B. Greenland; et al. (Global Change Biology, 2025)
As global temperatures rise, concerns about shifting mosquito ranges—and accompanying changes in the transmission of malaria, dengue, and other diseases—are mounting. However, systematic evidence for climate‐driven changes in mosquito ranges remains limited. We conducted a scoping review following PRISMA ‐ ScR guidelines of studies documenting expansions or contractions in medically important mosquito species. In total, 178 studies on six continents identified range expansions in 118 mosquito species. While over a third of these studies cited warming as a driver, fewer than 10% performed statistical tests of the role of climate. Instead, most expansions were linked to human‐aided dispersal (e.g., trade, travel), land‐use changes, and urbanization. Although several studies reported poleward or upward expansions consistent with climate warming, none demonstrated warm‐edge contractions driven by rising temperatures, which are theoretically predicted in some settings. Rather than expanding into newly suitable areas, many expansions appear to be filling preexisting thermally suitable habitats. Our findings highlight the need for long‐term mosquito monitoring, rigorous climate‐attribution methods, and better documentation of confounding factors like land‐use change and vector control efforts to disentangle climate‐driven changes from other anthropogenic factors.

P18-65 Advancing the Grouping and Harmonization of Similar Key Events in the AOP Wiki: Ontology-Based Key Event Component Combinations as Catalysts for Integration - J. Filipovska; K. Audouze; J. Blum; L.-A. Clerbaux; E. Coerek; E. Demuynck; S. Edwards; E. Fritsche; L. Gerner; K. Groh; G. Hench; N. Jeliazkova; et al. (Toxicology Letters, 2025)

Persisting neurobehavioral consequences of gestational exposure to cadmium and benzo[a]pyrene in rats - Andrew B. Hawkey; Rongxi Fan; Kala Nwachukwu; Shutong Liu; Anas Gondal; Sarabesh Natarajan; Jade Porter; Melissa Marchese; Giuliana Mesarick; Megan Stout; Corinne Wells; Amir H. Rezvani; et al. (Neurotoxicology and Teratology, 2025)

Suitability of using carbon dioxide as a tracer gas for studying vehicle emission dispersion in a real street canyon - Yuhan Huang; Helen B. Wang; Hilda M.W. Mak; Mengyuan Chu; Zhi Ning; Bruce Organ; Edward F.C. Chan; Chun-Ho Liu; Wai-Chuen Mok; Christof Gromke; Ho Kyong Shon; Chengwang Lei; et al. (Journal of Environmental Sciences, 2025)

The steady state population of Earth’s minimoons of lunar provenance - Robert Jedicke; Elisa Maria Alessi; Naja Wiedner; Mehul Ghosal; Edward B. Bierhaus; Mikael Granvik (Icarus, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Sex Differences in Head Acceleration Events in Law Enforcement Corrections Cadets - Carly R. Smith; Enora Le Flao; Samantha N. DeAngleo; Jeffrey J. Wing; Nathan A. Edwards; James A. Onate; Joshua A. Hagen; Scott Paur; Joshua Walters; Jaclyn B. Caccese (Annals of Biomedical Engineering, 2025)
Purpose Law enforcement cadets (LECs) undergo subject control technique training that may expose them to repetitive head impacts recorded as head acceleration events (HAEs) using instrumented mouthguards. Prior research suggests that sex and/or gender differences in HAE frequency and magnitude vary by sport. This study aimed to examine sex differences in HAE exposure among LECs during training. Methods We collected HAEs from 82 civilian LECs (16 females, mean age = 30 ± 9 years) using instrumented mouthguards. We compared peak linear acceleration (PLA) and peak rotational velocity (PRV) of HAEs > 5 g between sexes using a mixed-effects linear model, with sex and cohort as fixed-effect predictors and a random intercept for subject to account for repeated HAEs within individuals. Additionally, we assessed sex differences in the number of HAEs per athlete exposure using a negative binomial regression controlling for cohort. Results PLA was lower in female than male cadets (e.g., median PLA: females = 10.9 g, males = 12.3 g, p Conclusions Overall, sex differences in HAE frequency and magnitude during subject control technique trainings were minimal. When differences were observed, female cadets exhibited less frequent and less severe HAEs than male cadets. This finding suggests that current training practices, including sex- and/or skill-matched pairing, may effectively reduce HAE exposure risk to females.

Proximal hyperspectral imaging for early detection and disease development prediction of Septoria Leaf Blotch in wheat using spectral–temporal features - Zhongzhong Niu; Yikai Li; Jorge David Salgado Moncada; William Johnson; Edward B. Lang; Xuan Li; Jian Jin (Computers and Electronics in Agriculture, 2025)

Biogeochemical controls on iron speciation and cycling across upland to shoreline gradients in freshwater and estuarine coastal soils (Lake Erie and Chesapeake Bay, United States) - Lucie Stetten; Maxim I. Boyanov; Edward J. O'Loughlin; Shan Pushpajom Thomas; Kathleen R. Beilsmith; Roberta B. Peixoto; Fausto Machado-Silva; Donnie J. Day; Stephanie J. Wilson; Timothy W. Vugteveen; Allison N. Myers-Pigg; Opal Otenburg; et al. (Science of The Total Environment, 2025)

A novel control volume methodology to constrain ecosystem nutrient cycling within a tidal freshwater river - D.R. Mackenzie; D.R. Tait; J. Sippo; A. Ferguson; Rao S; C. Ralph; B. Stewart; M. Call; M. Reading; M. Andskog; D. Laicher-Edwards; D.T. Maher (Estuarine, Coastal and Shelf Science, 2025)

Assessing Pandemic Impacts to Collaborative Management in Parks and Protected Areas - Allie McCreary; Erin Seekamp; Michael B. Edwards (Environmental Management, 2025)
Partnerships are key in helping public land management agencies complete mission-critical conservation work and maintain agency relevancy through community engagement. While there had been a growing trend toward collaboration for many public agencies, the COVID-19 pandemic challenged the ability of volunteers and other groups to work with land management personnel. This study examined public agency personnel’s reported work accomplishments with partners and perceptions of partnerships before (2019), during (2020), and the year after (2021) the pandemic. Results indicate that partnership engagement on conservation-related tasks declined during the pandemic. While the volume of work somewhat recovered in 2021, there remained impacts to the types of partners personnel worked with and to personnel’s perceptions of institutional emphasis on partnerships. Implications for public agencies and their partners include increased emphasis on finding partnership ‘champions’ within the agency and umbrella organizations outside of the agency to facilitate partnership arrangements.

Community-onset bloodstream infection among people with opioid use disorders: a twenty-year population-based cohort study in Queensland, Australia - Kevin B. Laupland; Adam G. Stewart; Felicity Edwards; Patrick N. A. Harris; Sonali Coulter (Infectious Diseases, 2025)

A 33-year study comparing maize (Zea mays) in forage legume or soybean (Glycine max) rotations to maize monocultures: Nitrogen fertilizer replacement values and maize yields - Chang Liang; Bao-Luo Ma; Malcolm J. Morrison; Edward G. Gregorich; Neil B. McLaughlin; Lianne M. Dwyer (Field Crops Research, 2025)

Interference of PFAS sorption on zeolites from natural water characteristics - Nathaniel P. Sheehan; Charles A. Ponge; Abe Pankratz; Justin M. Hutchison; Brian B. Laird; Nuong P. Nguyen; Mark B. Shiflett; Deepak Timalsina; Michael Zhuo Wang; Edward F. Peltier (Chemosphere, 2025)

Determinants of time to positivity in bloodstream infections: an analysis of a population-based cohort in Queensland, Australia - Felicity Edwards; Michael Waller; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Purpose Time to Positivity (TTP) measures the interval from incubation to bacterial growth detection in blood cultures. Although shorter TTP is associated with higher mortality, factors associated with TTP remain uncertain. Methods A retrospective cohort study was conducted among Queensland residents with positive blood cultures between 2000–2019. Incident bloodstream infections (BSIs) were identified using Pathology Queensland data, with demographic, clinical, and outcome data linked to state-wide databases. Results The study analysed 84,341 patients with monomicrobial BSI with a median patient age of 65.6 years (IQR 45.4–78.1), and most infections being community-associated (77.0%). Age showed a non-linear relationship with TTP, and male sex was linked with slightly higher TTP (Incidence Rate Ratio (IRR) 1.01; 95% Confidence Intervals (CI) 1.00–1.02; p = 0.011), reflecting a small but measurable association. Liver disease and malignancy were associated with lower TTP (IRR 0.93; 95% CI 0.91–0.95; p < 0.0001 and IRR 0.95; 95% CI 0.94–0.97; p < 0.0001 respectively), whilst diabetes showed no significant difference (IRR 1.01; 95% CI 1.00–1.02; p = 0.0840). Hospital onset infections exhibited longer TTPs (IRR 1.09; 95% CI 1.08–1.10; p < 0.0001). Conclusions There are several host characteristics associated with TTP that may in part explain the complex relationship between this variable and mortality. Beyond microbiological factors such as isolate type, TTP is also influenced by clinical variables including patient demographics and infection characteristics highlighting its potential as a prognostic marker. Further evaluation is needed to clarify its role in predicting patient outcomes and guiding tailored treatment strategies.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Tropical Land‐Use Change Disrupts Zeta‐Diversity Across Taxa - Edicson Parra‐Sanchez; Guillaume Latombe; Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Diego Martinez‐Revelo; Oscar A. Perez‐Escobar; Robert W. Davies; Christopher G. Bousfield; Gianluca R. Cerullo; Jose Manuel Ochoa‐Quintero; Torbjørn Haugaasen; et al. (Global Change Biology, 2025)
Land‐use change causes community turnover via local extinction and colonisation of species, driving biotic homogenization or heterogenization at larger spatial scales. Quantification of these processes has focused on beta‐diversity metrics, which upweight rarity and overlook the role of widespread species. A key knowledge gap is understanding the impact of land‐use change on both rare and widespread species—zeta‐diversity—allowing the detection of statistical patterns and drivers based on community turnover across space. We sampled bird, dung beetle, and orchid communities in 341 plots across natural (Andean forests and paramo) and transformed habitats (pasturelands) spanning ~270 km north‐to‐south in the Colombian Andes. We detected major losses in species richness following land‐use conversion, which disrupts zeta‐diversity across elevation in two ways. First, biodiversity patterns are rewired such that bird and dung beetle communities become structured by dispersal ability, overriding the effects of natural biogeographical drivers (i.e., elevation) and landscape conditions (i.e., canopy cover). Second, land‐use change causes biotic homogenization across bird communities, with pasture retaining twice as many widespread species than natural habitats, and a four‐fold reduction in widespread dung beetle species pointing to subtractive heterogenization. Orchid communities show high community turnover in both natural and transformed habitat. Our results show that the effect of local deforestation has a doubly devastating impact simplifying communities and reducing widespread species. Transforming natural habitats into anthropogenic landscapes may substantially raise extinction risk for communities composed of both widespread and rare species, especially in orchids as the most sensitive taxon.

A Review of Global Fisheries Performance - Frank Asche; Taryn M. Garlock; James L. Anderson; Ruth B. Pincinato; Christopher M. Anderson; Edward V. Camp; Jingjie Chu; Andreea L. Cojocaru; Hakan Eggert; Kai Lorenzen; David C. Love; Ragnar Tveteras (Fish and Fisheries, 2025)
Management of fisheries is complex as it combines environmental, economic and social objectives. The relative importance of these objectives is highly debated and the best approaches to achieving good outcomes are unclear. A lack of global and multi‐dimensional data has largely precluded reviews providing comparisons of performances across systems at a large scale. We review fisheries performance by analysing outcomes over 14 dimensions of environmental, economic and community performance using a unique global dataset for 145 fisheries collected with the Fishery Performance Indicators. The fisheries are ranked into three performance groups by an average of their environmental, economic and community scores: the 10% best fisheries, the 10% worst fisheries and the middle 80%. Furthermore, we investigate how four different types of management systems, catch shares, territorial use rights, limited entry and open access, are represented in the three performance groups. The best performing fisheries scored equally or better and the poorest performing fisheries scored equally or worse in environmental, economic and social dimensions. We found three different management systems to be represented among the best performing fisheries, indicating that no specific management system is best. Moreover, some management systems were represented in all three performance categories, indicating that fisheries characteristics or management designs are important elements of fishery performance. The worst performing fisheries were dominated by open access fisheries with no or very limited management.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Ingestive behaviour, performance, and methane emissions of pregnant alpacas grazing cultivated pastures in the high Peruvian Andes - Laura B. Gualdrón-Duarte; Cecilia Loza; José I. Gere; Nancy F. Huanca-Marca; Francisco E. Franco; Yemi Sanca Uscamayta; Rubén García‐Ticllacuri; Guadalupe Orellana Ligas; Diannett Benito López; Feliciano Rivera Pachiño; Juan E. Moscoso-Muñoz; Medardo A. Díaz-Céspedes; et al. (Livestock Science, 2025)

Ultraviolet radiation vs air filtration to mitigate virus laden aerosol in an occupied clinical room - Shane A. Landry; Milan Jamriska; Vinay J. Menon; Leo Yi Yang Lee; Isabelle Magnin-Bougma; Dinesh Subedi; Jeremy J. Barr; Jason Monty; Kevin Kevin; Ajith Gunatilaka; Michelle Delaire; Guy B. Marks; et al. (Journal of Hazardous Materials, 2025)

Conversion of hydrogen gas to water in soil: Implications to fusion contributions - E.R. Edwards; B.J. Viner; M.C. Duff; S.M. Lyons; A. Seifert; H. VerMeulen; C.E. Aalseth; B. Boehnke; J.O. Davis; B.R. Hackett; M.C. Huh; D.B. Hunter; et al. (Journal of Environmental Radioactivity, 2025)

John Raven, FRS, FRSE: a truly great innovator in plant physiology, photosynthesis and much more - A. W. D. Larkum; P. G. Falkowski; Dianne Edwards; C. B. Osmond; H. Lambers; P. Sanchez-Baracaldo; R. J. Ritchie; J. W. Runcie; P. J. Ralph; M. Westoby; S. Maberly; H. Griffiths; et al. (Photosynthesis Research, 2025)
This is a tribute to a truly inspirational plant biologist, Prof. John A. Raven, FRS, FRSE (25th June 1941– 23rd May 2024), who died at the age of 82. He was a leader in the field of evolution and physiology of algae and land plants. His research touched on many areas including photosynthesis, ion transport, carbon utilisation, mineral use, such as silicon, iron and molybdenum, the evolution of phytoplankton, the evolution of root systems, the impact of global change, especially on the acidification of the oceans, carbon gain and water use in early land plants, and ways of detecting extraterrestrial photosynthesis. Beginning his research career in the Botany School, University of Cambridge, John studied ion uptake in a giant algal cell. This was at the time of great strides brought about by Peter Mitchell (1920–1992) in elucidating the role of energy generation in mitochondria and chloroplasts and the coupling of ion transport systems to energy generation. With Enid MacRobbie and Andrew Smith, John pioneered early work on the involvement of ion transport in the growth and metabolism of plant cells.On leaving Cambridge John took up a lectureship at the University of Dundee in 1971, where he was still attached upon his death. His primary focus over the years, with one of us (Paul Falkowski), was on phytoplankton, the photosynthetic microalgae of the oceans. Still, his publication list of 5 books and over 600 scientific papers spans a very broad range. The many highly cited papers (see Table 1) attest to an outstanding innovator, who influenced a multitude of students and coworkers and a very wide readership worldwide. At the personal level, John Raven was a wonderful human being; he had an extraordinary memory, dredging up facts and little-known scientific papers, like a scientific magician, but at the same time making humorous jokes and involving his colleagues in fun and sympathetic appreciation. Table 1 Ten best cited articles (from google scholar) Citations Date Aquatic Photosynthesis, 3rd EditionP.G. Falkowski & J.A. RavenPrinceton University Press, 2013 3854 2013 The evolution of modern eukaryotic phytoplanktonP.G. Falkowski, M.E. Katz, A.H. Knoll, A. Quigg, J.A. Raven, et alScience 305 , 354–360 1790 2004 C O 2 concentrating mechanisms in algae:mechanisms, environmental modulation, and evolutionM. Giordano, J. Beardall & J.A. RavenAnnu. Rev. Plant Biol. 56 (1), 99–131 1648 2005 Algae as nutritional food sources: revisiting our understandingM.L. Wells, P. Potin, J.S. Craigie, J.A. Raven, S.S. Merchant, et alJournal of applied phycology 29 , 949–982 1527 2017 Plant Nutrient acquisition strategies change with soil ageH. Lambers, J.A. Raven, G.R. Shaver & S.E. SmithTrends in ecology & evolution 23 , 95–103 1488 2008 Ocean acidification due to increasing atmospheric carbon dioxideJ. Raven, K. Caldeira, H. Elderfield, O. Hoegh-Guldberg, P. Liss, et alThe Royal Society, Policy Document, June 2005 1470 2005 Phytoplankton in a changing world: cell size and elemental stoichiometryZ.V. Finkel, J. Beardall, K.J. Flynn, A. Quigg, T.A.V. Rees & J.A. RavenJournal of plankton research 32 , 119–137 1198 2010 Opportunities for improving phosphorus efficiency in crop plantsE.J. Veneklaas, H. Lambers, J. Bragg, P.M. Finnegan, C.E. Lovelock, et alNew phytologist 195 , 306–320 951 2012 Adaptation of unicellular algae to irradiance: an analysis of strategiesK. Richardson, J. Beardall & J.A. RavenNew Phytologist 93 , 157–191 914 1983 N itrogen assimilation and transport in vascular land plants in relation to Intracellular pH regulationJ.A. Raven & F.A. SmithNew Phytologist 76 , 415–431 893 1976 Temperature and algal growth J.A. Raven & R.J. GeiderNew phytologist 110 , 441–461 867 1988 The role of trace metals in photosynthetic electron transport in O 2 -evolving organismsJ.A. Raven, M.C.W. Evans & R.E. KorbPhotosynthesis Research 60 , 111–150 840 1999

Effects of the invasive aquatic snail Potamopyrgus antipodarum (Gray, 1853) on ecosystem properties and services - Álvaro Alonso; Gonzalo A. Collado; Claudia Gérard; Edward P. Levri; Rodrigo B. Salvador; Pilar Castro-Díez (Hydrobiologia, 2025)
Ecosystems provide benefits to humans, including provisioning, regulating, and cultural services. However, invasive species can threaten ecosystem well-functioning and services provided. One invasive species with such potential is the New Zealand mud snail (NZMS) Potamopyrgus antipodarum . The aims of this study are focused on the quantitative review of (1) the NZMS impacts on ecosystem properties and their direct links with ecosystem services, and (2) the ecosystem services that can be affected by the NZMS. The high density reached by this species in most of the invaded ecosystems and its highly competitive ability affect ecosystem structure and functioning. However, some facilitation processes on native species may result in an improvement of some services. The NZMS tends to positively affect cultural services (88% positive cases) but negatively to provisioning services (77% of cases). Regarding, regulating and maintenance services, the proportions of positive and negative effects were similar (45% vs 36%, respectively). Therefore, the NZMS is a species with numerous negative impacts on ecosystem services. However, ecosystem services related to health (e.g., dilution effect against parasites) and research (e.g., biomonitoring) are cultural services that the NZMS can improve. No economic assessment of the impacts of the NZMS is available in the literature.

Detection of a late autumn Karenia papilionacea bloom in Virginia, USA, coastal waters - Jennifer L. Wolny; Michelle C. Tomlinson; Todd A. Egerton; Leah A. Gibala-Smith; Chyna B. Law; Ellen Gortz; Emma W. Brooks; Edward B. Whereat; Margaret R. Mulholland (Harmful Algae, 2025)

Risk of mortality in Fusobacterium species bloodstream infection from a large Australian cohort - Adam G. Stewart; Felicity Edwards; Patrick N. A. Harris; David L. Paterson; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Mercury deposition in central China from the Last Glacial Maximum to the early Holocene recorded in an accurately-dated stalagmite - Yanzhen Li; Liangcheng Tan; Simin Jin; Hai Xu; Lüfan Chen; David B. Kemp; Ashish Sinha; Le Ma; Chunju Huang; Lawrence R. Edwards; Hai Cheng (Science Bulletin, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Strength, mating success, and immune and nutritional costs in a population sample of US women and men: A registered report - Caroline B. Smith; Edward H. Hagen (Evolution and Human Behavior, 2025)

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

Investigating the enzymatic response of Plutella xylostella L. (Lepidoptera: Plutellidae) to Metarhizium anisopliae (Metschnikoff) Sorokin (Ascomycota: Hypocreales) Infection: A Comprehensive study - Abarna V.P.; Muthuswami M.; Jeyarajan Nelson S; Johnson Thangaraj Edward Y.S.; Manikanda Boopathi N.; Anita B.; Jeya Sundara Sharmila D. (Journal of Asia-Pacific Entomology, 2024)

Analysis of the scintillation characteristics on the different satellite links derived from GPS observations and SCINDA data over Mbarara - Edward Jurua; Geoffrey Andima; Paschal Oleni; Emirant B. Amabayo (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Impact of drought on hydropower generation in the Volta River basin and future projections under different climate and development pathways - Akwasi Adu-Poku; Ebenezer K. Siabi; Nathaniel Oppong Otchere; Francis B. Effah; Edward A. Awafo; Francis Kemausuor; Mashael Yazdanie (Energy and Climate Change, 2024)

A comprehensive analysis of new particle formation across the northwest Atlantic: Analysis of ACTIVATE airborne data - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Simon Kirschler; Hongyu Liu; John B. Nowak; Michael A. Shook; Cassidy Soloff; Kenneth L. Thornhill; et al. (Atmospheric Environment, 2024)

Juniper (Juniperus virginiana) encroachment into grassland results in increased trace-element inputs - Edward J. Primka; Shujun Chen; Lingyun Wan; Daolin Du; Hailin Zhang; Rodney Will; Chris B. Zou (Plant and Soil, 2024)
Background and aims Woody plant encroachment poses a significant threat to grasslands globally, and in the southcentral USA, juniper ( Juniperus virginiana ) is rapidly taking over large areas of grasslands. Despite ongoing research, the reasons behind the rapid encroachment of juniper species in Oklahoma remain elusive. We hypothesized that the interaction between juniper canopy, aeolian, and wet-deposition processes lead to a modification in trace-element inputs through stemflow and throughfall. This, in turn, plays a crucial role in determining the success of juniper encroachment. Methods We measured the influx of trace-elements in stemflow and throughfall beneath juniper canopies of different sizes, contrasting the results with those obtained under ambient precipitation. Results Our research unveiled a significant influence of the juniper canopy on trace-element inputs via stemflow and throughfall. Specifically, there was a significant increase in manganese, boron, and chlorine inputs, coupled with a decrease in copper inputs. Additionally, there was an increase in most cations and sulfate. Results Our results indicate that juniper encroachment alters the profile of trace-element, cation, and anion inputs beneath their canopies. Increased levels of manganese and reduction of copper inputs into the ecosystem may enhance the juniper growth, creating a positive feedback mechanism that could contribute to the success of juniper and other woody encroachers.

Moths are less attracted to light traps than they used to be - Ian Battles; Eric Burkness; Michael S. Crossley; Collin B. Edwards; Kristian Holmstrom; William Hutchison; Joseph Ingerson-Mahar; David Owens; Avalon C.S. Owens (Journal of Insect Conservation, 2024)
As evidence of global insect declines continues to mount, insect conservationists are becoming increasingly interested in modeling the demographic history of at-risk species from long-term survey data. However, certain entomological survey methods may be susceptible to temporal biases that will complicate these efforts. Entomological light traps, in particular, may catch fewer insects today than they once did due solely to increases in anthropogenic light pollution. Here we investigate this possibility by comparing the demographic histories of corn earworm moths ( Helicoverpa zea ) estimated from pairs of blacklight and pheromone traps monitored at the same farms. We find a stark decline in blacklight trap efficacy over 25 years of monitoring in Delaware, USA, mirrored over 10 years of monitoring in New Jersey, USA. While the precise causes of this decline remain a subject for discussion, the practical consequences are clear: insect conservationists cannot fully rely on long-term trends from entomological light traps.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Characterizing Head Acceleration Events in Law Enforcement Cadets During Subject Control Technique Training - Carly R. Smith; James A. Onate; Nathan A. Edwards; Joshua A. Hagen; Chris Kolba; Scott Paur; Joshua Walters; Jaclyn B. Caccese (Annals of Biomedical Engineering, 2024)
Law enforcement cadets (LECs) complete weeks of subject control technique training. Similar sport-related combat training has been shown to expose participants to head acceleration events (HAEs) that have potential to result in short- and long-term impairments. The purpose of this study was to describe the number and magnitude of HAEs in LECs throughout their training. 37 LECs (7 females; age = 30.6 ± 8.8 years; BMI = 30.0 ± 6.0) were recruited from a law enforcement organization. Participants wore instrumented mouthguards, which recorded all HAEs exceeding a resultant 5 g threshold for training sessions with the potential for HAEs. Participants completed three defensive tactics (DT) training sessions, a DT skill assessment (DTA), and three boxing sessions. Outcome measures included the number of HAEs, peak linear acceleration (PLA), and peak rotational velocity (PRV). There were 2758 true-positive HAEs recorded across the duration of the study. Boxing sessions accounted for 63.7% of all true-positive HAEs, while DT accounted for 31.4% and DTA accounted for 4.9%. Boxing sessions resulted in a higher number of HAEs per session ( F 2,28 = 48.588, p η p 2 = 0.776), and higher median PLA ( F 2,28 = 8.609, p = 0.001, η p 2 = 0.381) and median PRV ( F 2,28 = 11.297, p η p 2 = 0.447) than DT and DTA. The LECs experience a high number of HAEs, particularly during boxing sessions. Although this training is necessary for job duties, HAE monitoring may lead to modifications in training structure to improve participant safety and enhance recovery.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Recent discoveries on the historical foundations of cancer risk assessment: Shedding light on the limits of LNT - Edward Calabrese; James Giordano; Paul B. Selby (Science of The Total Environment, 2024)

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Tillage effects on residue-derived carbon distribution among soil fractions in a Mollisol - Yan Zhang; Aizhen Liang; Dandan Huang; Shaoqing Zhang; Yang Zhang; Yan Gao; Yafei Guo; Edward G. Gregorich; Neil B. McLaughlin; Xuewen Chen; Shixiu Zhang; Yongjun Wang (CATENA, 2024)

Proximity Labelling Confirms the Involvement of Papain-Like Cysteine Proteases and Chaperones in Cyclotide Biosynthesis - Meng-Han Lee; Mark A. Jackson; Fabian B. H. Rehm; Deborah S. Barkauskas; Wing L. Ho; Kuok Yap; David J. Craik; Edward K. Gilding (Plant Molecular Biology Reporter, 2024)
Cyclotides are disulfide-rich insecticidal peptides from plants that harbour a cyclic cystine knot motif that imparts them with high stability. Like most ribosomally encoded peptides, cyclotides are produced as precursor proteins that are subsequently processed to maturity through proteolytic activity. Although the final maturation of the prototypic cyclotide kalata B1 (kB1) is known to involve asparaginyl endopeptidases, the role of the in planta folding machinery is less well characterized, as is also the case for in planta N-terminal processing enzyme(s). Here, we used proximity labelling to identify proteins involved in the biosynthesis of kB1 in both a cyclotide-bearing plant species, Petunia × hybrida [Regel], and in Nicotiana benthamiana [Domin] that does not naturally produce cyclotides. Together, several ER resident chaperones, protein disulfide isomerases, a papain-like cysteine protease, and an asparaginyl endopeptidase were identified in the kB1 interactome. We found that overexpression of the identified papain-like cysteine protease resulted in an improvement in the yield of cyclic kB1, while this was not the case for the overexpression of protein disulfide isomerases, despite their interaction being verified using bimolecular fluorescence complementation. Together, these results provide a significant advance in our understanding of the role of auxiliary biosynthetic elements for heterologous cyclotide production in plants.

Epidemiology of biliary tract-associated bloodstream infections and adequacy of empiric therapy: an Australian population-based study - Ian Gassiep; Felicity Edwards; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose Although the biliary tract is a common source of invasive infections, the epidemiology of cholangitis- and cholecystitis-associated bloodstream infection (BSI) is not well defined. The objective of this study was to determine the incidence, clinical determinants, microbiology of biliary tract-associated BSI, and predicted adequacy of common empiric therapy regimens. Methods All biliary tract-associated BSI in Queensland during 2000–2019 were identified using state-wide data sources. Predicted adequacy of empiric antimicrobial therapy was determined according to microbiological susceptibility data. Results There were 3,698 episodes of biliary tract-associated BSI occurred in 3,433 patients of which 2,147 (58.1%) episodes were due to cholangitis and 1,551 (41.9%) cholecystitis, for age- and sex-standardized incidence rates of 2.7, and 2.0 per 100,000 population, respectively. An increasing incidence of biliary tract-associated BSI was observed over the study that was attributable to an increase in cholangitis cases. There was a significant increased risk for biliary tract-associated BSI observed with advancing age and male sex. Patients with cholangitis were older, more likely to have healthcare associated infection, and have more comorbidities most notably liver disease and malignancies as compared to patients with cholecystitis. The distribution of infecting pathogens was significantly different with polymicrobial aetiologies more commonly observed with cholangitis (18.4% vs. 10.5%; p < 0.001). The combination of ampicillin/gentamicin/metronidazole was predicted to have the overall highest adequacy (96.1%), whereas amoxicillin/clavulanate had the lowest (77.0%). Amoxicillin/clavulanate (75.2% vs. 79.4%, p:0.03) and ceftriaxone/metronidazole (83.4% vs. 89.6%; p < 0.001) showed significantly inferior predicted adequacy for cholangitis as compared to cholecystitis. Conclusions Bloodstream infections related to cholecystitis and cholangitis exhibit different epidemiology, microbiology, and requirements for empiric therapy.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Depredation: An old conflict with the sea - James Marcus Drymon; Amanda E. Jargowsky; Evan G. Prasky; Edward V. Camp; Ashley Oliphant; Sean P. Powers; Steven B. Scyphers (Fish and Fisheries, 2024)
Depredation (the partial or complete removal of a hooked species by a non‐target species) is a human–wildlife conflict as old as humans and the sea. In some ways, depredation is no different today than it was a century ago. But in many ways, this conflict has become more complicated. Following three decades of successful management, some US shark populations have begun to rebuild. However, many anglers attribute perceived increases in shark depredation to management measures, claiming they have led to ‘overpopulation’ of sharks and/or learned behaviour by sharks. We investigated whether these factors could explain the reported increases in depredation. Based on fishery‐independent surveys, neither shark population increases nor learned behaviour by sharks is evident. However, increases in angler effort provide an alternative explanation that is not often considered. While far from a smoking gun, at least four themes emerge from this thought exercise. First, it is important to understand historical predator baselines. Second, it is important to acknowledge lifting baselines, that is, instances where previously depleted populations are recovering. Third, it is important to remember that there are many instances when stakeholder observations were initially misaligned with traditional scientific observations but were ultimately recognized as pivotal for filling data gaps. Finally, and perhaps most important, is the acknowledgement that perceived conflict is as potent as real conflict. Arguably, it may not matter if depredation has increased or decreased; the overwhelming perception from stakeholders is an increase in depredation, and this is the perceived (or real) conflict that must be addressed.

Pseudomonas stutzeri bloodstream infection is a prevailing community-onset disease with important mortality rates: results from a retrospective observational study in Australia - Juan P. Horcajada; Felicity Edwards; Silvia Fonio; Milagro Montero; Patrick Harris; David L. Paterson; Kevin B. Laupland (Infectious Diseases, 2024)

Emotional and functional well-being in long-term breast cancer survivorship - Yumeng Ren; Joanna Maselko; Xianming Tan; Andrew F. Olshan; Angela M. Stover; Antonia V. Bennett; Katherine E. Reeder-Hayes; Jessie K. Edwards; Bryce B. Reeve; Melissa A. Troester; Marc A. Emerson (Cancer Causes & Control, 2024)

First report of X-ray induced somatic mutation by Muller’s department chair fails to support Muller’s linearity hypothesis - Edward Calabrese; Paul B. Selby (Archives of Toxicology, 2024)

Newly discovered letter: why Muller failed to cite the negative mouse mutation findings of Snell, preserving his chances to receive the Nobel Prize - Edward J. Calabrese; Paul B. Selby (Archives of Toxicology, 2024)

Persisting neurobehavioral consequences of daily or intermittent paternal cannabis administration in F1 and F2 Rats - Andrew B. Hawkey; Sarabesh Natarajan; Olivia Kelly; Anas Gondal; Corinne Wells; Michelle Louise Jones; Amir H. Rezvani; Susan K. Murphy; Edward D. Levin (NeuroToxicology, 2024)

Nitrogen fertilizer replacement value of stockpiled and rotted dairy cattle manures for corn (Zea mays L.) from a long-term study - Bao-Luo Ma; Chang Liang; Edward G. Gregorich; Neil B. McLaughlin; Malcolm J. Morrison; Lianne M. Dwyer (Field Crops Research, 2024)

Female foragers sometimes hunt, yet gendered divisions of labor are real: a comment on Anderson et al. (2023) The Myth of Man the Hunter - Vivek V. Venkataraman; Jordie Hoffman; Kyle Farquharson; Helen Elizabeth Davis; Edward H. Hagen; Raymond B. Hames; Barry S. Hewlett; Luke Glowacki; Haneul Jang; Robert Kelly; Karen Kramer; Sheina Lew-Levy; et al. (Evolution and Human Behavior, 2024)

Root exudation links root traits to soil functioning in agroecosystems - Adam C. von Haden; William C. Eddy; Mark. B. Burnham; Edward R. Brzostek; Wendy H. Yang; Evan H. DeLucia (Plant and Soil, 2024)

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Persistence and evidence for accelerated biodegradation of streptomycin in agricultural soils - Megan Demars; Tim McDowell; Justin B. Renaud; Andrew Scott; Michael Fruci; Edward Topp (Science of The Total Environment, 2024)

A Murky Ruling Threatens the Fate of Millions of US Wetlands - B. Alexander Simmons; Marcus W. Beck; Kerry Flaherty-Walia; Jessica Lewis; Edward T. Sherwood (Wetlands, 2024)
For decades, federal protections were extended to wetlands adjacent to “waters of the US” by the Clean Water Act. In its Sackett v. EPA ruling, however, the US Supreme Court redefined the meaning of “adjacent,” eliminating protections to wetlands without a continuous surface connection to these waters (i.e., geographically isolated wetlands, GIWs). Yet it remains unclear how this continuous surface test will work in reality, where ecological connectivity often extends beyond physical connectivity. Here, we calculate the number of US wetlands that could be considered geographically isolated depending upon the distance threshold used to define isolation (ranging from 1 m to 100 m from the nearest hydrological feature). Overall, we estimate that 27–45% of wetlands, at minimum, could be considered geographically isolated using this range of distance thresholds. Over 3 million wetlands are within 1–100 m of the nearest hydrological feature, making them most vulnerable to losing prior protections from the Clean Water Act. The Midwest and Northeast have the largest share of potential GIWs within this range. Freshwater emergent wetlands and forested/shrub wetlands make up the majority of these vulnerable wetlands, though this varies by state. Roughly 47% of these wetlands are located in states without state-level protections for GIWs. Our analysis highlights the heterogeneity of risk to wetlands across the country and the scale of the uncertainty imposed by the updated Sackett definition. State-level protections that are robust to changes in federal protections are urgently needed to secure the country’s wetlands from further pollution and destruction.

Heavy rains and hydrogeological disasters on February 18th–19th, 2023, in the city of São Sebastião, São Paulo, Brazil: from meteorological causes to early warnings - Jose A. Marengo; Ana P. Cunha; Marcelo E. Seluchi; Pedro I. Camarinha; Giovanni Dolif; Vinicius B. Sperling; Enner H. Alcântara; Andrea M. Ramos; Marcio M. Andrade; Rodrigo A. Stabile; José Mantovani; Edward Park; et al. (Natural Hazards, 2024)

Muller and mutations: mouse study of George Snell (a postdoc of Muller) fails to confirm Muller’s fruit fly findings, and Muller fails to cite Snell’s findings - Edward J. Calabrese; Paul B. Selby (Archives of Toxicology, 2024)

SO2 emission rates and incorporation into the air pollution dispersion forecast during the 2021 eruption of Fagradalsfjall, Iceland - Melissa A. Pfeffer; Santiago Arellano; Sara Barsotti; Guðrún Nína Petersen; Talfan Barnie; Evgenia Ilyinskaya; Tryggvi Hjörvar; Enikö Bali; Gro B.M. Pedersen; Gunnar B. Guðmundsson; Kristín Vogfjorð; Eemu Johannes Ranta; et al. (Journal of Volcanology and Geothermal Research, 2024)

Assessment of the effect of long-term serum storage for retrospective serologic diagnosis of canine monocytic ehrlichiosis (Ehrlichia canis) - Melina Karagkouni; Katerina Spilioti; Eleftherios Meletis; Polychronis Kostoulas; Christos Koutinas; Konstantina Theodorou; Edward B. Breitschwerdt; Mathios E. Mylonakis (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Relationship of psychotropic medication use with physical function among postmenopausal women - Hind A. Beydoun; May A. Beydoun; Edward Kwon; Brook T. Alemu; Alan B. Zonderman; Robert Brunner (GeroScience, 2024)
To examine cross-sectional and longitudinal relationships of psychotropic medications with physical function after menopause. Analyses involved 4557 Women’s Health Initiative Long Life Study (WHI-LLS) participants (mean age at WHI enrollment (1993–1998): 62.8 years). Antidepressant, anxiolytic, and sedative/hypnotic medications were evaluated at WHI enrollment and 3-year follow-up visits. Performance-based physical function [Short Physical Performance Battery (SPPB)] was assessed at the 2012–2013 WHI-LLS visit. Self-reported physical function [RAND-36] was examined at WHI enrollment and the last available follow-up visit—an average of 22 [±2.8] (range: 12–27) years post-enrollment. Multivariable regression models controlled for socio-demographic, lifestyle, and health characteristics. Anxiolytics were not related to physical function. At WHI enrollment, antidepressant use was cross-sectionally related to worse self-reported physical function defined as a continuous ( β = −6.27, 95% confidence interval [CI]: −8.48, −4.07) or as a categorical (< 78 vs. ≥ 78) (odds ratio [OR] = 2.10, 95% CI: 1.48, 2.98) outcome. Antidepressant use at WHI enrollment was also associated with worse performance-based physical function (SPPB) [< 10 vs. ≥ 10] (OR = 1.53, 95% CI: 1.05, 2.21) at the 2012–2013 WHI-LLS visit. Compared to non-users, those using sedative/hypnotics at WHI enrollment but not at the 3-year follow-up visit reported a faster decline in physical function between WHI enrollment and follow-up visits. Among postmenopausal women, antidepressant use was cross-sectionally related to worse self-reported physical function, and with worse performance-based physical function after > 20 years of follow-up. Complex relationships found for hypnotic/sedatives were unexpected and necessitate further investigation.

Prenatal and perinatal exposure to Per- and polyfluoroalkyl substances (PFAS)-contaminated drinking water impacts offspring neurobehavior and development - Melissa J. Marchese; Tianyi Zhu; Andrew B. Hawkey; Katherine Wang; Emi Yuan; Jinchen Wen; Sara E. Be; Edward D. Levin; Liping Feng (Science of The Total Environment, 2024)

Embryonic exposures to cadmium and PAHs cause long-term and interacting neurobehavioral effects in zebrafish - Alexandra Stickler; Andrew B. Hawkey; Anas Gondal; Sarabesh Natarajan; Mikayla Mead; Edward D. Levin (Neurotoxicology and Teratology, 2024)

Overprinting orogenic events, ductile extrusion and strain partitioning during Caledonian transpression, NW Mainland Shetland - Timothy B. Armitage; Robert E. Holdsworth; Robin A. Strachan; Edward D. Dempsey; Richard J. Walker; Diana T. Alvarez-Ruiz; Geoffrey E. Lloyd (Journal of Structural Geology, 2024)

Environmental drivers of biogeography and community structure in a Mid-Atlantic estuary - Haley A. Oleynik; Joseph J. Bizzarro; Edward A. Hale; Aaron B. Carlisle (Oecologia, 2024)
Estuaries include some of the most productive yet anthropogenically impacted marine ecosystems on the planet, and provide critical habitat to many ecologically and economically important marine species. In order to elucidate ecological function in estuaries, we must understand what factors drive community dynamics. Delaware Bay is the third largest estuary in the United States and hosts over 200 species of migrant and resident fishes and invertebrates. The Delaware Division of Fish and Wildlife has conducted two long-term trawl surveys at monthly intervals in Delaware Bay since 1966. The two surveys collect data on environmental conditions, species composition, and number of fishes and macroinvertebrates across different size classes and life histories. Using a suite of multivariate approaches including hierarchical cluster analysis, canonical correlation analysis, and permutational multivariate analysis of variance, we characterized the fish and macroinvertebrate community in Delaware Bay and found that community composition and environmental conditions varied across spatial and seasonal scales. We identified four distinct biogeographic regions, based on environmental conditions and community composition, which were consistent across surveys. We found that the community was driven primarily by gradients in temperature and salinity and that abundant, frequently occurring species in the Bay have well-defined environmental associations. Our work represents the first attempt to use an existing historical survey to better understand how environmental parameters influence diversity and distribution of macrofauna within Delaware Bay, providing insight into how abiotic variables, influenced by climate, may impact the Delaware Bay ecosystem and similar estuarine ecosystems worldwide.

The Occurrence of Karenia species in mid-Atlantic coastal waters: Data from the Delmarva Peninsula, USA - Jennifer L. Wolny; Edward B. Whereat; Todd A. Egerton; Leah A. Gibala-Smith; John R. McKay; Judith M. O'Neil; Catherine E. Wazniak; Margaret R. Mulholland (Harmful Algae, 2024)

Canopy-mediated microclimate refugia do not match narrow regeneration niches in a managed dry conifer forest - Edward M. Hill; Jeffery B. Cannon; Seth Ex; Troy W. Ocheltree; Miranda D. Redmond (Forest Ecology and Management, 2024)

Closing the gap between existing large‐area imaging research and marine conservation needs - Orion S. McCarthy; Kanisha Contractor; Will F. Figueira; Arthur C. R. Gleason; T. Shay Viehman; Clinton B. Edwards; Stuart A. Sandin (Conservation Biology, 2024)
Emerging technology has immense potential to increase the scale and efficiency of marine conservation. One such technology is large‐area imaging (LAI), which relies on structure‐from‐motion photogrammetry to create composite products, including 3‐dimensional (3‐D) environmental models, that are larger in spatial extent than the individual images used to create them. Use of LAI has become widespread in certain fields of marine science, primarily to measure the 3D structure of benthic ecosystems and track change over time. However, the use of LAI in the field of marine conservation appears limited. We conducted a review of the coral reef literature on the use of LAI to identify research themes and regional trends in applications of this technology. We also surveyed 135 coral reef scientists and conservation practitioners to determine community familiarity with LAI, evaluate barriers practitioners face in using LAI, and identify applications of LAI believed to be most exciting or relevant to coral conservation. Adoption of LAI was limited primarily to researchers at institutions based in advanced economies and was applied infrequently to conservation, although conservation practitioners and survey respondents from emerging economies indicated they expect to use LAI in the future. Our results revealed disconnect between current LAI research topics and conservation priorities identified by practitioners, highlighting the need for more diverse, conservation‐relevant research using LAI. We provide recommendations for how early adopters of LAI (typically Global North scientists from well‐resourced institutions) can facilitate access to this conservation technology. These recommendations include developing training resources, creating partnerships for data storage and analysis, publishing standard operating procedures for LAI workflows, standardizing methods, developing tools for efficient data extraction from LAI products, and conducting conservation‐relevant research using LAI.

The underwater soundscape of the North Sea - F. Basan; J.-G. Fischer; R. Putland; J. Brinkkemper; C.A.F. de Jong; B. Binnerts; A. Norro; D. Kühnel; L.-A. Ødegaard; M. Andersson; E. Lalander; J. Tougaard; et al. (Marine Pollution Bulletin, 2024)

Ammonia and aquatic ecosystems – A review of global sources, biogeochemical cycling, and effects on fish - Thea M. Edwards; Holly J. Puglis; Douglas B. Kent; Jonathan López Durán; Lillian M. Bradshaw; Aïda M. Farag (Science of The Total Environment, 2024)

Muller’s genetic load/species extinction hypothesis - Edward J. Calabrese; Paul B. Selby (Environmental Research, 2024)

Comet assay and hormesis - Edward J. Calabrese; Paul B. Selby (Environmental Pollution, 2024)

Shifts in bacterial traits under chronic nitrogen deposition align with soil processes in arbuscular, but not ectomycorrhizal‐associated trees - Juan Piñeiro; Chansotheary Dang; Jeth G. V. Walkup; Teagan Kuzniar; Rachel Winslett; Steven J. Blazewicz; Zachary B. Freedman; Edward Brzostek; Ember M. Morrissey (Global Change Biology, 2024)
Nitrogen (N) deposition increases soil carbon (C) storage by reducing microbial activity. These effects vary in soil beneath trees that associate with arbuscular (AM) and ectomycorrhizal (ECM) fungi. Variation in carbon C and N uptake traits among microbes may explain differences in soil nutrient cycling between mycorrhizal associations in response to high N loads, a mechanism not previously examined due to methodological limitations. Here, we used quantitative Stable Isotope Probing (qSIP) to measure bacterial C and N assimilation rates from an added organic compound, which we conceptualize as functional traits. As such, we applied a trait‐based approach to explore whether variation in assimilation rates of bacterial taxa can inform shifts in soil function under chronic N deposition. We show taxon‐specific and community‐wide declines of bacterial C and N uptake under chronic N deposition in both AM and ECM soils. N deposition‐induced reductions in microbial activity were mirrored by declines in soil organic matter mineralization rates in AM but not ECM soils. Our findings suggest C and N uptake traits of bacterial communities can predict C cycling feedbacks to N deposition in AM soils, but additional data, for instance on the traits of fungi, may be needed to connect microbial traits with soil C and N cycling in ECM systems. Our study also highlights the potential of employing qSIP in conjunction with trait‐based analytical approaches to inform how ecological processes of microbial communities influence soil functioning.

Diverse pathways for climate resilience in marine fishery systems - Jacob G. Eurich; Whitney R. Friedman; Kristin M. Kleisner; Lily Z. Zhao; Christopher M. Free; Meghan Fletcher; Julia G. Mason; Kanae Tokunaga; Alba Aguion; Andrea Dell'Apa; Mark Dickey‐Collas; Rod Fujita; et al. (Fish and Fisheries, 2024)
Both the ecological and social dimensions of fisheries are being affected by climate change. As a result, policymakers, managers, scientists and fishing communities are seeking guidance on how to holistically build resilience to climate change. Numerous studies have highlighted key attributes of resilience in fisheries, yet concrete examples that explicitly link these attributes to social‐ecological outcomes are lacking. To better understand climate resilience, we assembled 18 case studies spanning ecological, socio‐economic, governance and geographic contexts. Using a novel framework for evaluating 38 resilience attributes, the case studies were systematically assessed to understand how attributes enable or inhibit resilience to a given climate stressor. We found population abundance, learning capacity, and responsive governance were the most important attributes for conferring resilience, with ecosystem connectivity, place attachment, and accountable governance scoring the strongest across the climate‐resilient fisheries. We used these responses to develop an attribute typology that describes robust sources of resilience, actionable priority attributes and attributes that are case specific or require research. We identified five fishery archetypes to guide stakeholders as they set long‐term goals and prioritize actions to improve resilience. Lastly, we found evidence for two pathways to resilience: (1) building ecological assets and strengthening communities, which we observed in rural and small‐scale fisheries, and (2) building economic assets and improving effective governance, which was demonstrated in urban and wealthy fisheries. Our synthesis presents a novel framework that can be directly applied to identify approaches, pathways and actionable levers for improving climate resilience in fishery systems.

The relative influence of temperature and ontogeny on groundfish distribution varies across life stages - Lingbo Li; Anne B. Hollowed; Edward D. Cokelet; Aimee A. Keller; Steve J. Barbeaux; Michelle M. McClure; Wayne A. Palsson (Fish and Fisheries, 2024)
Distributional changes for fish populations may be difficult to interpret since temperature responses are often confounded with ontogenetic shifts. However, the relative importance of these two types of fish movement (temperature responses and ontogenetic shifts) to population distribution remains largely unstudied. This study presents the first attempt to compare the two types of movement in depth, latitude and longitude for 10 abundant groundfish species across size class and subregion. We utilized large, quality‐controlled datasets from random depth‐stratified, bottom trawl surveys consistently conducted during the summer along NE Pacific shelf from 1996 to 2015. We show that the size structure of each species varied across years and subregions with dramatically strong or poor recruitments for some species in 2015 during a marine heatwave. Principal component analysis (PCA) demonstrated that ontogenetic shifts in depth represented the primary movement pattern while temperature responses in latitude and longitude constituted a major, but a secondary pattern. Re‐run by size class, PCA results further showed that the influence of temperature and ontogeny on population distribution varied by size classes with greater ontogenetic shifts in smaller fish and elevated temperature responses in larger fish. We further show substantial ontogeny‐induced movements by depth, latitude and longitude with high variability among species and subregions. Our analyses suggest that failing to account for size structure can lead to serious misinterpretation of population distributional changes in all three dimensions: depth, latitude and longitude for populations with or without episodic recruitments.

Reinstatement and expansion of the genus Anatherum (Andropogoneae, Panicoideae, Poaceae) - Maria S. Vorontsova; Kurt B. Petersen; Patrick Minx; Taylor M. Aubuchon-Elder; M. Cinta Romay; Edward S. Buckler; Elizabeth A. Kellogg (Systematics and Biodiversity, 2023)

A globally integrated structure of taxonomy to support biodiversity science and conservation - Emily L. Sandall; Aurore A. Maureaud; Robert Guralnick; Melodie A. McGeoch; Yanina V. Sica; Matthew S. Rogan; Douglas B. Booher; Robert Edwards; Nico Franz; Kate Ingenloff; Maisha Lucas; Charles J. Marsh; et al. (Trends in Ecology & Evolution, 2023)

Hermann Muller and his LNT scientific and policy leadership: Private communication reveals uncertainties - Edward J. Calabrese; Paul B. Selby (Science of The Total Environment, 2023)

Temporal Patterns of Diet and Physical Activity and of Diet Alone Have More Numerous Relationships With Health and Disease Status Indicators Compared to Temporal Patterns of Physical Activity Alone - Luotao Lin; Jiaqi Guo; Anindya Bhadra; Saul B. Gelfand; Edward J. Delp; Elizabeth A. Richards; Erin Hennessy; Heather A. Eicher-Miller (Journal of the Academy of Nutrition and Dietetics, 2023)

Development of nitrogen-doped graphene/MOF nanocomposites towards adsorptive removal of Cr(VI) from the wastewater of the Herbert Bickley treatment works - Tshireletso M. Madumo; Sithembela A. Zikalala; Nozipho N. Gumbi; Shivani B. Mishra; Bulelwa Ntsendwana; Edward N. Nxumalo (Environmental Nanotechnology, Monitoring & Management, 2023)

Modulating signalling lifetime to optimise a prototypical animal opsin for optogenetic applications - Jessica Rodgers; Phillip Wright; Edward R. Ballister; Rebecca B. Hughes; Riccardo Storchi; Jonathan Wynne; Franck P. Martial; Robert J. Lucas (Pflügers Archiv - European Journal of Physiology, 2023)
Animal opsins are light activated G-protein-coupled receptors, capable of optogenetic control of G-protein signalling for research or therapeutic applications. Animal opsins offer excellent photosensitivity, but their temporal resolution can be limited by long photoresponse duration when expressed outside their native cellular environment. Here, we explore methods for addressing this limitation for a prototypical animal opsin (human rod opsin) in HEK293T cells. We find that the application of the canonical rhodopsin kinase (GRK1)/visual arrestin signal termination mechanism to this problem is complicated by a generalised suppressive effect of GRK1 expression. This attenuation can be overcome using phosphorylation-independent mutants of arrestin, especially when these are tethered to the opsin protein. We further show that point mutations targeting the Schiff base stability of the opsin can also reduce signalling lifetime. Finally, we apply one such mutation (E122Q) to improve the temporal fidelity of restored visual responses following ectopic opsin expression in the inner retina of a mouse model of retinal degeneration ( rd1 ). Our results reveal that these two strategies (targeting either arrestin binding or Schiff-base hydrolysis) can produce more time-delimited opsin signalling under heterologous expression and establish the potential of this approach to improve optogenetic performance.

How self-interest and deception led to the adoption of the linear non-threshold dose response (LNT) model for cancer risk assessment - Paul B. Selby; Edward J. Calabrese (Science of The Total Environment, 2023)

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Ecosystem feedbacks constrain the effect of day‐to‐day weather variability on land–atmosphere carbon exchange - Edward B. Rastetter; Kevin L. Griffin; Bonnie L. Kwiatkowski; George W. Kling (Global Change Biology, 2023)
Whole‐ecosystem interactions and feedbacks constrain ecosystem responses to environmental change. The effects of these constraints on responses to climate trends and extreme weather events have been well studied. Here we examine how these constraints respond to changes in day‐to‐day weather variability without changing the long‐term mean weather. Although environmental variability is recognized as a critical factor affecting ecological function, the effects of climate change on day‐to‐day weather variability and the resultant impacts on ecosystem function are still poorly understood. Changes in weather variability can alter the mean rates of individual ecological processes because many processes respond non‐linearly to environmental drivers. We assessed how these individual‐process responses to changes in day‐to‐day weather variability interact with one another at an ecosystem level. We examine responses of arctic tundra to changes in weather variability using stochastic simulations of daily temperature, precipitation, and light to drive a biogeochemical model. Changes in weather variability altered ecosystem carbon, nitrogen, and phosphorus stocks and cycling rates in our model. However, responses of some processes (e.g., respiration) were inconsistent with expectations because ecosystem feedbacks can moderate, or even reverse, direct process responses to weather variability. More weather variability led to greater carbon losses from land to atmosphere; less variability led to higher carbon sequestration on land. The magnitude of modeled ecosystem response to weather variability was comparable to that predicted for the effects of climate mean trends by the end of the century.

Experimental sintering of crystal-rich rhyolitic ash at high fluid pressures with implications for degassing of magma - Rachel Blandon; James E. Gardner; Fabian B. Wadsworth; Edward W. Llewellin; Jérémie Vasseur (Bulletin of Volcanology, 2023)

Light to moderate long-term grazing enhances ecosystem carbon across a broad climatic gradient in northern temperate grasslands - Edward W. Bork; Daniel B. Hewins; Eric G. Lamb; Cameron N. Carlyle; Mark P. Lyseng; Scott X. Chang; Michael J. Alexander; Walter D. Willms; Majid Iravani (Science of The Total Environment, 2023)

Avian biodiversity losses from grazing of high Andean páramo - Simon C. Mills; Edicson Parra Sanchez; Jacob B. Socolar; Chris Bousfield; Bryn Coffey; Jos Barlow; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; David P. Edwards (Biological Conservation, 2023)

Wildlife rehabilitation records reveal impacts of anthropogenic activities on wildlife health - Tara K. Miller; Karra Pierce; Edward E. Clark; Richard B. Primack (Biological Conservation, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Muller mistakes: The linear no-threshold (LNT) dose response and US EPA’s cancer risk assessment policies and practices - Edward J. Calabrese; Paul B. Selby (Chemico-Biological Interactions, 2023)

Analysis of electrical stimulation and voluntary muscle contraction on skeletal muscle oxygen uptake and mitochondrial recovery using near-infrared spectroscopy - Edward Z. Pelka; B. Ryan Davis; Patrick M. Tomko; John McDaniel (European Journal of Applied Physiology, 2023)

Acute inhalation of tungsten particles results in early signs of cardiac injury - Sage Templeton; Charlotte M. McVeigh; Colin Nguyen; Russell Hunter; David Scieszka; Guy W. Herbert; Edward B. Barr; Rui Liu; Haiwei Gu; Barry E. Bleske; Matthew J. Campen; Alicia M. Bolt (Toxicology Letters, 2023)

Incorporating caudate species susceptibilities and climate change into models of Batrachochytrium salamandrivorans risk in the United States of America - Matthew Grisnik; Matthew J. Gray; Jonah Piovia-Scott; Edward Davis Carter; William B. Sutton (Biological Conservation, 2023)

Variability in composition of parrotfish bite scars across space and over time on a central Pacific atoll - Jonathan A. Charendoff; Clinton B. Edwards; Nicole E. Pedersen; Vid Petrovic; Brian Zgliczynski; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2023)
Parrotfishes are conspicuous herbivores, microvores, and detritivores in coral reef ecosystems, and the impacts of their feeding, particularly their capacity to expose reef carbonate, have received much attention. In many cases, parrotfish assemblages have been shown to control algal proliferation and promote the settlement of corals and crustose coralline algae (CCA). In extreme cases, high densities of parrotfishes may negatively affect net reef accretion through bioerosion and targeted coral predation. Most evidence describing the impacts of parrotfish foraging on benthic community structure is based upon correlations between benthic composition and parrotfish behavior or abundance, with much less known about process-based change of individual parrotfish bite scars through time. Here, we estimated parrotfish bite selectivity and determined the change in benthic composition within parrotfish bite scars relative to change in the overall reefscape using data collected over a 12-month duration from the fore reef habitat at Palmyra Atoll. We identified 2150 parrotfish bite scars which appeared most frequently on turf algae covered substrata but also on coral, CCA, and encrusting macroalgae. Of those bites taken on live coral, 96% of scars returned to live coral within 12 months. Notably, adult coral survivorship in bite scars was higher than at randomly sampled coral-covered locations not affected by parrotfish bites. The exposed substrate within bite scars was most commonly colonized by the dominant benthic functional group in the area immediately surrounding the scar. We found little evidence of coral recruitment to bite scars (1/2150); however, CCA growth on bites initially on turf algae increased from 18.4 to 32.9% across the two time intervals. Our results suggest that benthic areas affected by parrotfish bites were more likely to undergo a successional shift to a more calcified state relative to unaffected benthic areas, indicating that parrotfish grazing helps maintain highly calcified coral reef ecosystems.

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

PALEO‐PGEM‐Series : A spatial time series of the global climate over the last 5 million years ( Plio‐Pleistocene ) - Elisa Barreto; Philip B. Holden; Neil R. Edwards; Thiago F. Rangel (Global Ecology and Biogeography, 2023)
Motivation Climate change plays an important role in the generation and maintenance of biodiversity by driving processes such as diversification and range shifts. As a result, biodiversity patterns are often found to carry the imprints of palaeoclimatic changes. However, we still know little about the spatial and temporal variation in climate over the scale of millennia affecting eco‐evolutionary dynamics, mostly because of the scarcity of user‐friendly and freely available spatio‐temporal palaeoclimate series at such temporal scales. Here, we address this gap by presenting PALEO‐PGEM‐Series, a global spatio‐temporal dataset of the last 5 Myr, with 1 kyr resolution, spatially downscaled from emulations performed with the intermediate‐complexity atmosphere–ocean general circulation model PALEO‐PGEM. PALEO‐PGEM‐Series holds the potential to advance our understanding of the mechanisms behind the strong relationship between biodiversity and climate, a pressing need given projected biodiversity responses to anthropogenic climatic change. Main Types of Variables Contained Spatio‐temporal series of monthly temperature and precipitation and 17 derived bioclimatic variables over the Pliocene–Pleistocene, along with standard error estimates from multiple runs of the emulator. Spatial Location and Grain Global landmasses, at 1° × 1°. Time Period and Grain Last 5 Myr at 1000 year resolution. Major Taxa and Level of Measurement Not applicable. Software Format Tab‐delimited text files and accompanying R code to derive bioclimatic variables.

Simulated effects of cover crops with no-tillage on soil and crop productivity in rainfed semi-arid cotton production systems - Jasdeep Singh; Srinivasulu Ale; Paul B. DeLaune; Edward M. Barnes (Soil and Tillage Research, 2023)

Heat stress in horses: a literature review - Hyungsuk Kang; Rebeka R. Zsoldos; Albert Sole-Guitart; Edward Narayan; A. Judith Cawdell-Smith; John B. Gaughan (International Journal of Biometeorology, 2023)
Healthy adult horses can balance accumulation and dissipation of body heat to maintain their body temperature between 37.5 and 38.5 °C, when they are in their thermoneutral zone (5 to 25 °C). However, under some circumstances, such as following strenuous exercise under hot, or hot and humid conditions, the accumulation of body heat exceeds dissipation and horses can suffer from heat stress. Prolonged or severe heat stress can lead to anhidrosis, heat stroke, or brain damage in the horse. To ameliorate the negative effects of high heat load in the body, early detection of heat stress and immediate human intervention is required to reduce the horse’s elevated body temperature in a timely manner. Body temperature measurement and deviations from the normal range are used to detect heat stress. Rectal temperature is the most commonly used method to monitor body temperature in horses, but other body temperature monitoring technologies, percutaneous thermal sensing microchips or infrared thermometry, are currently being studied for routine monitoring of the body temperature of horses as a more practical alternative. When heat stress is detected, horses can be cooled down by cool water application, air movement over the horse (e.g., fans), or a combination of these. The early detection of heat stress and the use of the most effective cooling methods is important to improve the welfare of heat stressed horses.

Dissolved N2O concentrations in oil palm plantation drainage in a peat swamp of Malaysia - Kazuya Nishina; Lulie Melling; Sakae Toyoda; Masayuki Itoh; Kotaro Terajima; Joseph W.B. Waili; Guan X. Wong; Frankie Kiew; Edward B. Aeries; Ryuichi Hirata; Yoshiyuki Takahashi; Takashi Onodera (Science of The Total Environment, 2023)

Embryonic exposure to PFAS causes long-term, compound-specific behavioral alterations in zebrafish - Andrew B. Hawkey; Mikayla Mead; Sarabesh Natarajan; Anas Gondal; Olivia Jarrett; Edward D. Levin (Neurotoxicology and Teratology, 2023)

Developmental exposure of zebrafish to neonicotinoid pesticides: Long-term effects on neurobehavioral function - Andrew B. Hawkey; Dilanaz Unal; Zade R. Holloway; Edward D. Levin (NeuroToxicology, 2023)

Meta-analysis of metal nanoparticles degrading pesticides: what parameters are relevant? - Wence Herrera; Joelis Vera; Humberto Aponte; Edward Hermosilla; Paola Fincheira; Javiera Parada; Gonzalo Tortella; Amedea B. Seabra; Maria Cristina Diez; Olga Rubilar (Environmental Science and Pollution Research, 2023)

Re-framing deer herbivory as a natural disturbance regime with ecological and socioeconomic outcomes in the eastern United States - Brice B. Hanberry; Edward K. Faison (Science of The Total Environment, 2023)

Biotinylation of reducing and non-reducing termini to create plug-and-play polysaccharides - Nimisha Mohandas; Patrick J.B. Edwards; Lisa M. Kent; Geoffrey B. Jameson; Martin A.K. Williams (Carbohydrate Polymers, 2023)

Updated guidelines for gene nomenclature in wheat - S. A. Boden; R. A. McIntosh; C. Uauy; S. G. Krattinger; J. Dubcovsky; W. J. Rogers; X. C. Xia; E. D. Badaeva; A. R. Bentley; G. Brown-Guedira; M. Caccamo; L. Cattivelli; et al. (Theoretical and Applied Genetics, 2023)
Key message Here, we provide an updated set of guidelines for naming genes in wheat that has been endorsed by the wheat research community. Abstract The last decade has seen a proliferation in genomic resources for wheat, including reference- and pan-genome assemblies with gene annotations, which provide new opportunities to detect, characterise, and describe genes that influence traits of interest. The expansion of genetic information has supported growth of the wheat research community and catalysed strong interest in the genes that control agronomically important traits, such as yield, pathogen resistance, grain quality, and abiotic stress tolerance. To accommodate these developments, we present an updated set of guidelines for gene nomenclature in wheat. These guidelines can be used to describe loci identified based on morphological or phenotypic features or to name genes based on sequence information, such as similarity to genes characterised in other species or the biochemical properties of the encoded protein. The updated guidelines provide a flexible system that is not overly prescriptive but provides structure and a common framework for naming genes in wheat, which may be extended to related cereal species. We propose these guidelines be used henceforth by the wheat research community to facilitate integration of data from independent studies and allow broader and more efficient use of text and data mining approaches, which will ultimately help further accelerate wheat research and breeding.

Survival of epithelial ovarian cancer in Black women: a society to cell approach in the African American cancer epidemiology study (AACES) - Joellen M. Schildkraut; Courtney Johnson; Lauren F. Dempsey; Bo Qin; Paul Terry; Maxwell Akonde; Edward S. Peters; Hannah Mandle; Michele L. Cote; Lauren Peres; Patricia Moorman; Ann G. Schwartz; et al. (Cancer Causes & Control, 2023)
Purpose The causes for the survival disparity among Black women with epithelial ovarian cancer (EOC) are likely multi-factorial. Here we describe the African American Cancer Epidemiology Study (AACES), the largest cohort of Black women with EOC. Methods AACES phase 2 (enrolled 2020 onward) is a multi-site, population-based study focused on overall survival (OS) of EOC. Rapid case ascertainment is used in ongoing patient recruitment in eight U.S. states, both northern and southern. Data collection is composed of a survey, biospecimens, and medical record abstraction. Results characterizing the survival experience of the phase 1 study population (enrolled 2010–2015) are presented. Results Thus far, ~ 650 patients with EOC have been enrolled in the AACES. The five-year OS of AACES participants approximates those of Black women in the Surveillance Epidemiology and End Results (SEER) registry who survive at least 10-month past diagnosis and is worse compared to white women in SEER, 49 vs. 60%, respectively. A high proportion of women in AACES have low levels of household income (45% < $25,000 annually), education (51% ≤ high school education), and insurance coverage (32% uninsured or Medicaid). Those followed annually differ from those without follow-up with higher levels of localized disease (28 vs 24%) and higher levels of optimal debulking status (73 vs 67%). Conclusion AACES is well positioned to evaluate the contribution of social determinants of health to the poor survival of Black women with EOC and advance understanding of the multi-factorial causes of the ovarian cancer survival disparity in Black women.

Urban heat island effect-related mortality under extreme heat and non-extreme heat scenarios: A 2010–2019 case study in Hong Kong - Janice Y. Ho; Yuan Shi; Kevin K.L. Lau; Edward Y.Y. Ng; Chao Ren; William B. Goggins (Science of The Total Environment, 2023)

Manhattan Project genetic studies: Flawed research discredits LNT recommendations - Edward J. Calabrese; Evgenios Agathokleous; James Giordano; Paul B. Selby (Environmental Pollution, 2023)

The National Conference on Health Disparities Student Research Forum - Marvella E. Ford; Angela M. Malek; Erica Martino; Latecia Abraham-Hilaire; Oluwole Ariyo; Dana Burshell; Gloria Callwood; Laura Campbell; Kimberly Cannady; Courtney Chavis; Brittney Crawford; Andie Edwards; et al. (Journal of Cancer Education, 2023)
The annual National Conference on Health Disparities (NCHD) was launched in 2000. It unites health professionals, researchers, community leaders, and government officials, and is a catalyzing force in developing policies, research interventions, and programs that address prevention, social determinants, health disparities, and health equity. The NCHD Student Research Forum (SRF) was established in 2011 at the Medical University of South Carolina to build high-quality biomedical research presentation capacity in primarily underrepresented undergraduate and graduate/professional students. This paper describes the unique research training and professional development aspects of the NCHD SRF. These include guidance in abstract development, a webinar on presentation techniques and methods, a vibrant student-centric conference, and professional development workshops on finding a mentor and locating scholarship/fellowship funding, networking, and strategies for handling ethical issues in research with mentors. Between 2011 and 2018, 400 undergraduate and graduate/professional students participated in the NCHD SRF. Most students were women (80.5%). Approximately half were African American or black (52.3%), 18.0% were white, and 21.3% were of Hispanic/Latinx ethnicity. The NCHD SRF is unique in several ways. First, it provides detailed instructions on developing a scientific abstract, including content area examples. Second, it establishes a mandatory pre-conference training webinar demonstrating how to prepare a scientific poster. Third, it works with the research mentors, faculty advisors, department chairs, and deans to help identify potential sources of travel funding for students with accepted abstracts. These features make the NCHD SRF different from many other conferences focused on students’ scientific presentations.

SCIP: software for efficient clinical interpretation of copy number variants detected by whole-genome sequencing - Qiliang Ding; Cherith Somerville; Roozbeh Manshaei; Brett Trost; Miriam S. Reuter; Kelsey Kalbfleisch; Kaitlin Stanley; John B. A. Okello; S. Mohsen Hosseini; Eriskay Liston; Meredith Curtis; Mehdi Zarrei; et al. (Human Genetics, 2023)
Copy number variants (CNVs) represent major etiologic factors in rare genetic diseases. Current clinical CNV interpretation workflows require extensive back-and-forth with multiple tools and databases. This increases complexity and time burden, potentially resulting in missed genetic diagnoses. We present the Suite for CNV Interpretation and Prioritization (SCIP), a software package for the clinical interpretation of CNVs detected by whole-genome sequencing (WGS). The SCIP Visualization Module near-instantaneously displays all information necessary for CNV interpretation (variant quality, population frequency, inheritance pattern, and clinical relevance) on a single page—supported by modules providing variant filtration and prioritization. SCIP was comprehensively evaluated using WGS data from 1027 families with congenital cardiac disease and/or autism spectrum disorder, containing 187 pathogenic or likely pathogenic (P/LP) CNVs identified in previous curations. SCIP was efficient in filtration and prioritization: a median of just two CNVs per case were selected for review, yet it captured all P/LP findings (92.5% of which ranked 1st). SCIP was also able to identify one pathogenic CNV previously missed. SCIP was benchmarked against AnnotSV and a spreadsheet-based manual workflow and performed superiorly than both. In conclusion, SCIP is a novel software package for efficient clinical CNV interpretation, substantially faster and more accurate than previous tools (available at https://github.com/qd29/SCIP , a video tutorial series is available at https://bit.ly/SCIPVideos ).

Abolishment of morphology-based taxa and change to binomial species names: 2022 taxonomy update of the ICTV bacterial viruses subcommittee - Dann Turner; Andrey N. Shkoporov; Cédric Lood; Andrew D. Millard; Bas E. Dutilh; Poliane Alfenas-Zerbini; Leonardo J. van Zyl; Ramy K. Aziz; Hanna M. Oksanen; Minna M. Poranen; Andrew M. Kropinski; Jakub Barylski; et al. (Archives of Virology, 2023)
This article summarises the activities of the Bacterial Viruses Subcommittee of the International Committee on Taxonomy of Viruses for the period of March 2021−March 2022. We provide an overview of the new taxa proposed in 2021, approved by the Executive Committee, and ratified by vote in 2022. Significant changes to the taxonomy of bacterial viruses were introduced: the paraphyletic morphological families Podoviridae , Siphoviridae , and Myoviridae as well as the order Caudovirales were abolished, and a binomial system of nomenclature for species was established. In addition, one order, 22 families, 30 subfamilies, 321 genera, and 862 species were newly created, promoted, or moved.

High summer temperatures are associated with poorer performance of underyearling Atlantic salmon ( Salmo salar ) in upland streams - Fionn R. Bernthal; Ben W. Seaman; Edward Rush; John D. Armstrong; Darryl McLennan; Keith H. Nislow; Neil B. Metcalfe (Journal of Fish Biology, 2023)
Future warming scenarios are predicted to result in an increased frequency of high, and potentially stressful, temperatures in aquatic ecosystems. Here we examined whether the performance of wild underyearling Atlantic salmon ( Salmo salar ) in Scottish streams stocked with identical egg densities was influenced by thermal stress. Biomass and density declined with degree hours exceeding 23°C, indicating apparent mortality or emigration as a possible result of exposure to high temperatures. These results strengthen the need for further action such as riparian tree planting to reduce stream summer temperatures.

Plant defense synergies and antagonisms affect performance of specialist herbivores of common milkweed - Collin B. Edwards; Stephen P. Ellner; Anurag A. Agrawal (Ecology, 2023)
As a general rule, plants defend against herbivores with multiple traits. The defense synergy hypothesis posits that some traits are more effective when co‐expressed with others compared to their independent efficacy. However, this hypothesis has rarely been tested outside of phytochemical mixtures, and seldom under field conditions. We tested for synergies between multiple defense traits of common milkweed ( Asclepias syriaca ) by assaying the performance of two specialist chewing herbivores on plants in natural populations. We employed regression and a novel application of random forests to identify synergies and antagonisms between defense traits. We found the first direct empirical evidence for two previously hypothesized defense synergies in milkweed (latex by secondary metabolites, latex by trichomes) and identified numerous other potential synergies and antagonisms. Our strongest evidence for a defense synergy was between leaf mass per area and low nitrogen content; given that these “leaf economic” traits typically covary in milkweed, a defense synergy could reinforce their co‐expression. We report that each of the plant defense traits showed context‐dependent effects on herbivores, and increased trait expression could well be beneficial to herbivores for some ranges of observed expression. The novel methods and findings presented here complement more mechanistic approaches to the study of plant defense diversity and provide some of the best evidence to date that multiple classes of plant defense synergize in their impact on insects. Plant defense synergies against highly specialized herbivores, as shown here, are consistent with ongoing reciprocal evolution between these antagonists.

Coral disease outbreak at the remote Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Michael S. Studivan; Ian C. Enochs; Adrienne M. S. Correa; Nicole Besemer; Ryan J. Eckert; Kimberly Edwards; Ryan Hannum; Xinping Hu; Marissa Nuttall; Kelly O’Connell; Ana M. Palacio-Castro; et al. (Frontiers in Marine Science, 2023)
East and West Flower Garden Bank (FGB) are part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwest Gulf of Mexico. This geographically-isolated reef system contains extensive coral communities with the highest coral cover (>50%) in the continental United States due, in part, to their remoteness and depth, and have historically exhibited low incidence of coral disease and bleaching despite ocean warming. Yet in late August 2022, disease-like lesions on seven coral species were reported during routine monitoring surveys on East and West FGB (2.1–2.6% prevalence). A series of rapid response cruises were conducted in September and October 2022 focused on 1) characterizing signs and epidemiological aspects of the disease across FGB and within long-term monitoring sites, 2) treating affected coral colonies with Base 2B plus amoxicillin, and 3) collecting baseline images through photostations and photomosaics. Marginal and/or multi-focal lesions and tissue loss were observed, often associated with substantial fish and invertebrate predation, affecting the dominant coral species Pseudodiploria strigosa (7–8% lesion prevalence), Colpophyllia natans (11–18%), and Orbicella spp. (1%). Characterizing this disease event during its early epidemic phase at East and West FGB provides a critical opportunity to observe how coral disease functions in a relatively healthy coral ecosystem versus on reefs chronically affected by various stressors (e.g., Caribbean reefs adjacent to urban centers). Insights into the etiology, spread, and impacts of the disease can ultimately inform efforts to mitigate its effects on coral communities.

Irregular silviculture and stand structural effects on the plant community in an ancient semi-natural woodland - D.C. Alder; B. Edwards; A. Poore; J. Norrey; S.J. Marsden (Forest Ecology and Management, 2023)

Fine particulate matter and incident coronary heart disease events up to 10 years of follow-up among Deepwater Horizon oil spill workers - Dazhe Chen; Dale P. Sandler; Alexander P. Keil; Gerardo Heiss; Eric A. Whitsel; Gregory C. Pratt; Patricia A. Stewart; Mark R. Stenzel; Caroline P. Groth; Sudipto Banerjee; Tran B. Huynh; Jessie K. Edwards; et al. (Environmental Research, 2023)

Lipid Nanoparticles for Nucleic Acid Delivery to Endothelial Cells - Gary W. Liu; Edward B. Guzman; Nandita Menon; Robert S. Langer (Pharmaceutical Research, 2023)
Endothelial cells play critical roles in circulatory homeostasis and are also the gateway to the major organs of the body. Dysfunction, injury, and gene expression profiles of these cells can cause, or are caused by, prevalent chronic diseases such as diabetes, cardiovascular disease, and cancer. Modulation of gene expression within endothelial cells could therefore be therapeutically strategic in treating longstanding disease challenges. Lipid nanoparticles (LNP) have emerged as potent, scalable, and tunable carrier systems for delivering nucleic acids, making them attractive vehicles for gene delivery to endothelial cells. Here, we discuss the functions of endothelial cells and highlight some receptors that are upregulated during health and disease. Examples and applications of DNA, mRNA, circRNA, saRNA, siRNA, shRNA, miRNA, and ASO delivery to endothelial cells and their targets are reviewed, as well as LNP composition and morphology, formulation strategies, target proteins, and biomechanical factors that modulate endothelial cell targeting. Finally, we discuss FDA-approved LNPs as well as LNPs that have been tested in clinical trials and their challenges, and provide some perspectives as to how to surmount those challenges.

High sensitivity of tropical forest birds to deforestation at lower altitudes - Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Edicson Parra; Diego E. Martínez‐Revelo; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; David P. Edwards (Ecology, 2023)
Habitat conversion is a major driver of tropical biodiversity loss, but its effects are poorly understood in montane environments. While community‐level responses to habitat loss display strong elevational dependencies, it is unclear whether these arise via elevational turnover in community composition and interspecific differences in sensitivity or elevational variation in environmental conditions and proximity to thermal thresholds. Here we assess the relative importance of inter‐ and intraspecific variation across the elevational gradient by quantifying how 243 forest‐dependent bird species vary in sensitivity to landscape‐scale forest loss across a 3000‐m elevational gradient in the Colombian Andes. We find that species that live at lower elevations are strongly affected by loss of forest in the nearby landscape, while those at higher elevations appear relatively unperturbed, an effect that is independent of phylogeny. Conversely, we find limited evidence of intraspecific elevational gradients in sensitivity, with populations displaying similar sensitivities to forest loss, regardless of where they exist in a species' elevational range. Gradients in biodiversity response to habitat loss thus appear to arise via interspecific gradients in sensitivity rather than proximity to climatically limiting conditions.

Caught red handed: modeling and confirmation of the myeloperoxidase ceruloplasmin alpha-thrombin complex - Yana A. Zabrodskaya; Vladimir V. Egorov; Alexey V. Sokolov; Alexey V. Shvetsov; Yulia E. Gorshkova; Oleksandr I. Ivankov; Valeria A. Kostevich; Nikolay P. Gorbunov; Edward S. Ramsay; Natalya D. Fedorova; Andrey B. Bondarenko; Vadim B. Vasilyev (BioMetals, 2022)

Streptomyces spiramenti sp. nov., isolated from a deep-sea microbial mat - Rachel M. Loughran; Caitlin M. Diefendorf; Jassmine R. Reill-VanSise; Edward A. Mitchell; Oliver B. Vining; David A. Gallegos; Gregory Miller; Marc J. Koyack; David K. Oline; Orion S. Rivers; Blake Ushijima; Jimmy H. Saw; et al. (Archives of Microbiology, 2022)

A growing crisis for One Health: Impacts of plastic pollution across layers of biological function - Margaret Morrison; Rafael Trevisan; Prabha Ranasinghe; Greg B. Merrill; Jasmine Santos; Alexander Hong; William C. Edward; Nishad Jayasundara; Jason A. Somarelli (Frontiers in Marine Science, 2022)
The global accumulation of plastic waste has reached crisis levels. The diverse and multilayered impacts of plastic on biological health prompts an evaluation of these effects from a One Health perspective, through which the complexity of these processes can be integrated and more clearly understood. Plastic particles ranging from nanometers to meters in size are found throughout every ecosystem on Earth, from the deepest marine trenches to the highest mountains. Plastic waste affects all layers of biological organization, from the molecular and cellular to the organismal, community, and ecosystem-levels. These effects are not only mediated by the physical properties of plastics, but also by the chemical properties of the plastic polymers, the thousands of additives combined with plastics during manufacturing, and the sorbed chemicals and microbes that are transported by the plastic waste. Using a One Health framework we provide an overview of the following themes: 1) ways in which plastic impacts global health across levels of biological organization, 2) how the effects of plastic interact between layers of biology, and 3) what knowledge gaps exist in understanding the effects of plastic within and between biological scales. We also propose potential solutions to address this growing crisis, with an emphasis on One Health perspectives that consider the oneness of animals, humans, and the environment.

Determinants and outcomes of bloodstream infections related to obesity - Felicity Edwards; Kate Glen; Patrick N. A. Harris; David L. Paterson; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Although obesity is a major healthcare problem that is increasing in many populations worldwide, there are limited studies that have examined its contribution to infectious diseases morbidity and mortality. The aim of this study was to examine the clinical determinants and outcomes of bloodstream infections among patients with obesity. All adults within the publicly funded healthcare system in Queensland, Australia, identified with a BSI during 2017–2019 were included and the presence of obesity was based on discharge International Classification of Diseases (ICD-10) codes. Clinical features, microbiology, and outcomes were compared among obese and non-obese subjects. A total of 24,602 incident BSI were identified among 21,613 Queensland residents; of which 4,579 (21.2%) and 17,034 (78.8%) were classified as obese or non-obese, respectively. Obese patients were less likely to have community associated infections and were more likely to be younger, female, have higher comorbidity scores, and have bone and joint or soft tissue infections as compared to non-obese subjects. Obese patients had a lower proportion of Escherichia coli BSI and higher proportions of b-haemolytic streptococci. Although obese patients had longer hospital admissions and more repeat incident BSI within 1 year, they had lower overall case fatality. In a logistic regression model, obesity was associated with a lower risk for 30-day case fatality (adjusted odds ratio 0.51, 95% confidence interval 0.45–0.58). Obesity is associated with significant differences in the determinants and outcome of BSI. Increasing rates of obesity is likely to influence the epidemiology of BSI in populations.

Magmatic origin for the massive sulfide ores in the sedimentary country rocks of mafic–ultramafic intrusions in the Midcontinent Rift System - Joshua M. Smith; Edward M. Ripley; Chusi Li; Steven B. Shirey; Erin K. Benson (Mineralium Deposita, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Cancer clinical trials in the Philippines - Michelle Ann B. Eala; Patricia Anne S. Basilio; Edward Christopher Dee; Reno Eufemon P. Cereno; Christian Daniel Ang; Nikko J. Magsanoc; Frederic Ivan L. Ting; Dennis L. Sacdalan (Cancer Causes & Control, 2022)

Population genomic structure in Goodman's mouse lemur reveals long‐standing separation of Madagascar's Central Highlands and eastern rainforests - George P. Tiley; Tobias van Elst; Helena Teixeira; Dominik Schüßler; Jordi Salmona; Marina B. Blanco; José M. Ralison; Blanchard Randrianambinina; Rodin M. Rasoloarison; Amanda R. Stahlke; Paul A. Hohenlohe; Lounès Chikhi; et al. (Molecular Ecology, 2022)
Madagascar's Central Highlands are largely composed of grasslands, interspersed with patches of forest. The historical perspective was that Madagascar's grasslands had anthropogenic origins, but emerging evidence suggests that grasslands were a component of the pre‐human Central Highlands vegetation. Consequently, there is now vigorous debate regarding the extent to which these grasslands have expanded due to anthropogenic pressures. Here, we shed light on the temporal dynamics of Madagascar's vegetative composition by conducting a population genomic investigation of Goodman's mouse lemur ( Microcebus lehilahytsara ; Cheirogaleidae). These small‐bodied primates occur both in Madagascar's eastern rainforests and in the Central Highlands, making them a valuable indicator species. Population divergences among forest‐dwelling mammals will reflect changes to their habitat, including fragmentation, whereas patterns of post‐divergence gene flow can reveal formerly wooded migration corridors. To explore these patterns, we used RADseq data to infer population genetic structure, demographic models of post‐divergence gene flow, and population size change through time. The results offer evidence that open habitats are an ancient component of the Central Highlands, and that widespread forest fragmentation occurred naturally during a period of decreased precipitation near the last glacial maximum. Models of gene flow suggest that migration across the Central Highlands has been possible from the Pleistocene through the recent Holocene via riparian corridors. Though our findings support the hypothesis that Central Highland grasslands predate human arrival, we also find evidence for human‐mediated population declines. This highlights the extent to which species imminently threatened by human‐mediated deforestation may already be vulnerable from paleoclimatic conditions.

A possible role for river restoration enhancing biodiversity through interaction with wildfire - Brittany E. Pugh; Megan Colley; Stephen J. Dugdale; Patrick Edwards; Rebecca Flitcroft; Andrés Holz; Matthew Johnson; Michela Mariani; Mickey Means‐Brous; Kate Meyer; Kevan B. Moffett; Lisa Renan; et al. (Global Ecology and Biogeography, 2022)
Background Historically, wildfire regimes produced important landscape‐scale disturbances in many regions globally. The “pyrodiversity begets biodiversity” hypothesis suggests that wildfires that generate temporally and spatially heterogeneous mosaics of wildfire severity and post‐burn recovery enhance biodiversity at landscape scales. However, river management has often led to channel incision that disconnects rivers from their floodplains, desiccating floodplain habitats and depleting groundwater. In conjunction with predicted increases in frequency, intensity and extent of wildfires under climate change, this increases the likelihood of deep, uniform burns that reduce biodiversity. Predicted synergy of river restoration and biodiversity increase Recent focus on floodplain re‐wetting and restoration of successional floodplain habitat mosaics, developed for river management and flood prevention, could reduce wildfire intensity in restored floodplains and make the burns less uniform, increasing climate‐change resilience; an important synergy. According to theory, this would also enhance biodiversity. However, this possibility is yet to be tested empirically. We suggest potential research avenues. Illustration and future directions We illustrate the interaction between wildfire and river restoration using a restoration project in Oregon, USA. A project to reconnect the South Fork McKenzie River and its floodplain suffered a major burn (“Holiday Farm” wildfire, 2020), offering a rare opportunity to study the interaction between this type of river restoration and wildfire; specifically, the predicted increases in pyrodiversity and biodiversity. Given the importance of river and wetland ecosystems for biodiversity globally, a research priority should be to increase our understanding of potential mechanisms for a “triple win” of flood reduction, wildfire alleviation and biodiversity promotion.

Genomic regions associated with resistance to soybean rust (Phakopsora pachyrhizi) under field conditions in soybean germplasm accessions from Japan, Indonesia and Vietnam - David R. Walker; Samuel C. McDonald; Donna K. Harris; H. Roger Boerma; James W. Buck; Edward J. Sikora; David B. Weaver; David L. Wright; James J. Marois; Zenglu Li (Theoretical and Applied Genetics, 2022)
Key message Eight soybean genomic regions, including six never before reported, were found to be associated with resistance to soybean rust ( Phakopsora pachyrhizi ) in the southeastern USA. Abstract Soybean rust caused by Phakopsora pachyrhizi is one of the most important foliar diseases of soybean [ Glycine max (L.) Merr.]. Although seven Rpp resistance gene loci have been reported, extensive pathotype variation in and among fungal populations increases the importance of identifying additional genes and loci associated with rust resistance. One hundred and ninety-one soybean plant introductions from Japan, Indonesia and Vietnam, and 65 plant introductions from other countries were screened for resistance to P. pachyrhizi under field conditions in the southeastern USA between 2008 and 2015. The results indicated that 84, 69, and 49% of the accessions from southern Japan, Vietnam or central Indonesia, respectively, had negative BLUP values, indicating less disease than the panel mean. A genome-wide association analysis using SoySNP50K Infinium BeadChip data identified eight genomic regions on seven chromosomes associated with SBR resistance, including previously unreported regions of Chromosomes 1, 4, 6, 9, 13, and 15, in addition to the locations of the Rpp3 and Rpp6 loci. The six unreported genomic regions might contain novel Rpp loci. The identification of additional sources of rust resistance and associated genomic regions will further efforts to develop soybean cultivars with broad and durable resistance to soybean rust in the southern USA.

Total Dental Occlusal Area as a Feeding Constraint Feature in Extant Walruses (Odobenus rosmarus), and Implications for the Evolution of Molluscivory in Odobenidae - Win N. F. McLaughlin; Caitlyn J. Boatman; Edward B. Davis; Samantha S. B. Hopkins (Journal of Mammalian Evolution, 2022)

Predicting larval alewife transport in Lake Michigan using hydrodynamic and Lagrangian particle dispersion models - Mark D. Rowe; Sara E. Prendergast; Karen M. Alofs; David B. Bunnell; Edward S. Rutherford; Eric J. Anderson (Limnology and Oceanography, 2022)
Several species of fish in large lakes and marine environments have a pelagic larval stage, and are subject to variable transport that can ultimately regulate survival and recruitment success. Alewife, Alosa pseudoharengus , are subject to transport by complex coastal currents during their pelagic larval stage (~ 30 d). We assessed backward‐trajectory simulations, consisting of a Lagrangian particle dispersion model linked to the Finite Volume Community Ocean Model, to estimate likely hatch locations of aged larval alewife collected from locations on both the eastern and western sides of Lake Michigan during July 2015. We used four deployments of three satellite‐tracked drifter buoys in coastal waters to assess model skill in estimating the origin of a drifter from its final location. We found that the trajectories of drifters varied greatly, depending on wind events and associated coastal transport processes, including upwelling/downwelling and coastal jet currents. In 2 of 12 cases, the backward trajectory simulations failed to predict the drifter origin, associated with transport of 170 km in a narrow coastal jet current. In the remaining 10 cases, the known drifter origin was within 3.5 km of the spatial patch of predicted possible origins for a scenario of horizontal diffusivity (188 m 2 s −1 ) consistent with the offshore model grid resolution. Modeled backward trajectories estimated that alewife originated from the same side of the lake where they were collected, within ~ 100 km of the collection site. Our paper demonstrates the utility of hydrodynamic models to estimate a region of origin for aged larval fish.

Three‐dimensional ontogenetic shifts of groundfish in the Northeast Pacific - Lingbo Li; Anne B. Hollowed; Edward D. Cokelet; Michelle M. McClure; Aimee A. Keller; Steve J. Barbeaux; Wayne A. Palsson (Fish and Fisheries, 2022)
It has been more than 100 years since fish were first described to move to deep waters as size increased, termed ‘Heincke's Law’. However, large‐scale studies on ontogenetic shifts are rare compared with increased reports of distributional changes in response to temperature, often confounded with the ontogenetic shifts. We fill this gap by examining the distribution of ten abundant groundfish species in three dimensions, depth, latitude and longitude, at 10‐cm size intervals within nine subregions of NE Pacific. Here, we utilized large, quality‐controlled datasets from random depth‐stratified, bottom trawl surveys consistently conducted during summer along the NE Pacific shelf from 1996 to 2015. Groundfish demonstrated complex ontogenetic movements in three dimensions across species, size class and subregion. In addition to the expected ontogenetic deepening, shoaling also occurred and some species demonstrated major ontogenetic shifts in longitude and/or latitude with limited changes in depth. Based on standardized ontogenetic shifts in three dimensions, our analyses show that there were significant differences in aggregate fish ontogenetic shifts between small (≤30 cm) and large (>30 cm) size groups. Small fish exhibited substantially larger ontogenetic shifts in depth than the large size group while both groups showed relatively small shifts in latitude and longitude. Our analyses strongly suggest that size structure and ontogenetic shifts should be included in the population distribution.

Fates of petroleum during the deepwater horizon oil spill: A chemistry perspective - Edward B. Overton; Puspa L. Adhikari; Jagoš R. Radović; Uta Passow (Frontiers in Marine Science, 2022)
We describe the initial bulk and compound specific composition of the liquid oil spilled during the Deepwater Horizon (DwH) disaster. The emphasis is on the target hydrocarbon compounds typically found in highest concentrations and on those of concern from a toxicological perspective (i.e., the target normal alkanes and isoprenoids, and PAHs on U.S. Environmental Protection Agency’s (EPA) priority list with their alkyl homolog compounds), and/or those relevant for forensic fingerprinting of spill residues (i.e., sulfur containing PAHs and biomarker compounds). Weathering changed the oil’s composition in various environmental compartments. These compositional changes and potential environmental impacts of the remaining weathered residues are presented in this paper. Biodegradation occurred in both surface and subsurface environments while photooxidation primarily modified and removed hydrocarbons in floating oil slicks. The volatile, soluble and highly labile C 1 to C 10 hydrocarbons were rapidly degraded in the water column and/or emitted to the atmosphere (evaporation). The semi-volatile hydrocarbons (labile C 10 to C 25 ) that remained in the water column and floating oil on the water’s surface were lost from oil residues during weathering. The heavy nonvolatile and insoluble hydrocarbons (recalcitrant C 25 +) were least affected by initial weathering processes in 2010. The composition of the residual oil fraction in surface floating oil was further altered by the addition of oil soluble oxy hydrocarbons produced from photooxidation. During 2011 and 2012 the resulting highly insoluble recalcitrant C 25 + oily residues remained on the shorelines, bottom sediments, or bound to suspended particulates in the water column, with detectable residues mostly returning to near pre-spill levels by 2015 to 2020. Some recalcitrant oil residues can still be found at various locations, including some coastal environments (e.g., marshes), or deep-water sediments, at very low levels, ten years after the spill.

Seismic site characterization with shear wave (SH) reflection and refraction methods - James A. Hunter; Heather L. Crow; William J. Stephenson; André J.-M. Pugin; Robert A. Williams; James B. Harris; Jack K. Odum; Edward W. Woolery (Journal of Seismology, 2022)
Reflection and critically refracted seismic methods use traveltime measurements of body waves propagating between a source and a series of receivers on the ground surface to calculate subsurface velocities. Body wave energy is refracted or reflected at boundaries where there is a change in seismic impedance, defined as the product of material density and seismic velocity. This article provides practical guidance on the use of horizontally propagating shear wave (SH-wave) refraction and reflection methods to determine shear wave velocity as a function of depth for near-surface seismic site characterizations. Method principles and the current state of engineering practice are reviewed, along with discussions of limitations and uncertainty assessments. Typical data collection procedures are described using basic survey equipment, along with information on more advanced applications and emerging technologies. Eight case studies provide examples of the techniques in real-world seismic site characterizations performed in a variety of geological settings.

Growth and survival rates of dispersing free embryos and settled larvae of pallid sturgeon (Scaphirhynchus albus) in the Missouri River, Montana and North Dakota - Patrick J. Braaten; Robert J. Holm; Jeffrey Powell; Edward J. Heist; Amy C. Buhman; Colt T. Holley; Aaron J. DeLonay; Tyler M. Haddix; Ryan H. Wilson; Robert B. Jacobson (Environmental Biology of Fishes, 2022)
We released nearly 1.0 million 1-day post-hatch (dph) and 5-dph pallid sturgeon ( Scaphirhynchus albus ) free embryos in the Missouri River on 1 July 2019 and sequentially captured survivors at multiple sites through a 240-km river reach to quantify daily growth and survival rates during the early life stages. Genetic analysis was used to assign captured fish to released family lots and known ages. Growth rate was similar (0.74–0.75 mm day −1 ) between the 1- and 5-dph age groups during the 3–4-day dispersal period when water temperature averaged 16.8 °C. Daily survival rate was 0.64 during 1–4 dph for the original 1-dph age group and 0.80 during 5–7 dph for the original 5-dph age group. Total survival during free embryo dispersal (hatch to 9 dph) was estimated as 0.0437. The transition from dispersing as free embryos to settling as benthic larvae was verified for fish originally released as 5 dph. Growth of settled larvae was quantified with a Gompertz model through 75 dph (9 September; 112 mm) when water temperature was 18.8–21.0 °C in the rearing areas. Settled larvae had an estimated daily survival rate of 0.96, and estimated total survival during 9–75 dph was 0.0714. This study provides the first empirical survival estimates for pallid sturgeon early life stages in natural settings and is one of few studies reporting similar information for other sturgeon species. Applications of this work extend to pallid sturgeon restoration programs where population models are being developed to predict recruitment potential and population responses to river management alternatives.

Benthic assemblages are more predictable than fish assemblages at an island scale - Stuart A. Sandin; Esmeralda Alcantar; Randy Clark; Ramón de León; Faisal Dilrosun; Clinton B. Edwards; Andrew J. Estep; Yoan Eynaud; Beverly J. French; Michael D. Fox; Dave Grenda; Scott L. Hamilton; et al. (Coral Reefs, 2022)
Decades of research have revealed relationships between the abundance of coral reef taxa and local conditions, especially at small scales. However, a rigorous test of covariation requires a robust dataset collected across wide environmental or experimental gradients. Here, we surveyed spatial variability in the densities of major coral reef functional groups at 122 sites along a 70 km expanse of the leeward, forereef habitat of Curaçao in the southern Caribbean. These data were used to test the degree to which spatial variability in community composition could be predicted based on assumed functional relationships and site-specific anthropogenic, physical, and ecological conditions. In general, models revealed less power to describe the spatial variability of fish biomass than cover of reef builders (R 2 of best-fit models: 0.25 [fish] and 0.64 [reef builders]). The variability in total benthic cover of reef builders was best described by physical (wave exposure and reef relief) and ecological (turf algal height and coral recruit density) predictors. No metric of anthropogenic pressure was related to spatial variation in reef builder cover. In contrast, total fish biomass showed a consistent (albeit weak) association with anthropogenic predictors (fishing and diving pressure). As is typical of most environmental gradients, the spatial patterns of both fish biomass density and reef builder cover were spatially autocorrelated. Residuals from the best-fit model for fish biomass retained a signature of spatial autocorrelation while the best-fit model for reef builder cover removed spatial autocorrelation, thus reinforcing our finding that environmental predictors were better able to describe the spatial variability of reef builders than that of fish biomass. As we seek to understand spatial variability of coral reef communities at the scale of most management units (i.e., at kilometer- to island-scales), distinct and scale-dependent perspectives will be needed when considering different functional groups.

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

A melting cryosphere constrains fish growth by synchronizing the seasonal phenology of river food webs - J. Ryan Bellmore; Jason B. Fellman; Eran Hood; Matthew R. Dunkle; Richard T. Edwards (Global Change Biology, 2022)
Mountain watersheds often contain a mosaic of glacier‐, snow‐, and rain‐fed streams that have distinct hydrologic, temperature, and biogeochemical regimes. However, as glaciers diminish and precipitation shifts from snow to rain, the physical and chemical characteristics that make glacial or snowmelt streams distinct from rain‐fed streams will fade. Among the unforeseen consequences of this hydrologic homogenization could be the loss of unique food webs that sustain aquatic consumers. To explore the impacts of a melting cryosphere on stream food webs, we parameterized an aquatic food web model with empirical physicochemical data from glacier‐, snow‐, and rain‐fed streams in southeast Alaska and used the model to simulate the seasonal biomass dynamics of aquatic primary producers and consumers and the growth of juvenile salmon. Model results suggest that glacier‐, snow‐, and rain‐fed streams exhibit seasonal asynchronies in the timing of biofilm and aquatic invertebrate abundance. Although warmer rain‐fed streams were more productive during the summer (June through September), colder glacial and snowmelt streams provided enhanced foraging and growth opportunities throughout the remainder of the year. For juvenile salmon that can track peaks in resource abundance within river networks, the loss of meltwater streams strongly constrained modeled growth opportunities by removing spatially and temporally distinct foraging habitats within a watershed. These findings suggest that climate change induced homogenization of high latitude river networks may result in the loss of unique food web dynamics, which could diminish the capacity of watersheds to sustain mobile consumers.

Microsatellite markers for 24 loci developed for genotyping eastern woodrats, Neotoma floridana - Tiffanie B. Atherton; Edward J. Heist; Clayton K. Nielsen (Conservation Genetics Resources, 2022)

Sustainable development outcomes of livelihood diversification in small‐scale fisheries - Matthew B. Roscher; Edward H. Allison; David J. Mills; Hampus Eriksson; Denis Hellebrandt; Neil L. Andrew (Fish and Fisheries, 2022)
Livelihood diversification is increasingly central to policy advice and investments in rural development and fisheries management. For small‐scale fishing communities in low‐ to middle‐income countries, more diverse livelihoods are generally hypothesized to reduce fishing pressure and vulnerabilities to external shocks and adverse trends while enabling people to construct routes out of poverty. Yet, evidence of impacts from livelihood diversification in small‐scale fisheries remains sparse. Our examination of the peer‐reviewed literature found substantial differences in how livelihood diversification is pursued, and in the realized outcomes from the process of diversification. Studies describing diversified livelihoods were almost as likely to report that livelihoods were not improved or that outcomes were mixed (54% combined) as they were to report improved livelihood outcomes (45%). Furthermore, one of the main theoretical drivers behind the support for diversified livelihoods—ecological conservation benefits—was unexplored in over 70% of studies. Of the minority of studies that did explore ecological outcomes, most reported that ecological conditions had not improved. These findings indicate conceptual ambiguity around livelihood diversification and a lack of empirical evidence supporting its theoretical underpinnings. There remain important questions about the impacts of diversification on multidimensional poverty and ecological conservation. Future research on and investment in diversification should be both more deliberate of what diversification means and more rigorous in the evaluation of its impacts.

Post-settlement demographics of reef building corals suggest prolonged recruitment bottlenecks - Lauranne Sarribouette; Nicole E. Pedersen; Clinton B. Edwards; Stuart A. Sandin (Oecologia, 2022)
For many organisms, early life stages experience significantly higher rates of mortality relative to adults. However, tracking early life stage individuals through time in natural settings is difficult, limiting our understanding of the duration of these ‘mortality bottlenecks’, and the time required for survivorship to match that of adults. Here, we track a cohort of juvenile corals (1–5 cm maximum diameter) from 12 taxa at a remote atoll in the Central Pacific from 2013 to 2017 and describe patterns of annual survivorship. Of the 537 juveniles initially detected, 219 (41%) were alive 4 years later, 163 (30%) died via complete loss of live tissue from the skeleton, and the remaining 155 (29%) died via dislodgement. The differing mortality patterns suggest that habitat characteristics, as well as species-specific features, may influence early life stage survival. Across most taxa, survival fit a logistic model, reaching > 90% annual survival within 4 years. These data suggest that mortality bottlenecks characteristic of ‘recruitment’ extend up to 5 years after individuals can be visually detected. Ultimately, replenishment of adult coral populations via sexual reproduction is needed to maintain both coral cover and genetic diversity. This study provides key insights into the dynamics and time scales that characterize these critical early life stages.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The North American Freshwater Migratory Fish Database ( NAFMFD ): Characterizing the migratory life histories of freshwater fishes of Canada, the United States and Mexico - Emily M. Dean; Arthur R. Cooper; Lizhu Wang; Wesley Daniel; Solomon David; Clayton Ernzen; Keith B. Gido; Edward Hale; Tim J. Haxton; William Kelso; Nancy Leonard; Chris Lido; et al. (Journal of Biogeography, 2022)
Aim Migratory freshwater fishes are those that must access discrete habitats to complete their life cycles. Freshwater fish migrations occur around the world and provide numerous ecosystem services for humans and natural systems; however, many migratory species are in decline globally. A limiting factor to successfully conserve freshwater migratory fishes is that the migratory life histories of many species are unknown or only partially described. To provide researchers with critical and comprehensive information to conserve migratory fishes, we developed the North American Freshwater Migratory Fish Database (NAFMFD). Location Canada, Mexico and the United States. Taxon Freshwater fish. Methods To develop this database, we assigned migratory status, pattern and behaviour to a comprehensive list of freshwater fish species found throughout North America. We assembled the database which included assignments (i.e. migratory status, pattern and behaviour) as well as the sources used to make the assignments. Researchers and managers from across North America reviewed the database for completeness and accuracy on the migratory life histories of fishes. Results The database synthesizes current knowledge of migratory status, pattern and behaviour of native and non‐native freshwater fishes throughout North America, including 1250 species representing 79 families and 325 genera. Results showcase the diversity of migratory life histories of freshwater fishes on the continent, including that at least 25% of North American freshwater fishes are migratory, 23% are non‐migratory and 44% have undetermined migratory status. Main conclusions NAFMFD improves the quality of migratory data accessible to researchers, which supports a more holistic understanding of the threats encountered by migratory fishes, including habitat fragmentation. The approach we used in developing NAFMFD can provide guidance for developing similar databases in other regions. Collectively, our work offers new insights into the range of freshwater fish migratory life histories, stimulating a need to better understand this diversity globally.

Wildfire, Smoke Exposure, Human Health, and Environmental Justice Need to be Integrated into Forest Restoration and Management - Savannah M. D’Evelyn; Jihoon Jung; Ernesto Alvarado; Jill Baumgartner; Pete Caligiuri; R. Keala Hagmann; Sarah B. Henderson; Paul F. Hessburg; Sean Hopkins; Edward J. Kasner; Meg A. Krawchuk; Jennifer E. Krenz; et al. (Current Environmental Health Reports, 2022)
Purpose of Review Increasing wildfire size and severity across the western United States has created an environmental and social crisis that must be approached from a transdisciplinary perspective. Climate change and more than a century of fire exclusion and wildfire suppression have led to contemporary wildfires with more severe environmental impacts and human smoke exposure. Wildfires increase smoke exposure for broad swaths of the US population, though outdoor workers and socially disadvantaged groups with limited adaptive capacity can be disproportionally exposed. Exposure to wildfire smoke is associated with a range of health impacts in children and adults, including exacerbation of existing respiratory diseases such as asthma and chronic obstructive pulmonary disease, worse birth outcomes, and cardiovascular events. Seasonally dry forests in Washington, Oregon, and California can benefit from ecological restoration as a way to adapt forests to climate change and reduce smoke impacts on affected communities. Recent Findings Each wildfire season, large smoke events, and their adverse impacts on human health receive considerable attention from both the public and policymakers. The severity of recent wildfire seasons has state and federal governments outlining budgets and prioritizing policies to combat the worsening crisis. This surging attention provides an opportunity to outline the actions needed now to advance research and practice on conservation, economic, environmental justice, and public health interests, as well as the trade-offs that must be considered. Summary Scientists, planners, foresters and fire managers, fire safety, air quality, and public health practitioners must collaboratively work together. This article is the result of a series of transdisciplinary conversations to find common ground and subsequently provide a holistic view of how forest and fire management intersect with human health through the impacts of smoke and articulate the need for an integrated approach to both planning and practice.

Transport Processes in the Gulf of Mexico Along the River-Estuary-Shelf-Ocean Continuum: a Review of Research from the Gulf of Mexico Research Initiative - Dubravko Justić; Villy Kourafalou; Giulio Mariotti; Songjie He; Robert Weisberg; Yannis Androulidakis; Christopher Barker; Annalisa Bracco; Brian Dzwonkowski; Chuanmin Hu; Haosheng Huang; Gregg Jacobs; et al. (Estuaries and Coasts, 2022)
Estuarine and coastal geomorphology, biogeochemistry, water quality, and coastal food webs in river-dominated shelves of the Gulf of Mexico (GoM) are modulated by transport processes associated with river inputs, winds, waves, tides, and deep-ocean/continental shelf interactions. For instance, transport processes control the fate of river-borne sediments, which in turn affect coastal land loss. Similarly, transport of freshwater, nutrients, and carbon control the dynamics of eutrophication, hypoxia, harmful algal blooms, and coastal acidification. Further, freshwater inflow transports pesticides, herbicides, heavy metals, and oil into receiving estuaries and coastal systems. Lastly, transport processes along the continuum from the rivers and estuaries to coastal and shelf areas and adjacent open ocean (abbreviated herein as “river-estuary-shelf-ocean”) regulate the movements of organisms, including the spatial distributions of individuals and the exchange of genetic information between distinct subpopulations. The Gulf of Mexico Research Initiative (GoMRI) provided unprecedented opportunities to study transport processes along the river-estuary-shelf-ocean continuum in the GoM. The understanding of transport at multiple spatial and temporal scales in this topographically and dynamically complex marginal sea was improved, allowing for more accurate forecasting of the fate of oil and other constituents. For this review, we focus on five specific transport themes: (i) wetland, estuary, and shelf exchanges; (ii) river-estuary coupling; (iii) nearshore and inlet processes; (iv) open ocean transport processes; and (v) river-induced fronts and cross-basin transport. We then discuss the relevancy of GoMRI findings on the transport processes for ecological connectivity and oil transport and fate. We also examine the implications of new findings for informing the response to future oil spills, and the management of coastal resources and ecosystems. Lastly, we summarize the research gaps identified in the many studies and offer recommendations for continuing the momentum of the research provided by the GoMRI effort. A number of uncertainties were identified that occurred in multiple settings. These include the quantification of sediment, carbon, dissolved gasses and nutrient fluxes during storms, consistent specification of the various external forcings used in analyses, methods for smooth integration of multiscale advection mechanisms across different flow regimes, dynamic coupling of the atmosphere with sub-mesoscale and mesoscale phenomena, and methods for simulating finer-scale dynamics over long time periods. Addressing these uncertainties would allow the scientific community to be better prepared to predict the fate of hydrocarbons and their impacts to the coastal ocean, rivers, and marshes in the event of another spill in the GoM.

Use of a 360-Degree Underwater Camera to Characterize Artificial Reef and Fish Aggregating Effects around Marine Energy Devices - Lenaïg G. Hemery; Kailan F. Mackereth; Cailene M. Gunn; Edward B. Pablo (Journal of Marine Science and Engineering, 2022)
Marine energy devices must be attached to the seafloor by their foundations, pilings, or anchors, and will have other parts in the water column like the devices themselves, mooring lines, and power export cables running along the seafloor. The installation and presence of these artificial structures will create physical changes that can disrupt or create new habitats, and potentially alter the behavior of mobile organisms such as fish around a device by attracting them to these new artificial reefs and fish aggregating devices. In this study, we tested a new approach for monitoring fish activity around a marine energy device anchor: a 360-degree underwater camera to keep the target (a wave energy converter’s anchor) in the field of view of the camera. The camera was deployed in three configurations (hand-held, tripod, video lander) at sites with different hydrodynamics and underwater visibilities. The video lander was the best configuration: very stable, versatile, and easy to handle. The 360-degree field of view enabled observing and counting fishes, which were more abundant at dusk than dawn or noon, around the anchor. Despite remaining challenges, 360-degree cameras are useful tools for monitoring animal interactions with marine energy devices.

Using structured decision making to guide habitat restoration for butterflies: a case study of Oregon silverspots - Cassandra F. Doll; Sarah J. Converse; Collin B. Edwards; Cheryl B. Schultz (Journal of Insect Conservation, 2022)

Resolving taxonomic confusion: establishing the genus Phytobacter on the list of clinically relevant Enterobacteriaceae - Theo H. M. Smits; Lavinia N. V. S. Arend; Sofia Cardew; Erika Tång-Hallbäck; Marcelo T. Mira; Edward R. B. Moore; Jorge L. M. Sampaio; Fabio Rezzonico; Marcelo Pillonetto (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Although many clinically significant strains belonging to the family Enterobacteriaceae fall into a restricted number of genera and species, there is still a substantial number of isolates that elude this classification and for which proper identification remains challenging. With the current improvements in the field of genomics, it is not only possible to generate high-quality data to accurately identify individual nosocomial isolates at the species level and understand their pathogenic potential but also to analyse retrospectively the genome sequence databases to identify past recurrences of a specific organism, particularly those originally published under an incorrect or outdated taxonomy. We propose a general use of this approach to classify further clinically relevant taxa, i.e., Phytobacter spp., that have so far gone unrecognised due to unsatisfactory identification procedures in clinical diagnostics. Here, we present a genomics and literature-based approach to establish the importance of the genus Phytobacter as a clinically relevant member of the Enterobacteriaceae family.

Pasteurella species bloodstream infections in Queensland, Australia, 2000–2019 - Kevin B. Laupland; Adam G. Stewart; Felicity Edwards; Patrick Harris; Claire Heney; Narelle George; Sonali Coulter; David L. Paterson (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Pasteurella species are infrequent but potentially severe causes of bloodstream infection (BSI). The objective of this study was to determine the incidence, risk factors, and outcomes of Pasteurella species BSI in a large Australian population. Retrospective, laboratory-based surveillance was conducted in Queensland, Australia (population ≈ 5 million) during 2000–2019, and clinical and outcome information was established by linkage to state hospital admissions and vital statistics databases. During more than 86 million person-years of surveillance, 272 incident Pasteurella species BSI occurred for an overall age- and sex-standardized annual incidence of 3.3 per million residents. The incidence of Pasteurella species BSI was highest in recent years and older individuals were at greatest risk. The median (interquartile range) Charlson Comorbidity Index was 2 (0–4) with scores of zero, 1, 2, and 3 + observed in 81 (30%), 37 (14%), 44 (16%), and 110 (40%) of cases. The 30-day all-cause case fatality was 9% (24/272) and patients who died had more comorbidities and were less likely to have community-associated disease. Although Pasteurella species are infrequent causes of BSI, older individuals and those with comorbidities are at highest risk. The burden of this disease may be expected to increase with an aging and more comorbid population.

Using groundwater noble gas measurements to confirm paleorecharge hypotheses at Pahute Mesa, Nevada National Security Site, Nevada, USA - Ate Visser; Edward Kwicklis; Irene Farnham; Andrew F. B. Tompson; Ronald L. Hershey (Hydrogeology Journal, 2022)

Expanding the horizon of research into the pathogenesis of the white matter diseases: Proceedings of the 2021 Annual Workshop of the Albert Research Institute for White Matter and Cognition - Shawn N. Whitehead; Askiel Bruno; Jeffrey M. Burns; S. Thomas Carmichael; Anna Csiszar; Jodi D. Edwards; Fanny M. Elahi; Giuseppe Faraco; Douglas B. Gould; Deborah R. Gustafson; Vladimir Hachinski; Gary Rosenberg; et al. (GeroScience, 2022)

Alcohol intake and risk of pituitary adenoma - David J. Cote; Timothy R. Smith; Ursula B. Kaiser; Edward R. Laws; Meir J. Stampfer (Cancer Causes & Control, 2022)

Sea-Level Rise: From Global Perspectives to Local Services - Gaël Durand; Michiel R. van den Broeke; Goneri Le Cozannet; Tamsin L. Edwards; Paul R. Holland; Nicolas C. Jourdain; Ben Marzeion; Ruth Mottram; Robert J. Nicholls; Frank Pattyn; Frank Paul; Aimée B. A. Slangen; et al. (Frontiers in Marine Science, 2022)
Coastal areas are highly diverse, ecologically rich, regions of key socio-economic activity, and are particularly sensitive to sea-level change. Over most of the 20th century, global mean sea level has risen mainly due to warming and subsequent expansion of the upper ocean layers as well as the melting of glaciers and ice caps. Over the last three decades, increased mass loss of the Greenland and Antarctic ice sheets has also started to contribute significantly to contemporary sea-level rise. The future mass loss of the two ice sheets, which combined represent a sea-level rise potential of ∼65 m, constitutes the main source of uncertainty in long-term (centennial to millennial) sea-level rise projections. Improved knowledge of the magnitude and rate of future sea-level change is therefore of utmost importance. Moreover, sea level does not change uniformly across the globe and can differ greatly at both regional and local scales. The most appropriate and feasible sea level mitigation and adaptation measures in coastal regions strongly depend on local land use and associated risk aversion. Here, we advocate that addressing the problem of future sea-level rise and its impacts requires (i) bringing together a transdisciplinary scientific community, from climate and cryospheric scientists to coastal impact specialists, and (ii) interacting closely and iteratively with users and local stakeholders to co-design and co-build coastal climate services, including addressing the high-end risks.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Mesozooplankton Community Dynamics and Grazing Potential Across Algal Bloom Cycles in a Subtropical Estuary - L. Holly Sweat; Hunter Alexander; Edward J. Phlips; Kevin B. Johnson (Frontiers in Marine Science, 2021)
Mesozooplankton, as abundant grazers of microalgae in coastal systems, have the potential to prevent or mitigate harmful algal blooms (HABs) and their effects. The Indian River Lagoon (IRL) is a subtropical estuary in eastern Florida (United States) where repeated blooms, dominated by the toxic dinoflagellate Pyrodinium bahamense , the brown tide species Aureoumbra lagunensis , pico/nano planktonic cyanobacteria and other nano-eukaryotes, have highlighted the need to better understand fluctuations in the grazing potential of mesozooplankton populations across bloom cycles. Mesozooplankton and abiotic environmental data were collected at five sites in the northern IRL system at 6-week intervals from November 2013 through June 2016. A total of 107 taxa from 14 phyla were detected. Communities varied across sites, dates and between bloom and non-bloom periods, with densities up to 338 individuals L –1 . Eight taxa comprising 85–94% of the total population at each site were identified as primary potential grazers, including barnacle nauplii, cladocerans, adult copepods, gastropod veligers, larvaceans, and polychaete metatrochophores. Although abundant, the estimated grazing potential of the primary taxa, calculated from their measured densities and previously published grazing rates, suggest that mesozooplankton lack the capacity to suppress phytoplankton once they reach bloom levels. These findings illustrate the utility of monitoring data and underscore the importance of systematically evaluating algal bloom controls with a consideration for the dynamic conditions of each unique ecosystem.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Bacterial Viruses Subcommittee and Archaeal Viruses Subcommittee of the ICTV: update of taxonomy changes in 2021 - Mart Krupovic; Dann Turner; Vera Morozova; Mike Dyall-Smith; Hanna M. Oksanen; Rob Edwards; Bas E. Dutilh; Susan M. Lehman; Alejandro Reyes; Diana P. Baquero; Matthew B. Sullivan; Jumpei Uchiyama; et al. (Archives of Virology, 2021)
In this article, we – the Bacterial Viruses Subcommittee and the Archaeal Viruses Subcommittee of the International Committee on Taxonomy of Viruses (ICTV) – summarise the results of our activities for the period March 2020 – March 2021. We report the division of the former Bacterial and Archaeal Viruses Subcommittee in two separate Subcommittees, welcome new members, a new Subcommittee Chair and Vice Chair, and give an overview of the new taxa that were proposed in 2020, approved by the Executive Committee and ratified by vote in 2021. In particular, a new realm, three orders, 15 families, 31 subfamilies, 734 genera and 1845 species were newly created or redefined (moved/promoted).

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

High Genetic Addiction Risk Score (GARS) in Chronically Prescribed Severe Chronic Opioid Probands Attending Multi-pain Clinics: an Open Clinical Pilot Trial - Mark Moran; Kenneth Blum; Jessica Valdez Ponce; Lisa Lott; Marjorie C. Gondré–Lewis; Sampada Badgaiyan; Raymond Brewer; B. William Downs; Philip Fynman; Alexander Weingarten; Jean Lud Cadet; David E. Smith; et al. (Molecular Neurobiology, 2021)
Millions of Americans experience pain daily. In 2017, opioid overdose claimed 64,000 lives increasing to 84,000 lives in 2020, resulting in a decrease in national life expectancy. Chronic opioid use results in dependency, drug tolerance, neuroadaptation, hyperalgesia, potential addictive behaviors, or Reward Deficiency Syndrome (RDS) caused by a hypodopaminergia. Evaluation of pain clinic patients with the Genetic Addiction Risk Score (GARS) test and the Addiction Severity Index (ASI- Media Version V) revealed that GARS scores equal to or greater than 4 and 7 alleles significantly predicted drug and alcohol severity, respectively. We utilized RT-PCR for SNP genotyping and multiplex PCR/capillary electrophoresis for fragment analysis of the role of eleven alleles in a ten-reward gene panel, reflecting the activity of brain reward circuitry in 121 chronic opioid users. The study consisted of 55 males and 66 females averaging ages 54 and 53 years of age, respectively. The patients included Caucasians, African Americans, Hispanics, and Asians. Inclusion criteria mandated that the Morphine Milligram Equivalent (MME) was 30–600 mg/day (males) and 20 to 180 mg/day (females) for treatment of chronic pain over 12 months. Ninety-six percent carried four or more risk alleles, and 73% carried seven or more risk alleles, suggesting a high predictive risk for opioid and alcohol dependence, respectively. These data indicate that chronic, legally prescribed opioid users attending a pain clinic possess high genetic risk for drug and alcohol addiction. Early identification of genetic risk, using the GARS test upon entry to treatment, may prevent iatrogenic induced opioid dependence.

Are visual working memory and episodic memory distinct processes? Insight from stroke patients by lesion-symptom mapping - Selma Lugtmeijer; Linda Geerligs; Frank Erik de Leeuw; Edward H. F. de Haan; Roy P. C. Kessels; Anouk R. Smits; Ben A. Schmand; Edward H. F. de Haan; Frank Erik de Leeuw; Gert jan Luijckx; H. Steven Scholte; Joke M. Spikman; et al. (Brain Structure and Function, 2021)
Working memory and episodic memory are two different processes, although the nature of their interrelationship is debated. As these processes are predominantly studied in isolation, it is unclear whether they crucially rely on different neural substrates. To obtain more insight in this, 81 adults with sub-acute ischemic stroke and 29 elderly controls were assessed on a visual working memory task, followed by a surprise subsequent memory test for the same stimuli. Multivariate, atlas- and track-based lesion-symptom mapping (LSM) analyses were performed to identify anatomical correlates of visual memory. Behavioral results gave moderate evidence for independence between discriminability in working memory and subsequent memory, and strong evidence for a correlation in response bias on the two tasks in stroke patients. LSM analyses suggested there might be independent regions associated with working memory and episodic memory. Lesions in the right arcuate fasciculus were more strongly associated with discriminability in working memory than in subsequent memory, while lesions in the frontal operculum in the right hemisphere were more strongly associated with criterion setting in subsequent memory. These findings support the view that some processes involved in working memory and episodic memory rely on separate mechanisms, while acknowledging that there might also be shared processes.

Alleviation of nutrient co‐limitation induces regime shifts in post‐fire community composition and productivity in Arctic tundra - Ian Klupar; Adrian V. Rocha; Edward B. Rastetter (Global Change Biology, 2021)
Recent unprecedented fires in the Arctic during the past two decades have indicated a pressing need to understand the long‐term ecological impacts of fire in this biome. Anecdotal evidence suggests that tundra fires can induce regime shifts that change tussock tundra to more shrub‐dominated ecosystems. However, the ecological mechanisms regulating these shifts are poorly understood, but are hypothesized to involve changes to nutrient availability in this nutrient limited system. Here we conducted a 4‐year two‐factorial (control: C, nitrogen along: N + , phosphorus alone: P + , nitrogen and phosphorus combined: NP + ) fertilization experiment in both unburned and burned tundra to test this hypothesis after a decade of post‐fire recovery. A decade after fire, the burned site exhibited an increase in soil nitrogen and phosphorus availability and a transition toward taller, more productive, and more deciduous vegetation. This shift in vegetation structure, composition, and function was induced at the unburned site through the addition of both NP + and the alleviation of their co‐limitation. Both burned and unburned tundra responded similarly to fertilizer treatments by increasing leaf area index, greenness, and canopy height in NP + treatments, and exhibited no significant response in individual N + or P + treatments. These results point to a greater need to understand coupled carbon, nitrogen, and phosphorus cycles in this system, and suggest that post‐fire regime shifts are regulated by the alleviation of nitrogen and phosphorus co‐limitation in Arctic tundra.

Changes in phenology and abundance of an at-risk butterfly - Rachael E. Bonoan; Elizabeth E. Crone; Collin B. Edwards; Cheryl B. Schultz (Journal of Insect Conservation, 2021)

Effects of Holocene climate change, volcanism and mass migration on the ecosystem of a small, dry island (Brava, Cabo Verde) - Alvaro Castilla‐Beltrán; Lea de Nascimento; José María Fernández‐Palacios; Robert J. Whittaker; Maria M. Romeiras; Andrew B. Cundy; Mary Edwards; Sandra Nogué (Journal of Biogeography, 2021)
Aim Palaeoecological data provide an essential long‐term perspective of ecological change and its drivers in oceanic islands. However, analysing the effects of multi‐scalar and potentially co‐occurring disturbances is particularly challenging in dry islands. Here, we aim to identify the ecological consequences of the integrated impacts of a regional drying trend, volcanic eruptions and human mass migrations in a spatially constrained environment—a small, dry oceanic island in Macaronesia. Location Brava Island, Republic of Cabo Verde. Taxa Terrestrial vegetation and fungi. Methods We use palaeoecological analyses applied to a caldera soil profile that dates back to 9700 cal yr BP (calibrated years before the present). Analyses include pollen (vegetation history), non‐pollen palynomorphs (changes in fern and fungal communities), grain‐size distribution, loss‐on‐ignition and geochemistry (sedimentology and erosion regimes), microscopic tephra shards (volcanic ash deposition) and charcoal (fire regime). Results A regional drying trend after c. 4000 cal yr BP caused increased erosion but had limited immediate impacts on highland grassland vegetation. The expansion of fern‐rich woody scrubland was contemporaneous with significant deposition of volcanic ash and erosion between 1800 and 650 cal yr BP. About 300 cal yr BP, exogenous plants expanded, grazing and fires increased, and there was a decrease of native vegetation cover. Main conclusions Throughout the Holocene, highland vegetation in Brava was characterized by the presence of open landscapes dominated by herbaceous species (e.g. Poaceae, Forsskaolea ), with some presence of woody native taxa (e.g. Ficus , Dodonaea ). A regional drying trend was a driver of erosion since the Mid Holocene but did not have an immediate influence on highland vegetation. Tephra deposition is a possible driver of vegetation change. Inter‐island mass migration after volcanic events in Fogo Island c. 1680 CE potentially triggered land use change and intensification, causing a reduction of native vegetation in Brava.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Differences in microbial community response to nitrogen fertilization result in unique enzyme shifts between arbuscular and ectomycorrhizal‐dominated soils - Joseph E. Carrara; Christopher A. Walter; Zachary B. Freedman; Ashley N. Hostetler; Jennifer S. Hawkins; Ivan J. Fernandez; Edward R. Brzostek (Global Change Biology, 2021)
While the effect of nitrogen (N) deposition on belowground carbon (C) cycling varies, emerging evidence shows that forest soils dominated by trees that associate with ectomycorrhizal fungi (ECM) store more C than soils dominated by trees that associate with arbuscular mycorrhizae (AM) with increasing N deposition. We hypothesized that this is due to unique nutrient cycling responses to N between AM and ECM‐dominated soils. ECM trees primarily obtain N through fungal mining of soil organic matter subsidized by root‐C. As such, we expected the largest N‐induced responses of C and N cycling to occur in ECM rhizospheres and be driven by fungi. Conversely, as AM trees rely on bacterial scavengers in bulk soils to cycle N, we predicted the largest AM responses to be driven by shifts in bacteria and occur in bulk soils. To test this hypothesis, we measured microbial community composition, metatranscriptome profiles, and extracellular enzyme activity in bulk, rhizosphere, and organic horizon (OH) soils in AM and ECM‐dominated soils at Bear Brook Watershed in Maine, USA. After 27 years of N fertilization, fungal community composition shifted across ECM soils, but bacterial communities shifted across AM soils. These shifts were mirrored by enhanced C relative to N mining enzyme activities in both mycorrhizal types, but this occurred in different soil fractions. In ECM stands these shifts occurred in rhizosphere soils, but in AM stands they occurred in bulk soils. Additionally, ECM OH soils exhibited the opposite response with declines in C relative to N mining. As rhizosphere soils account for only a small portion of total soil volume relative to bulk soils, coupled with declines in C to N enzyme activity in ECM OH soils, we posit that this may partly explain why ECM soils store more C than AM soils as N inputs increase.

Ecosystem Recovery from Disturbance is Constrained by N Cycle Openness, Vegetation-Soil N Distribution, Form of N Losses, and the Balance Between Vegetation and Soil-Microbial Processes - Edward B. Rastetter; George W. Kling; Gaius R. Shaver; Byron C. Crump; Laura Gough; Kevin L. Griffin (Ecosystems, 2021)

Root‐derived inputs are major contributors to soil carbon in temperate forests, but vary by mycorrhizal type - Adrienne B. Keller; Edward R. Brzostek; Matthew E. Craig; Joshua B. Fisher; Richard P. Phillips (Ecology Letters, 2021)
Roots promote the formation of slow‐cycling soil carbon (C), yet we have a limited understanding of the magnitude and controls on this flux. We hypothesised arbuscular mycorrhizal (AM)‐ and ectomycorrhizal (ECM)‐associated trees would exhibit differences in root‐derived C accumulation in the soil, and that much of this C would be transferred into mineral‐associated pools. We installed δ 13 C‐enriched ingrowth cores across mycorrhizal gradients in six Eastern U.S. forests ( n = 54 plots). Overall, root‐derived C was 54% greater in AM versus ECM‐dominated plots. This resulted in nearly twice as much root‐derived C in putatively slow‐cycling mineral‐associated pools in AM compared to ECM plots. Given that our estimates of root‐derived inputs were often equal to or greater than leaf litter inputs, our results suggest that variation in root‐derived soil C accumulation due to tree mycorrhizal dominance may be a key control of soil C dynamics in forests.

Factors influencing spatial patterns in primary productivity in Kenyan territorial waters - Joseph Kamau; Noah Ngisiange; Oliver Ochola; James Kilionzi; Amon Kimeli; Shigalla B. Mahongo; Harrison Onganda; Charles Mitto; Boaz Ohowa; Charles Magori; Edward Kimani; Melckzedeck Osore (Western Indian Ocean Journal of Marine Science, 2021)
This study was formulated to investigate productivity systems within Kenyan territorial waters. The interaction of processes on the margins of the marine waters, particularly the influx of fresh water loaded with sediments and nutrients, influences productivity of coastal waters. These deposited sediments, rich in nutrients, create a topographic barrier to the northerly flowing East African Coastal Current (EACC). Phosphate and nitrate peaks observed around the North Kenya Bank area provide evidence of an upwelling event. The contribution of sediments from the Lamu archipelago mangrove system is evident from the high observed particulate organic carbon (POC) input around the area. The system around the Lamu archipelago did not however show high chlorophyll-a levels despite the high POC influx. This may be due to the low levels of limiting phosphate in the surrounding waters, contrary to the observation further north in the region where high chlorophyll-a levels and corresponding higher phosphate levels were apparent. Productivity was largely supported by upwelling and organic matter mineralization. High levels of chlorophyll corresponded to high pelagic fish densities in the south (around 4.5°S) and north of the study area (around 2.5°S).

Livelihood impacts and adaptation in fishing practices as a response to recent climatic changes in the upwelling region of the East African Coastal Current - Jacob Ochiewo; Fridah Munyi; Edward Waiyaki; Faith Kimanga; Nicholas Karani; Joseph Kamau; Shigalla B. Mahongo (Western Indian Ocean Journal of Marine Science, 2021)
A socio-economic assessment was carried out at Amu and Shela in Lamu County and Ngomeni in Kilifi County on the coast of Kenya. The aim was to establish fisher perspectives on the livelihood impacts of changes in upwelling associated with the East African Coastal Current, and adaptations in fishing practices to determine the vulnerability, resilience and adaptation options for fisheries dependent communities in this upwelling region. Primary data and information were collected through direct observation, semi-structured interviews, key informant interviews and oral histories. Descriptive and non-parametric analysis was conducted for quantitative data and content analysis for qualitative data. The study covered 92 respondents out of which 90 were male. About 82.5 percent of the respondents had attained different levels of primary school education and below, and were therefore highly vulnerable to climate change impacts. Furthermore, 80.4 percent of the respondents were aged between 20 years and 49 years with a mean age of 40 years, thus falling into the economically active age category. In terms of livelihoods, fishing and fishing-related activities formed the primary livelihoods at the three study sites with fishing being the main occupation for 93 percent of the respondents. Fishing effort was higher during the north-east monsoon season. Fifty two percent of the respondents targeted small pelagic species. The main changes observed included increased fishing effort and a decline in the quantity of fish caught per fisher, and changes in the composition of fish species. Changes in the composition of fish species have further been compounded by a decline in rainfall over time, sea level rise, irregular wind patterns and increased temperatures. The decline in fish catch further led to a general decline in income and welfare. The climatic changes increased vulnerability of the fishing communities.

Calc-alkaline volcanic rocks and zircon ages of the late Tonian: early Cryogenian arc-related Big Naryn Complex in the Eastern Djetim-Too Range, Middle Tianshan block, Kyrgyzstan - Baiansuluu Terbishalieva; Martin Jan Timmerman; Alexander Mikolaichuk; Uwe Altenberger; Jiří Sláma; Anja Maria Schleicher; Masafumi Sudo; Edward R. Sobel; Sarah B. Cichy (International Journal of Earth Sciences, 2021)
The Big Naryn Complex (BNC) in the East Djetim-Too Range of the Kyrgyz Middle Tianshan block is a tectonized, at least 2 km thick sequence of predominantly felsic to intermediate volcanic rocks intruded by porphyric rhyolite sills. It overlies a basement of metamorphic rocks and is overlain by late Neoproterozoic Djetim-Too Formation sediments; these also occur as tectonic intercalations in the BNC. The up to ca. 1100 m thick Lower Member is composed of predominantly rhyolites-to-dacites and minor basalts, while the at least 900 m thick pyroclastic Upper Member is dominated by rhyolitic-to-dacitic ignimbrites. Porphyric rhyolite sills are concentrated at the top of the Lower Member. A Lower Member rhyolite and a sill sample have LA-ICP-MS U–Pb zircon crystallization ages of 726.1 ± 2.2 Ma and 720.3 ± 6.5 Ma, respectively, showing that most of the magmatism occurred within a short time span in the late Tonian–early Cryogenian. Inherited zircons in the sill sample have Neoarchean (2.63, 2.64 Ga), Paleo- (2.33–1.81 Ga), Meso- (1.55 Ga), and Neoproterozoic (ca. 815 Ma) ages, and were derived from a heterogeneous Kuilyu Complex basement. A 1751 ± 7 Ma 40 Ar/ 39 Ar age for amphibole from metagabbro is the age of cooling subsequent to Paleoproterozoic metamorphism of the Kuilyu Complex. The large amount of pyroclastic rocks, and their major and trace element compositions, the presence of Neoarchean to Neoproterozoic inherited zircons and a depositional basement of metamorphic rocks point to formation of the BNC in a continental magmatic arc setting.

Multi-stressor Effects of Ultraviolet Light, Temperature, and Salinity on Louisiana Sweet Crude Oil Toxicity in Larval Estuarine Organisms - Marie E. DeLorenzo; Peter B. Key; Katy W. Chung; Kaitlin Aaby; Deanna Hausman; Cheldina Jean; Paul L. Pennington; Emily C. Pisarski; Edward F. Wirth (Archives of Environmental Contamination and Toxicology, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Spatial and Temporal Influences of Nearshore Hydrography on Fish Assemblages Associated with Energy Platforms in the Northern Gulf of Mexico - Ryan T. Munnelly; David B. Reeves; Edward J. Chesney; Donald M. Baltz (Estuaries and Coasts, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

MYCO WELL D-ONE detection of Ureaplasma spp. and Mycoplasma hominis in sexual health patients in Wales - Daniel J. Morris; Lucy C. Jones; Rebecca L. Davies; Kirsty Sands; Edward Portal; Owen B. Spiller (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
The genital mycoplasmas are a unique group of inherently antibiotic-resistant sexually transmitted bacteria, often associated with non-gonococcal urethritis and bacterial vaginosis. The MYCO WELL D-ONE is a culture-based assay that aims to detect these organisms whilst concurrently screening them for antibiotic resistance. Urine and/or swabs from 856 informed and consented participants attending Welsh sexual health clinics were subjected to MYCO WELL D-ONE analysis, alongside qPCR and culture titration methodologies to determine sensitivity, specificity, PPV, NPV and accuracy. Resistance was confirmed by CLSI-compliant susceptibility testing and genetic mechanisms determined. The MYCO WELL D-ONE displayed a sensitivity and specificity of 91.98% and 96.44% for the detection of Ureaplasma spp., with sensitivity and specificity values of 78.23% and 98.84% for Mycoplasma hominis , compared with qPCR. Swabs harboured significantly greater bacterial loads than urine samples for both Ureaplasma spp. and M . hominis . Levofloxacin resistance rates, mediated by Ser83Leu mutation in ParC, for Ureaplasma spp. were 0.54%. Tetracycline resistance rates, mediated by tet (M), were 0.54% and 2% for Ureaplasma spp. and M . hominis , respectively; sequence analysis of tet (M)-positive Ureaplasma spp. and M . hominis strains isolated from a single individual confirmed separate resistance gene origins. The MYCO WELL D-ONE is a sensitive and specific assay for the detection of Ureaplasma spp. and M . hominis in genitourinary medicine samples, facilitating the accurate detection of these organisms within low-technology environments. While good for antibiotic resistance screening, accurate confirmation by MIC determination or molecular methods are required, and more optimally performed on urine samples.

A Bornean peat swamp forest is a net source of carbon dioxide to the atmosphere - Angela C. I. Tang; Lulie Melling; Paul C. Stoy; Kevin K. Musin; Edward B. Aeries; Joseph W. Waili; Mariko Shimizu; Benjamin Poulter; Ryuichi Hirata (Global Change Biology, 2020)
Tropical peat forests are a globally important reservoir of carbon, but little is known about CO 2 exchange on an annual basis. We measured CO 2 exchange between the atmosphere and tropical peat swamp forest in Sarawak, Malaysia using the eddy covariance technique over 4 years from 2011 to 2014. The CO 2 fluxes varied between seasons and years. A small carbon uptake took place during the rainy season at the beginning of 2011, while a substantial net efflux of >600 g C/m 2 occurred over a 2 month period in the middle of the dry season. Conversely, the peat ecosystem was a source of carbon during both the dry and rainy seasons in subsequent years and more carbon was lost during the rainy season relative to the dry season. Our results demonstrate that the forest was a net source of CO 2 to the atmosphere during every year of measurement with annual efflux ranging from 183 to 632 g C m −2 year −1 , noting that annual flux values were sensitive to gap filling methodology. This is in contrast to the typical view of tropical peat forests which must have acted as net C sinks over time scales of centuries to millennia to create the peat deposits. Path analyses revealed that the gross primary productivity (GPP) and ecosystem respiration (RE) were primarily affected by vapour pressure deficit (VPD). Results suggest that future increases in VPD could further reduce the C sink strength and result in additional net CO 2 losses from this tropical peat swamp forest in the absence of plant acclimation to such changes in atmospheric dryness.

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Evidence for craniofacial enhancer variation underlying nonsyndromic cleft lip and palate - Vershanna E. Morris; S. Shahrukh Hashmi; Lisha Zhu; Lorena Maili; Christian Urbina; Steven Blackwell; Matthew R. Greives; Edward P. Buchanan; John B. Mulliken; Susan H. Blanton; W. Jim Zheng; Jacqueline T. Hecht; et al. (Human Genetics, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Governance of alluvial aquifers and community participation: a social-ecological systems analysis of the Brazilian semi-arid region - Bárbara B. Tsuyuguchi; Edward A. Morgan; Janiro C. Rêgo; Carlos de Oliveira Galvão (Hydrogeology Journal, 2020)

Quantifying life history demographics of the scleractinian coral genus Pocillopora at Palmyra Atoll - Sho M. Kodera; Clinton B. Edwards; Vid Petrovic; Nicole E. Pedersen; Yoan Eynaud; Stuart A. Sandin (Coral Reefs, 2020)

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

Nutritional factors modulating plant and fruit susceptibility to pathogens: BARD workshop, Haifa, Israel, February 25–26, 2018 - Dov Prusky; Leandro José de Assis; Riccardo Baroncelli; Ernesto P. Benito; Virginia Casado del Castillo; Timothy Chaya; Shay Covo; José María Díaz-Mínguez; Nicole M. Donofrio; Eduardo Espeso; Tânia Ribeiro Fernandes; Gustavo H. Goldman; et al. (Phytoparasitica, 2020)

Calcite precipitation in Lake Powell reduces alkalinity and total salt loading to the Lower Colorado River Basin - Bridget R. Deemer; Edward G. Stets; Charles B. Yackulic (Limnology and Oceanography, 2020)
Reservoirs can retain and transform carbon, nitrogen, phosphorus, and silica, but less is known about their effects on other biogeochemically relevant solutes. The salinization of freshwater ecosystems is a growing concern in many regions, and the role of reservoirs in salinity transport is an important research frontier. Here, we examine how a large desert southwest reservoir, Lake Powell, has altered the downstream transport of total dissolved solids (TDSs) as well as the dominant cations and anions comprising the TDS pool ( , , and Ca 2+ ). Average downstream TDS concentrations have declined significantly since river impoundment and seasonal fluctuations in TDS concentrations have become more modulated, but year to year variation in TDS concentrations has remained similar. While some of the reductions in TDS concentration can be attributed to watershed management, we find that Lake Powell retains about 10% of the TDS loaded to the system (1991 Mg TDS d −1 ). Much of this retention is occurring in the forms of calcium and bicarbonate, likely via calcite precipitation, and is equivalent to an average burial of 522 mg C m −2 d −1 , thus reducing the alkalinity of downstream water. Flow‐weighted modeling suggests that, in the absence of Lake Powell, downstream salinity limits would be surpassed at the outflow to Lake Powell 41% of the time (vs. 0% of the time currently). Understanding the dominant mechanisms regulating solute transport through the reservoir is important given the relevance for downstream drinking water and irrigation concerns, biogeochemical cycling, and the high potential for reduced flows in the future.

Impairments in Emotion Recognition and Risk-Taking Behavior After Isolated, Cerebellar Stroke - Nils S. van den Berg; Rients B. Huitema; Jacoba M. Spikman; Gert-Jan Luijckx; Edward H. F. de Haan (The Cerebellum, 2020)
An increasing amount of research has shown a cerebellar involvement in higher order cognitive functions, including emotional processing and decision-making. However, it has not been investigated whether impairments in facial emotion recognition, which could be a marker of impaired emotional experiences, are related to risky decision-making in these patients. Therefore, we aimed to investigate facial emotion recognition and risky decision-making in these patients as well as to investigate a relationship between these constructs. Thirteen patients with a discrete, isolated, cerebellar lesion as a consequence of a stroke were included in the study. Emotion recognition was assessed with the Facial Expressions of Emotions—Stimuli and Test (FEEST). Risk-taking behavior was assessed with the Action Selection Test (AST). Furthermore, 106 matched healthy controls performed the FEEST and 20 matched healthy controls performed the AST. Compared with healthy controls, patients were significantly worse in the recognition of emotional expressions and they took significantly more risks. In addition, a worse ability to recognize fearful facial expressions was strongly related to an increase in risky decisions in the AST. Therefore, we suggest that tests of emotion recognition should be incorporated into the neuropsychological assessment after cerebellar stroke to boost detection and treatment of these impairments in these patients.

Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.

High dietary sodium augments vascular tone and attenuates low-flow mediated constriction in salt-resistant adults - Ninette Shenouda; Meghan G. Ramick; Shannon L. Lennon; William B. Farquhar; David G. Edwards (European Journal of Applied Physiology, 2020)

7700-year persistence of an isolated, free-living coral assemblage in the Galápagos Islands: a model for coral refugia? - J. S. Feingold; B. Riegl; K. Hendrickson; L. T. Toth; H. Cheng; R. L. Edwards; R. B. Aronson (Coral Reefs, 2020)

The importance of naturally attenuated SARS‐CoV ‐2 in the fight against COVID ‐19 - Jean Armengaud; Agnès Delaunay‐Moisan; Jean‐Yves Thuret; Eelco van Anken; Diego Acosta‐Alvear; Tomás Aragón; Carolina Arias; Marc Blondel; Ineke Braakman; Jean‐François Collet; René Courcol; Antoine Danchin; et al. (Environmental Microbiology, 2020)
The current SARS‐CoV‐2 pandemic is wreaking havoc throughout the world and has rapidly become a global health emergency. A central question concerning COVID‐19 is why some individuals become sick and others not. Many have pointed already at variation in risk factors between individuals. However, the variable outcome of SARS‐CoV‐2 infections may, at least in part, be due also to differences between the viral subspecies with which individuals are infected. A more pertinent question is how we are to overcome the current pandemic. A vaccine against SARS‐CoV‐2 would offer significant relief, although vaccine developers have warned that design, testing and production of vaccines may take a year if not longer. Vaccines are based on a handful of different designs (i), but the earliest vaccines were based on the live, attenuated virus. As has been the case for other viruses during earlier pandemics, SARS‐CoV‐2 will mutate and may naturally attenuate over time (ii). What makes the current pandemic unique is that, thanks to state‐of‐the‐art nucleic acid sequencing technologies, we can follow in detail how SARS‐CoV‐2 evolves while it spreads. We argue that knowledge of naturally emerging attenuated SARS‐CoV‐2 variants across the globe should be of key interest in our fight against the pandemic.

Taxonomy of prokaryotic viruses: 2018-2019 update from the ICTV Bacterial and Archaeal Viruses Subcommittee - Evelien M. Adriaenssens; Matthew B. Sullivan; Petar Knezevic; Leonardo J. van Zyl; B. L. Sarkar; Bas E. Dutilh; Poliane Alfenas-Zerbini; Małgorzata Łobocka; Yigang Tong; James Rodney Brister; Andrea I. Moreno Switt; Jochen Klumpp; et al. (Archives of Virology, 2020)

Disturbance legacies increase and synchronize nutrient concentrations and bacterial productivity in coastal ecosystems - John S. Kominoski; Evelyn E. Gaiser; Edward Castañeda‐Moya; Stephen E. Davis; Shimelis B. Dessu; Paul Julian; Dong Yoon Lee; Luca Marazzi; Victor H. Rivera‐Monroy; Andres Sola; Ulrich Stingl; Sandro Stumpf; et al. (Ecology, 2020)
Long‐term ecological research can resolve effects of disturbance on ecosystem dynamics by capturing the scale of disturbance and interactions with environmental changes. To quantify how disturbances interact with long‐term directional changes (sea‐level rise, freshwater restoration), we studied 17 yr of monthly dissolved organic carbon (DOC), total nitrogen (TN), and phosphorus (TP) concentrations and bacterioplankton productivity across freshwater‐to‐marine estuary gradients exposed to multiple disturbance events (e.g., droughts, fire, hurricanes, and low‐temperature anomalies) and long‐term increases in water levels. By studying two neighboring drainages that differ in hydrologic connectivity, we additionally tested how disturbance legacies are shaped by hydrologic connectivity. We predicted that disturbance events would interact with long‐term increases in water levels in freshwater and marine ecosystems to increase spatiotemporal similarity (i.e., synchrony) of organic matter, nutrients, and microbial activities. Wetlands along the larger, deeper, and tidally influenced Shark River Slough (SRS) drainage had higher and more variable DOC, TN, and TP concentrations than wetlands along the smaller, shallower, tidally restricted Taylor River Slough/Panhandle (TS/Ph) drainage. Along SRS, DOC concentrations declined with proximity to coast, and increased in magnitude and variability following drought and flooding in 2015 and a hurricane in 2017. Along TS/Ph, DOC concentrations varied by site (higher in marine than freshwater wetlands) but not year. In both drainages, increases in TN from upstream freshwater marshes occurred following fire in 2008 and droughts in 2010 and 2015, whereas downstream increases in TP occurred with coastal storm surge from hurricanes in 2005 and 2017. Decreases in DOC:TN and DOC:TP were explained by increased TN and TP. Increases in bacterioplankton productivity occurred throughout both drainages following low‐temperature events (2010 and 2011) and a hurricane (2017). Long‐term TN and TP concentrations and bacterioplankton productivity were correlated ( r > 0.5) across a range of sampling distances (1–50 km), indicating spatiotemporal synchrony. DOC concentrations were not synchronized across space or time. Our study advances disturbance ecology theory by illustrating how disturbance events interact with long‐term environmental changes and hydrologic connectivity to determine the magnitude and extent of disturbance legacies. Understanding disturbance legacies will enhance prediction and enable more effective management of rapidly changing ecosystems.

Direct Observation of Low Strain, High Rate Deformation of Cultured Brain Tissue During Primary Blast - Edward W. Vogel; Matthew B. Panzer; Fatima N. Morales; Nevin Varghese; Cameron R. Bass; David F. Meaney; Barclay Morrison (Annals of Biomedical Engineering, 2020)

The association of HFE gene H63D polymorphism with endurance athlete status and aerobic capacity: novel findings and a meta-analysis - Ekaterina A. Semenova; Eri Miyamoto-Mikami; Egor B. Akimov; Fatima Al-Khelaifi; Haruka Murakami; Hirofumi Zempo; Elena S. Kostryukova; Nikolay A. Kulemin; Andrey K. Larin; Oleg V. Borisov; Motohiko Miyachi; Daniil V. Popov; et al. (European Journal of Applied Physiology, 2020)
Purpose Iron is an important component of the oxygen-binding proteins and may be critical to optimal athletic performance. Previous studies have suggested that the G allele of C/G rare variant (rs1799945), which causes H63D amino acid replacement, in the HFE is associated with elevated iron indexes and may give some advantage in endurance-oriented sports. The aim of the present study was to investigate the association between the HFE H63D polymorphism and elite endurance athlete status in Japanese and Russian populations, aerobic capacity and to perform a meta-analysis using current findings and three previous studies. Methods The study involved 315 international-level endurance athletes (255 Russian and 60 Japanese) and 809 healthy controls (405 Russian and 404 Japanese). Genotyping was performed using micro-array analysis or by PCR. VO 2max in 46 male Russian endurance athletes was determined using gas analysis system. Results The frequency of the iron-increasing CG/GG genotypes was significantly higher in Russian (38.0 vs 24.9%; OR 1.85, P = 0.0003) and Japanese (13.3 vs 5.0%; OR 2.95, P = 0.011) endurance athletes compared to ethnically matched controls. The meta-analysis using five cohorts (two French, Japanese, Spanish, and Russian; 586 athletes and 1416 controls) showed significant prevalence of the CG/GG genotypes in endurance athletes compared to controls (OR 1.96, 95% CI 1.58–2.45; P = 1.7 × 10 –9 ). Furthermore, the HFE G allele was associated with high V̇O 2max in male athletes [CC: 61.8 (6.1), CG/GG: 66.3 (7.8) ml/min/kg; P = 0.036]. Conclusions We have shown that the HFE H63D polymorphism is strongly associated with elite endurance athlete status, regardless ethnicities and aerobic capacity in Russian athletes.

Correction to: Culturable microbial composition in the midgut of Aedes aegypti strains with different susceptibility to dengue-2 virus infection - Edward H. Molina-Henao; M. Yineth Graffe; Elsa De La Cadena; Idalba M. Serrato; Adriana Correa; Lizeth V. Romero; Paola A. Caicedo; Clara B. Ocampo (Symbiosis, 2020)

Culturable microbial composition in the midgut of Aedes aegypti strains with different susceptibility to dengue-2 virus infection - Edward H. Molina-Henao; M. Yineth Graffe; Elsa P. De La Cadena; Idalba M. Serrato; Adriana Correa; Lizeth V. Romero; Paola A. Caicedo; Clara B. Ocampo (Symbiosis, 2020)

Changes in benthic community composition associated with the outbreak of the corallimorph, Rhodactis howesii, at Palmyra Atoll - Amanda L. Carter; Clinton B. Edwards; Michael D. Fox; Corinne G. Amir; Yoan Eynaud; Maggie D. Johnson; Levi S. Lewis; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

Auditory performance in bald eagles and red-tailed hawks: a comparative study of hearing in diurnal raptors - JoAnn McGee; Peggy B. Nelson; Julia B. Ponder; Jeffrey Marr; Patrick Redig; Edward J. Walsh (Journal of Comparative Physiology A, 2019)

Transgenic maize phosphoenolpyruvate carboxylase alters leaf–atmosphere CO2 and 13CO2 exchanges in Oryza sativa - Rita Giuliani; Shanta Karki; Sarah Covshoff; Hsiang-Chun Lin; Robert A. Coe; Nuria K. Koteyeva; Marc A. Evans; W. Paul Quick; Susanne von Caemmerer; Robert T. Furbank; Julian M. Hibberd; Gerald E. Edwards; et al. (Photosynthesis Research, 2019)

Decentralization and the environment: Assessing smallholder oil palm development in Indonesia - Rosamond L. Naylor; Matthew M. Higgins; Ryan B. Edwards; Walter P. Falcon (Ambio, 2019)

Metabolic rhythms in flowing waters: An approach for classifying river productivity regimes - Philip Savoy; Alison P. Appling; James B. Heffernan; Edward G. Stets; Jordan S. Read; Judson W. Harvey; Emily S. Bernhardt (Limnology and Oceanography, 2019)
Although seasonal patterns of ecosystem productivity have been extensively described and analyzed with respect to their primary forcings in terrestrial and marine systems, comparatively little is known about these same processes in rivers. However, it is now possible to perform a large‐scale synthesis on the patterns and drivers of river productivity regimes because of the recent sensor advances allowing for near‐continuous estimates of river productivity. Here, we explore a dataset of 47 U.S. rivers to examine whether there are characteristic river productivity regimes. We use classification approaches to develop a typology of productivity regimes and then use these regimes to examine differences with respect to potential controls of productivity. We identified two distinct metabolic regimes, which we named Summer Peak and Spring Peak Rivers , within our dataset. These regimes meaningfully differed in both the timing and magnitude of productivity and were robust to different approaches to classification. We also found that several variables, including watershed area and characteristics of water temperature or discharge, were able to predict the class membership of these regimes with modest accuracy. Our results support the presence of characteristic metabolic regimes and suggests that these regimes may have common sets of environmental controls. We present classification as one approach to begin exploring the productivity regimes of rivers. The strength of our approach is that it fully leverages these newly available high‐frequency productivity estimates to create classes that can be used to draw inferences about how the controls of river productivity differ between or within systems.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Hook size selectivity in the artisanal handline fishery of Shimoni fishing area, south coast, Kenya - Mary B. Ontomwa; Benerd M. Fulanda; Edward N. Kimani; Gladys M. Okemwa (Western Indian Ocean Journal of Marine Science, 2019)

Modeling Environmental DNA Transport in the Coastal Ocean Using Lagrangian Particle Tracking - Elizabeth A. Andruszkiewicz; Jeffrey R. Koseff; Oliver B. Fringer; Nicholas T. Ouellette; Anna B. Lowe; Christopher A. Edwards; Alexandria B. Boehm (Frontiers in Marine Science, 2019)

Limited coral mortality following acute thermal stress and widespread bleaching on Palmyra Atoll, central Pacific - Michael D. Fox; Amanda L. Carter; Clinton B. Edwards; Yuichiro Takeshita; Maggie D. Johnson; Vid Petrovic; Corinne G. Amir; Enric Sala; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

Addressing limitations in existing ‘simplified’ liquefaction triggering evaluation procedures: application to induced seismicity in the Groningen gas field - R. A. Green; J. J. Bommer; A. Rodriguez-Marek; B. W. Maurer; P. J. Stafford; B. Edwards; P. P. Kruiver; G. de Lange; J. van Elk (Bulletin of Earthquake Engineering, 2019)

Simulations for the development of a ground motion model for induced seismicity in the Groningen gas field, The Netherlands - B. Edwards; B. Zurek; E. van Dedem; P. J. Stafford; S. Oates; J. van Elk; B. deMartin; J. J. Bommer (Bulletin of Earthquake Engineering, 2019)

Subregional differences in groundfish distributional responses to anomalous ocean bottom temperatures in the northeast Pacific - Lingbo Li; Anne B. Hollowed; Edward D. Cokelet; Steven J. Barbeaux; Nicholas A. Bond; Aimee A. Keller; Jacquelynne R. King; Michelle M. McClure; Wayne A. Palsson; Phyllis J. Stabeno; Qiong Yang (Global Change Biology, 2019)
Although climate‐induced shifts in fish distribution have been widely reported at the population level, studies that account for ontogenetic shifts and subregional differences when assessing responses are rare.In this study, groundfish distributional changes in depth, latitude, and longitude were assessed at different size classes by species within nine subregions. We examined large, quality‐controlled datasets of depth‐stratified‐random bottom trawl surveys conducted during summer in three large regions—the Gulf of Alaska and the west coasts of Canada and the United States—over the period 1996–2015, a time period punctuated by a marine “heat wave.” Temporal biases in bottom temperature were minimized by subdividing each region into three subregions, each with short‐duration surveys. Near‐bottom temperatures, weighted by stratum area, were unsynchronized across subregions and exhibited varying subregional interannual variability. The weighted mean bottom depths in the subregions also vary largely among subregions. The centroids (centers of gravity) of groundfish distribution were weighted with catch per unit effort and stratum area for 10 commercially important groundfish species by size class and subregion. Our multivariate analyses showed that there were significant differences in aggregate fish movement responses to warm temperatures across subregions but not among species or sizes. Groundfish demonstrated poleward responses to warming temperatures only in a few subregions and moved shallower or deeper to seek colder waters. The temperature responses of groundfish depended on where they were. Under global warming, groundfish may form geographically distinct thermal ecoregions along the northeast Pacific shelf. Shallow‐depth species exhibited greatly different distributional responses to temperature changes across subregions while deep‐depth species of different subregions tend to have relatively similar temperature responses. Future climate studies would benefit by considering fish distributions on small subregional scales.

On Methodological issues in the Indo-European debate By Michel Danino - Marina Silva; John T Koch; Maria Pala; Ceiridwen J Edwards; Pedro Soares; Martin B Richards (Journal of Biosciences, 2019)

How “The Blob” affected groundfish distributions in the Gulf of Alaska - Qiong Yang; Edward D. Cokelet; Phyllis J. Stabeno; Lingbo Li; Anne B. Hollowed; Wayne A. Palsson; Nicholas A. Bond; Steven J. Barbeaux (Fisheries Oceanography, 2019)
We investigated the distributional shifts of groundfish in response to anomalous ocean conditions, particularly the recent anomalously warm period (2014–2016; “The Blob”), based on data from ten Gulf of Alaska bottom trawl surveys conducted by the Alaska Fisheries Science Center during 1996–2015. Six groundfish species were considered: Pacific cod ( Gadus macrocephalus ), arrowtooth flounder ( Atheresthes stomias ), walleye pollock ( Gadus chalcogrammus ), Pacific ocean perch ( Sebastes alutus ), northern rock sole ( Lepidopsetta polyxystra ), and southern rock sole ( Lepidopsetta bilineata ). Ontogenetic differences were examined by dividing data for each fish species into size classes. Our study demonstrated that after accounting for size‐specific depth preferences, the spatial responses of groundfish to anomalous ocean conditions differed by species and foraging guild in the central Gulf of Alaska. Pacific cod and arrowtooth flounder showed similar responses to ocean warming, but different responses to cooling. In general, Pacific cod moved to deeper depths in warmer years and moved to shallower depths in colder years. Arrowtooth flounder also moved deeper in warmer years. However, in colder years, large arrowtooth flounder (>40 cm) shifted toward shallower depths while smaller‐sized fish shifted toward deeper depths. In warmer years, large pollock (>30 cm) moved to deeper waters while smaller pollock (10–20 cm) moved to shallower waters. Pacific ocean perch exhibited an opposite response to thermal changes in habitat compared with Pacific cod and arrowtooth flounder. They moved deeper in colder years, but there was no clear change in depth as a function of size in response to warmer habitat.

Joint exposure to smoking, excessive weight, and physical inactivity and survival of ovarian cancer patients, evidence from the Ovarian Cancer Association Consortium - Albina N. Minlikeeva; Rikki Cannioto; Allan Jensen; Susanne K. Kjaer; Susan J. Jordan; Brenda Diergaarde; J. Brian Szender; Kunle Odunsi; Hani Almohanna; Paul Mayor; Kirsten Starbuck; Emese Zsiros; et al. (Cancer Causes & Control, 2019)

Modeling potential impacts of three benthic invasive species on the Lake Erie food web - Hongyan Zhang; Edward S. Rutherford; Doran M. Mason; Marion E. Wittmann; David M. Lodge; Xinhua Zhu; Timothy B. Johnson; Andrew Tucker (Biological Invasions, 2019)

Advancing Research for the Management of Long-Lived Species: A Case Study on the Greenland Shark - Jena E. Edwards; Elizabeth Hiltz; Franziska Broell; Peter G. Bushnell; Steven E. Campana; Jørgen S. Christiansen; Brynn M. Devine; Jeffrey J. Gallant; Kevin J. Hedges; M. Aaron MacNeil; Bailey C. McMeans; Julius Nielsen; et al. (Frontiers in Marine Science, 2019)

Quantitation of Purines from Pigeon Guano and Implications for Cryptococcus neoformans Survival During Infection - Jessica L. Chitty; David J. Edwards; Avril A. B. Robertson; Mark S. Butler; John A. Duley; Matthew A. Cooper; James A. Fraser (Mycopathologia, 2019)

Fluoride removal studies using virgin and Ti (IV)-modified Musa paradisiaca (plantain pseudo-stem) carbons - Bongekile R. Vilakati; Venkataraman Sivasankar; Edward N. Nxumalo; Bhekie B. Mamba; Kiyoshi Omine; Titus A. M. Msagati (Environmental Science and Pollution Research, 2019)

Decision support platforms for climate change adaptation: an overview and introduction - Jean P. Palutikof; Roger B. Street; Edward P. Gardiner (Climatic Change, 2019)

Looking to the future: guidelines for decision support as adaptation practice matures - Jean P. Palutikof; Roger B. Street; Edward P. Gardiner (Climatic Change, 2019)

Pre-diagnostic 25-hydroxyvitamin D levels and survival in cancer patients - Johanna E. Torfadottir; Thor Aspelund; Unnur A. Valdimarsdottir; Mary Frances Cotch; Laufey Tryggvadottir; Tamara B. Harris; Vilmundur Gudnason; Hans-Olov Adami; Lorelei A. Mucci; Edward L. Giovannucci; Meir J. Stampfer; Laufey Steingrimsdottir (Cancer Causes & Control, 2019)

Experimental constraints on the textures and origin of obsidian pyroclasts - James E. Gardner; Fabian B. Wadsworth; Edward W. Llewellin; James M. Watkins; Jason P. Coumans (Bulletin of Volcanology, 2019)

Interactive Effects of Hypoxia and Temperature on Coastal Pelagic Zooplankton and Fish - Michael R. Roman; Stephen B. Brandt; Edward D. Houde; James J. Pierson (Frontiers in Marine Science, 2019)

The effects of training population design on genomic prediction accuracy in wheat - Stefan McKinnon Edwards; Jaap B. Buntjer; Robert Jackson; Alison R. Bentley; Jacob Lage; Ed Byrne; Chris Burt; Peter Jack; Simon Berry; Edward Flatman; Bruno Poupard; Stephen Smith; et al. (Theoretical and Applied Genetics, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Bartonella quintana and Bartonella vinsonii subsp. vinsonii bloodstream co-infection in a girl from North Carolina, USA - Edward B. Breitschwerdt; Ricardo G. Maggi (Medical Microbiology and Immunology, 2019)

Multi-level emulation of complex climate model responses to boundary forcing data - Giang T. Tran; Kevin I. C. Oliver; Philip B. Holden; Neil R. Edwards; András Sóbester; Peter Challenor (Climate Dynamics, 2019)

Molecular characterization of hepatitis B virus in blood donors in Botswana - Wonderful T. Choga; Motswedi Anderson; Edward Zumbika; Sikhulile Moyo; Tshepiso Mbangiwa; Bonolo B. Phinius; Pinkie Melamu; Mukendi K. Kayembe; Ishmael Kasvosve; Theresa K. Sebunya; Jason T. Blackard; Max Essex; et al. (Virus Genes, 2019)

Contrasting genetic structure of sympatric congeneric gastropods: Do differences in habitat preference, abundance and distribution matter? - Edward J. G. Wort; Mark A. Chapman; Stephen J. Hawkins; Lucy Henshall; Alfonso Pita; Marc Rius; Suzanne T. Williams; Phillip B. Fenberg (Journal of Biogeography, 2019)
Aim The relationship of population genetics with the ecology and biogeography of species may be explored by comparing phenotypically similar but ecologically different congeners with overlapping ranges. We compared genetic differentiation between two congeneric rocky intertidal gastropods across a major portion of their sympatric range. We hypothesized that the habitat generalist with high abundance and continuous distribution would exhibit comparatively less genetic differentiation than the habitat specialist with low abundance and a fragmented distribution. Location North‐east Atlantic from the north‐west Iberian Peninsula to southern British coastline. Taxon Gastropoda, Trochidae, Steromphala (formerly Gibbula ). Methods Field surveys were conducted to assess the presence/absence and the abundance of Steromphala umbilicalis (generalist) and S. pennanti (specialist) at 23 localities along ~1,800 km coastline. We isolated polymorphic microsatellite markers for both species (seven loci for S. umbilicalis and eight for S. pennanti ) and used these to genotype 187 S. umbilicalis and 157 S. pennanti individuals. We used standard population genetic analyses to compare patterns of genetic differentiation between species in relation to the field surveys. Results Steromphala pennanti showed a more fragmented distribution, significantly lower abundance, and greater genetic differentiation than S. umbilicalis . One S. umbilicalis population towards the north of the range (southern Britain) was genetically distinct from all other sampled populations. Steromphala pennanti showed greater genetic differentiation between three southern localities, which may be attributable to its fragmented distribution and lower abundance because of limited availability of its preferred fucoid habitat in this region. We also suggest that oceanographic currents could be associated with regional genetic structure. Main conclusions The habitat generalist showed high‐local abundances, continuous distribution and low regional genetic differentiation. We found the opposite pattern for the habitat specialist. Our study highlights the importance of considering ecological (e.g. abundance, habitat preferences) and abiotic variables (e.g. ocean currents and temperature) for understanding differences in genetic structure of sympatrically distributed congeners.

Spatial distribution bias in subject-specific abnormalities analyses - Andrew B. Dodd; Josef M. Ling; Edward J. Bedrick; Timothy B. Meier; Andrew R. Mayer (Brain Imaging and Behavior, 2018)

Bending the rules: exploitation of allochthonous resources by a top‐predator modifies size‐abundance scaling in stream food webs - Daniel M. Perkins; Isabelle Durance; Francois K. Edwards; Jonathan Grey; Alan G. Hildrew; Michelle Jackson; J. Iwan Jones; Rasmus B. Lauridsen; Katrin Layer‐Dobra; Murray S. A. Thompson; Guy Woodward (Ecology Letters, 2018)
Body mass–abundance ( M‐N ) allometries provide a key measure of community structure, and deviations from scaling predictions could reveal how cross‐ecosystem subsidies alter food webs. For 31 streams across the UK, we tested the hypothesis that linear log‐log M‐N scaling is shallower than that predicted by allometric scaling theory when top predators have access to allochthonous prey. These streams all contained a common and widespread top predator (brown trout) that regularly feeds on terrestrial prey and, as hypothesised, deviations from predicted scaling increased with its dominance of the fish assemblage. Our study identifies a key beneficiary of cross‐ecosystem subsidies at the top of stream food webs and elucidates how these inputs can reshape the size‐structure of these ‘open’ systems.

Acute and chronic phagocyte determinants of cardiac allograft vasculopathy - Kristofor Glinton; Matthew DeBerge; Xin-Yi Yeap; Jenny Zhang; Joseph Forbess; Xunrong Luo; Edward B. Thorp (Seminars in Immunopathology, 2018)

Abundance and Distribution of Reef-Associated Fishes Around Small Oil and Gas Platforms in the Northern Gulf of Mexico’s Hypoxic Zone - David B. Reeves; Edward J. Chesney; Ryan T. Munnelly; Donald M. Baltz; Brian D. Marx (Estuaries and Coasts, 2018)

Long-Term Grazing Accelerated Litter Decomposition in Northern Temperate Grasslands - Xiaozhu Chuan; Cameron N. Carlyle; Edward W. Bork; Scott X. Chang; Daniel B. Hewins (Ecosystems, 2018)

Impact of Glutathione Peroxidase-1 (Gpx1) Genotype on Selenoenzyme and Transcript Expression When Repleting Selenium-Deficient Mice - Roger A. Sunde; Edward T. Zemaitis; Andrew B. Blink; Julia A. Lawinger (Biological Trace Element Research, 2018)

High‐resolution reconstruction of 8.2‐ka BP event documented in Père Noël cave, southern Belgium - M. Allan; N. Fagel; H. J. L. van der Lubbe; H. B. Vonhof; H. Cheng; R. Lawrence Edwards; S. Verheyden (Journal of Quaternary Science, 2018)
A distinct shift in δ 18 O, δ 13 C and trace element contents of the Père Noël (PN) stalagmite from southern Belgium revealed an abrupt climatic anomaly at 8.13 ± 0.03 ka BP (before present = before 1950 AD). This anomaly is characterized by a maximum drop in the δ 18 O (−1.4‰ compared the mean) between 8.13 and 8.10 ka BP (±0.03). This drop of δ 18 O coincides with a decrease in δ 13 C and trace element (Sr, Ba and Mg) concentrations suggesting drier conditions. Our precise chronology provides the timing of the outburst of proglacial lakes Agassiz and Ojibway that caused the δ 18 O, δ 13 C and trace elemental anomalies at 8.13–8.10 ± 0.03 ka BP, which corresponds to the 8.2‐ka BP event. The PN stalagmite bears δ 18 O values in fluid inclusions that covary with the δ 18 O values in calcite, suggesting that the speleothem calcite δ 18 O primarily reflects variations in the rainfall δ 18 O. Comparison of the PN record with different marine and terrestrial archives during the 8.2‐ka BP event shows a good agreement in timing and duration, suggesting that the PN speleothem can be regarded as a valuable proxy to better understand the 8.2‐ka BP event.

Aggregating fields of annual crops to form larger-scale monocultures can suppress dispersal-limited herbivores - Collin B. Edwards; Jay A. Rosenheim; Moran Segoli (Theoretical Ecology, 2018)

Colorectal and cardiovascular effects of [Lys5,MeLeu9,Nle10]-NKA(4-10) in anesthetized macaques - Nadia M. J. Rupniak; Mary Katofiasc; Edward C. Burgard; Karl B. Thor (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Critical comparison of molecular methods for detection and enumeration of the harmful algal species, Heterosigma akashiwo, in environmental water samples - Christopher R. Main; Dianne I. Greenfield; Cameron Doll; Yanfei Wang; Edward B. Whereat; Rebecca Mortensen; D. Tye Pettay; Kathryn J. Coyne (Journal of Applied Phycology, 2018)

Co-Processed Excipients for Dispersible Tablets—Part 2: Patient Acceptability - Karolina Dziemidowicz; Felipe L. Lopez; Ben J. Bowles; Andrew J. Edwards; Terry B. Ernest; Mine Orlu; Catherine Tuleu (AAPS PharmSciTech, 2018)

Co-Processed Excipients for Dispersible Tablets–Part 1: Manufacturability - Ben J. Bowles; Karolina Dziemidowicz; Felipe L. Lopez; Mine Orlu; Catherine Tuleu; Andrew J. Edwards; Terry B. Ernest (AAPS PharmSciTech, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Integrating Dynamic Subsurface Habitat Metrics Into Species Distribution Models - Stephanie Brodie; Michael G. Jacox; Steven J. Bograd; Heather Welch; Heidi Dewar; Kylie L. Scales; Sara M. Maxwell; Dana M. Briscoe; Christopher A. Edwards; Larry B. Crowder; Rebecca L. Lewison; Elliott L. Hazen (Frontiers in Marine Science, 2018)

Long-term grazing impacts on vegetation diversity, composition, and exotic species presence across an aridity gradient in northern temperate grasslands - Mark P. Lyseng; Edward W. Bork; Daniel B. Hewins; Mike J. Alexander; Cameron N. Carlyle; Scott X. Chang; Walter D. Willms (Plant Ecology, 2018)

Converging and emerging threats to health security - C. Raina MacIntyre; Thomas Edward Engells; Matthew Scotch; David James Heslop; Abba B. Gumel; George Poste; Xin Chen; Wesley Herche; Kathleen Steinhöfel; Samsung Lim; Alex Broom (Environment Systems and Decisions, 2018)

Characteristics and consequences of lava dome collapse at Ruawahia, Taupo Volcanic Zone, New Zealand - P. A. Ashwell; B. M. Kennedy; M. Edwards; J. W. Cole (Bulletin of Volcanology, 2018)

Physiological and regulatory underpinnings of geographic variation in reptilian cold tolerance across a latitudinal cline - Shane C. Campbell‐Staton; Anna Bare; Jonathan B. Losos; Scott V. Edwards; Zachary A. Cheviron (Molecular Ecology, 2018)
Understanding the mechanisms that produce variation in thermal performance is a key component to investigating climatic effects on evolution and adaptation. However, disentangling the effects of local adaptation and phenotypic plasticity in shaping patterns of geographic variation in natural populations can prove challenging. Additionally, the physiological mechanisms that cause organismal dysfunction at extreme temperatures are still largely under debate. Using the green anole, Anolis carolinensis , we integrate measures of cold tolerance ( CT min ), standard metabolic rate, heart size, blood lactate concentration and RNA seq data from liver tissue to investigate geographic variation in cold tolerance and its underlying mechanisms along a latitudinal cline. We found significant effects of thermal acclimation and latitude of origin on variation in cold tolerance. Increased cold tolerance correlates with decreased rates of oxygen consumption and blood lactate concentration (a proxy for oxygen limitation), suggesting elevated performance is associated with improved oxygen economy during cold exposure. Consistent with these results, co‐expression modules associated with blood lactate concentration are enriched for functions associated with blood circulation, coagulation and clotting. Expression of these modules correlates with thermal acclimation and latitude of origin. Our findings support the oxygen and capacity‐limited thermal tolerance hypothesis as a potential contributor to variation in reptilian cold tolerance. Moreover, differences in gene expression suggest regulation of the blood coagulation cascade may play an important role in reptilian cold tolerance and may be the target of natural selection in populations inhabiting colder environments.

Exploring the genetic and adaptive diversity of a pan-Mediterranean crop wild relative: narrow-leafed lupin - Mahsa Mousavi-Derazmahalleh; Philipp E. Bayer; Bruno Nevado; Bhavna Hurgobin; Dmitry Filatov; Andrzej Kilian; Lars G. Kamphuis; Karam B. Singh; Jens D. Berger; James K. Hane; David Edwards; William Erskine; et al. (Theoretical and Applied Genetics, 2018)

Toxicological effects of chemical constituents from Piper against the environmental burden Aedes aegypti Liston and their impact on non-target toxicity evaluation against biomonitoring aquatic insects - Prabhakaran Vasantha-Srinivasan; Annamalai Thanigaivel; Edward-Sam Edwin; Athirstam Ponsankar; Sengottayan Senthil-Nathan; Selvaraj Selin-Rani; Kandaswamy Kalaivani; Wayne B. Hunter; Veeramuthu Duraipandiyan; Naif Abdullah Al-Dhabi (Environmental Science and Pollution Research, 2018)

Acute toxicity of chemical pesticides and plant-derived essential oil on the behavior and development of earthworms, Eudrilus eugeniae (Kinberg) and Eisenia fetida (Savigny) - Prabhakaran Vasantha-Srinivasan; Sengottayan Senthil-Nathan; Athirstam Ponsankar; Annamalai Thanigaivel; Muthiah Chellappandian; Edward-Sam Edwin; Selvaraj Selin-Rani; Kandaswamy Kalaivani; Wayne B. Hunter; Veeramuthu Duraipandiyan; Naif Abdullah Al-Dhabi (Environmental Science and Pollution Research, 2018)

An evaluation of Z-transform algorithms for identifying subject-specific abnormalities in neuroimaging data - Andrew R. Mayer; Andrew B. Dodd; Josef M. Ling; Christopher J. Wertz; Nicholas A. Shaff; Edward J. Bedrick; Carlo Viamonte (Brain Imaging and Behavior, 2018)

A three-dimensional numerical study of river plume mixing processes in Otsuchi Bay, Japan - Kaushik Sasmal; Eiji Masunaga; Adrean Webb; Oliver B. Fringer; Edward S. Gross; Matthew D. Rayson; Hidekatsu Yamazaki (Journal of Oceanography, 2018)

First evidence for crossbreeding between invasive Iguana iguana and the native rock iguana (Genus Cyclura) on Little Cayman Island - Jeanette B. Moss; Mark E. Welch; Frederic J. Burton; Michael V. Vallee; Edward W. Houlcroft; Tanja Laaser; Glenn P. Gerber (Biological Invasions, 2018)

Taxonomy of prokaryotic viruses: 2017 update from the ICTV Bacterial and Archaeal Viruses Subcommittee - Evelien M. Adriaenssens; Johannes Wittmann; Jens H. Kuhn; Dann Turner; Matthew B. Sullivan; Bas E. Dutilh; Ho Bin Jang; Leonardo J. van Zyl; Jochen Klumpp; Malgorzata Lobocka; Andrea I. Moreno Switt; Janis Rumnieks; et al. (Archives of Virology, 2018)

Regional forcing explains local species diversity and turnover on tropical islands - Thomas Ibanez; Gunnar Keppel; Cláudia Baider; Chris Birkinshaw; Heike Culmsee; Susan Cordell; F. B. Vincent Florens; Janet Franklin; Christian P. Giardina; Thomas W. Gillespie; Melinda Laidlaw; Creighton M. Litton; et al. (Global Ecology and Biogeography, 2018)
Aim To determine the role of regional forcing on plot‐level species diversity and composition, and to quantify the relative importance of biogeographical and climatic factors in explaining woody plant diversity and composition at the local‐, island‐ and archipelago‐scale. Location Forty‐one tropical islands of the Indo‐Pacific region from Madagascar to Hawai‘i Island. Methods We analysed the diversity and composition of tropical woody plant communities located across 113 plots, 41 islands and 19 archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the role of regional forcing at the island and archipelago scale and to assess the relative importance of biogeographical (area and isolation of islands or archipelagos, geographical distance between plots) and climatic factors in explaining differences in local diversity and composition (species turnover). Analyses were conducted at different geographical scales (local, island and archipelago) and taxonomic levels (species, genus and family). Results Variation in local (plot‐level) diversity (as species density, the number of species per 100 woody plants) was primarily explained by island and archipelago identity. Maximum species density was positively correlated with the area of an island (or archipelago) and negatively correlated with the isolation of an archipelago. Local climatic variability was also a significant predictor of species density, but less important than regional forcing. Climate variables explained Main conclusions Regional forcing was the key driver of local diversity and composition on islands. Island area and archipelago isolation are likely driving local diversity through their effects on the pool of island species. Geographical distance between plots is the main factor explaining species turnover, while at higher taxonomic levels, climatic factors and niche conservatism are the main drivers.

“Think horizontally, act vertically”: the centenary (1916–2016) of pollen analysis and the legacy of Lennart von Post - Marie-José Gaillard; Björn E. Berglund; H. John B. Birks; Kevin J. Edwards; Felix Bittmann (Vegetation History and Archaeobotany, 2018)

Experimental sintering of ash at conduit conditions and implications for the longevity of tuffisites - James E. Gardner; Fabian B. Wadsworth; Edward W. Llewellin; James M. Watkins; Jason P. Coumans (Bulletin of Volcanology, 2018)

Anthropometric characteristics and ovarian cancer risk and survival - Albina N. Minlikeeva; Kirsten B. Moysich; Paul C. Mayor; John L. Etter; Rikki A. Cannioto; Roberta B. Ness; Kristen Starbuck; Robert P. Edwards; Brahm H. Segal; Sashikant Lele; Kunle Odunsi; Brenda Diergaarde; et al. (Cancer Causes & Control, 2018)

Resource partitioning among syntopic Characidae corroborated by gut content and stable isotope analyses - Karine O. Bonato; Edward D. Burress; Clarice B. Fialho; Jonathan W. Armbruster (Hydrobiologia, 2018)

Development of a rapid MALDI-TOF MS based epidemiological screening method using MRSA as a model organism - Åsa Lindgren; Nahid Karami; Roger Karlsson; Christina Åhrén; Martin Welker; Edward R. B. Moore; Liselott Svensson Stadler (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Glacial and interglacials in the Neotropics: a 130,000-year diatom record from central Panama - C. R. Shadik; G. M. Cárdenes-Sandí; A. Correa-Metrio; R. L. Edwards; A. Min; M. B. Bush (Journal of Paleolimnology, 2017)

Large-area imaging reveals biologically driven non-random spatial patterns of corals at a remote reef - Clinton B. Edwards; Yoan Eynaud; Gareth J. Williams; Nicole E. Pedersen; Brian J. Zgliczynski; Arthur C. R. Gleason; Jennifer E. Smith; Stuart A. Sandin (Coral Reefs, 2017)

Chemical sterilization of allograft dermal tissues - Abigail Phipps; Edward Vaynshteyn; John B. Kowalski; Manh-Dan Ngo; Karen Merritt; Joel Osborne; Evangelia Chnari (Cell and Tissue Banking, 2017)

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Body shape variation within the Southern Cavefish, Typhlichthys subterraneus (Percopsiformes: Amblyopsidae) - Pamela B. H. Burress; Edward D. Burress; Jonathan W. Armbruster (Zoomorphology, 2017)

Effects of nalfurafine on the reinforcing, thermal antinociceptive, and respiratory-depressant effects of oxycodone: modeling an abuse-deterrent opioid analgesic in rats - E. Andrew Townsend; Jennifer E. Naylor; S. Stevens Negus; Shelley R. Edwards; Hina N. Qureshi; Hunter W. McLendon; Christopher R. McCurdy; Coco N. Kapanda; Jussara M. do Carmo; Fernanda S. da Silva; John E. Hall; Kenneth J. Sufka; et al. (Psychopharmacology, 2017)

Assessment of the Neuroprotective Effects of Arginine-Rich Protamine Peptides, Poly-Arginine Peptides (R12-Cyclic, R22) and Arginine–Tryptophan-Containing Peptides Following In Vitro Excitotoxicity and/or Permanent Middle Cerebral Artery Occlusion in Rats - Bruno P. Meloni; Diego Milani; Jane L. Cross; Vince W. Clark; Adam B. Edwards; Ryan S. Anderton; David J. Blacker; Neville W. Knuckey (NeuroMolecular Medicine, 2017)

Music as an Adjunct to Opioid-Based Analgesia - Peter R. Chai; Stephanie Carreiro; Megan L. Ranney; Ketki Karanam; Marko Ahtisaari; Robert Edwards; Kristin L. Schreiber; Lubabah Ben-Ghaly; Timothy B. Erickson; Edward W. Boyer (Journal of Medical Toxicology, 2017)

Greater temperature sensitivity of plant phenology at colder sites: implications for convergence across northern latitudes - Janet Prevéy; Mark Vellend; Nadja Rüger; Robert D. Hollister; Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Karin Clark; Elisabeth J. Cooper; Bo Elberling; Anna M. Fosaa; Gregory H. R. Henry; et al. (Global Change Biology, 2017)
Warmer temperatures are accelerating the phenology of organisms around the world. Temperature sensitivity of phenology might be greater in colder, higher latitude sites than in warmer regions, in part because small changes in temperature constitute greater relative changes in thermal balance at colder sites. To test this hypothesis, we examined up to 20 years of phenology data for 47 tundra plant species at 18 high‐latitude sites along a climatic gradient. Across all species, the timing of leaf emergence and flowering was more sensitive to a given increase in summer temperature at colder than warmer high‐latitude locations. A similar pattern was seen over time for the flowering phenology of a widespread species, Cassiope tetragona . These are among the first results highlighting differential phenological responses of plants across a climatic gradient and suggest the possibility of convergence in flowering times and therefore an increase in gene flow across latitudes as the climate warms.

History of hypertension, heart disease, and diabetes and ovarian cancer patient survival: evidence from the ovarian cancer association consortium - Albina N. Minlikeeva; Jo L. Freudenheim; Rikki A. Cannioto; J. Brian Szender; Kevin H. Eng; Francesmary Modugno; Roberta B. Ness; Michael J. LaMonte; Grace Friel; Brahm H. Segal; Kunle Odunsi; Paul Mayor; et al. (Cancer Causes & Control, 2017)

Taxonomy of prokaryotic viruses: 2016 update from the ICTV bacterial and archaeal viruses subcommittee - Evelien M. Adriaenssens; Mart Krupovic; Petar Knezevic; Hans-Wolfgang Ackermann; Jakub Barylski; J. Rodney Brister; Martha R. C. Clokie; Siobain Duffy; Bas E. Dutilh; Robert A. Edwards; Francois Enault; Ho Bin Jang; et al. (Archives of Virology, 2017)

Ensemble Decision Tree Models Using RUSBoost for Estimating Risk of Iron Failure in Drinking Water Distribution Systems - S. R. Mounce; K. Ellis; J. M. Edwards; V. L. Speight; N. Jakomis; J. B. Boxall (Water Resources Management, 2017)

Modeling for Understanding v. Modeling for Numbers - Edward B. Rastetter (Ecosystems, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

In‐situ incubation of iron‐sulfur mineral reveals a diverse chemolithoautotrophic community and a new biogeochemical role for Thiomicrospira - Roman A. Barco; Colleen L. Hoffman; Gustavo A. Ramírez; Brandy M. Toner; Katrina J. Edwards; Jason B. Sylvan (Environmental Microbiology, 2017)
Summary Sulfide mineral precipitation occurs at mid‐ocean ridge (MOR) spreading centers, both in the form of plume particles and seafloor massive sulfide structures. A common constituent of MOR is the iron‐bearing sulfide mineral pyrrhotite, which was chosen as a substrate for in‐situ incubation studies in shallow waters of Catalina Island, CA to investigate the colonization of iron‐oxidizing bacteria. Microbial community datasets were obtained from in‐situ incubated pyrrhotite, allowing for direct comparison to microbial communities of iron‐sulfides from active and inactive chimneys in deep‐sea environments. Unclassified Gammaproteobacteria and Alphaproteobacteria ( Magnetovibrio) largely dominated the bacterial community on pyrrhotite samples incubated in the water column while samples incubated at the surface sediment showed more even dominance by Deltaproteobacteria ( Desulfobulbus ), Gammaproteobacteria (Piscirickettsiaceae), Alphaproteobacteria (Rhodobacteraceae), and Bacteroidetes (Flavobacteriia). Cultivations that originated from pyrrhotite samples resulted in the enrichment of both, sheath‐forming and stalk‐forming Zetaproteobacteria. Additionally, a putative novel species of Thiomicrospira was isolated and shown to grow autotrophically with iron, indicating a new biogeochemical role for this ubiquitous microorganism.

Valuing increased zinc (Zn) fertiliser-use in Pakistan - Edward J. M. Joy; Waqar Ahmad; Munir H. Zia; Diriba B. Kumssa; Scott D. Young; E. Louise Ander; Michael J. Watts; Alexander J. Stein; Martin R. Broadley (Plant and Soil, 2017)

Characterisation of neuroprotective efficacy of modified poly-arginine-9 (R9) peptides using a neuronal glutamic acid excitotoxicity model - Adam B. Edwards; Ryan S. Anderton; Neville W. Knuckey; Bruno P. Meloni (Molecular and Cellular Biochemistry, 2017)

The Neuroprotective Peptide Poly-Arginine-12 (R12) Reduces Cell Surface Levels of NMDA NR2B Receptor Subunit in Cortical Neurons; Investigation into the Involvement of Endocytic Mechanisms - Gabriella MacDougall; Ryan S. Anderton; Adam B. Edwards; Neville W. Knuckey; Bruno P. Meloni (Journal of Molecular Neuroscience, 2017)

Application of human factors engineering (HFE) to the design of a naloxone auto-injector for the treatment of opioid emergencies - Robert B. Raffa; Robert Taylor; Joseph V. Pergolizzi; Srinivas Nalamachu; Eric S. Edwards; Evan T. Edwards (Drug Delivery and Translational Research, 2017)
The increased use of opioids for chronic treatment of pain and the resulting epidemic of opioid overdoses have created a major public health challenge. Parenteral naloxone has been used since the 1970’s to treat opioid overdose. Recently, a novel naloxone auto-injector device (EVZIO, kaleo, Inc., Richmond, VA) was approved by the Food and Drug Administration. In this article, we review the Human Factors Engineering (HFE) process used in the development and testing of this novel naloxone auto-injector currently used in nonmedical settings for the emergency treatment of known or suspected opioid overdose. HFE methods were employed throughout the product development process for the naloxone auto-injector including formative and summative studies in order to optimize the auto-injector’s user interface, mitigate use-related hazards and increase reliability during an opioid emergency use scenario. HFE was also used to optimize the product’s design and user interface in order to reduce or prevent user confusion and misuse. The naloxone auto-injector went through a rigorous HFE process that included perceptual, cognitive, and physical action analysis; formative usability evaluations; use error analysis and summative design validation studies. Applying HFE resulted in the development of a product that is safe, fast, easy and predictably reliable to deliver a potentially life-saving dose of naloxone during an opioid overdose emergency. The naloxone auto-injector may be considered as a universal precaution option for at-risk patients prescribed opioids or those who are at increased risk for an opioid overdose emergency.

Evolution of a small hydrothermal eruption episode through a mud pool of varying depth and rheology, White Island, NZ - M. J. Edwards; B. M. Kennedy; A. D. Jolly; B. Scheu; P. Jousset (Bulletin of Volcanology, 2017)

Ecosystem responses to climate change at a Low Arctic and a High Arctic long-term research site - John E. Hobbie; Gaius R. Shaver; Edward B. Rastetter; Jessica E. Cherry; Scott J. Goetz; Kevin C. Guay; William A. Gould; George W. Kling (Ambio, 2017)

The effect of liquid composition on the partitioning of Ni between olivine and silicate melt - Andrew K. Matzen; Michael B. Baker; John R. Beckett; Bernard J. Wood; Edward M. Stolper (Contributions to Mineralogy and Petrology, 2017)

Review of Fusarium species isolated in association with mango malformation in Australia - E. C. Y. Liew; M. H. Laurence; C. A. Pearce; R. G. Shivas; G. I. Johnson; Y.P. Tan; J. Edwards; S. Perry; A.W. Cooke; B. A. Summerell (Australasian Plant Pathology, 2016)

Fine-scale spatial variation in ice cover and surface temperature trends across the surface of the Laurentian Great Lakes - Lacey A. Mason; Catherine M. Riseng; Andrew D. Gronewold; Edward S. Rutherford; Jia Wang; Anne Clites; Sigrid D. P. Smith; Peter B. McIntyre (Climatic Change, 2016)

Daphnia magna’s sense of competition: intra-specific interactions (ISI) alter life history strategies and increase metals toxicity - Kurt A. Gust; Alan J. Kennedy; Nicolas L. Melby; Mitchell S. Wilbanks; Jennifer Laird; Barbara Meeks; Erik B. Muller; Roger M. Nisbet; Edward J. Perkins (Ecotoxicology, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

Hyperspectral logging of middle Cambrian marine sediments with hydrocarbon prospectivity: a case study from the southern Georgina Basin, northern Australia - B. Ayling; J. Huntington; B. Smith; D. Edwards (Australian Journal of Earth Sciences, 2016)

Commercially Available Rapid Methods for Detection of Selected Food-borne Pathogens - Wladir B. Valderrama; Edward G. Dudley; Stephanie Doores; Catherine N. Cutter (Critical Reviews in Food Science and Nutrition, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Tree‐mycorrhizal associations detected remotely from canopy spectral properties - Joshua B. Fisher; Sean Sweeney; Edward R. Brzostek; Tom P. Evans; Daniel J. Johnson; Jonathan A. Myers; Norman A. Bourg; Amy T. Wolf; Robert W. Howe; Richard P. Phillips (Global Change Biology, 2016)
A central challenge in global ecology is the identification of key functional processes in ecosystems that scale, but do not require, data for individual species across landscapes. Given that nearly all tree species form symbiotic relationships with one of two types of mycorrhizal fungi – arbuscular mycorrhizal ( AM ) and ectomycorrhizal ( ECM ) fungi – and that AM ‐ and ECM ‐dominated forests often have distinct nutrient economies, the detection and mapping of mycorrhizae over large areas could provide valuable insights about fundamental ecosystem processes such as nutrient cycling, species interactions, and overall forest productivity. We explored remotely sensed tree canopy spectral properties to detect underlying mycorrhizal association across a gradient of AM ‐ and ECM ‐dominated forest plots. Statistical mining of reflectance and reflectance derivatives across moderate/high‐resolution Landsat data revealed distinctly unique phenological signals that differentiated AM and ECM associations. This approach was trained and validated against measurements of tree species and mycorrhizal association across ~130 000 trees throughout the temperate United States. We were able to predict 77% of the variation in mycorrhizal association distribution within the forest plots ( P

Genetic Analysis of the Indri Reveals No Evidence of Distinct Subspecies - Rick A. Brenneman; Adam T. McLain; Justin M. Taylor; John R. Zaonarivelo; Runhua Lei; Susie M. McGuire; Rambinintsoa Andriantompohavana; Anthony B. Rylands; Edward E. Louis (International Journal of Primatology, 2016)

A prospective study of oral contraceptive use and colorectal adenomas - Brittany M. Charlton; Edward Giovannucci; Charles S. Fuchs; Andrew T. Chan; Jung Eun Lee; Yin Cao; Stacey A. Missmer; Bernard A. Rosner; Susan E. Hankinson; Walter Willett; Kana Wu; Karin B. Michels (Cancer Causes & Control, 2016)

A Framework to Assess Biogeochemical Response to Ecosystem Disturbance Using Nutrient Partitioning Ratios - J. Marty Kranabetter; Kendra K. McLauchlan; Sara K. Enders; Jennifer M. Fraterrigo; Philip E. Higuera; Jesse L. Morris; Edward B. Rastetter; Rebecca Barnes; Brian Buma; Daniel G. Gavin; Laci M. Gerhart; Lindsey Gillson; et al. (Ecosystems, 2016)

Taxonomy of prokaryotic viruses: update from the ICTV bacterial and archaeal viruses subcommittee - Mart Krupovic; Bas E. Dutilh; Evelien M. Adriaenssens; Johannes Wittmann; Finn K. Vogensen; Mathew B. Sullivan; Janis Rumnieks; David Prangishvili; Rob Lavigne; Andrew M. Kropinski; Jochen Klumpp; Annika Gillis; et al. (Archives of Virology, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Prediction of Timing of Watermain Failure Using Gene Expression Models - Ahmed M. A. Sattar; B. Gharabaghi; Edward A. McBean (Water Resources Management, 2016)

Are Hypsodonty and Occlusal Enamel Complexity Evolutionarily Correlated in Ungulates? - Nicholas A. Famoso; Edward Byrd Davis; Robert S. Feranec; Samantha S. B. Hopkins; Samantha A. Price (Journal of Mammalian Evolution, 2016)

The invertebrate ecology of the Chalk aquifer in England (UK) - L. Maurice; A. R. Robertson; D. White; L. Knight; T. Johns; F. Edwards; M. Arietti; J. P. R. Sorensen; D. Weitowitz; B. P. Marchant; J. P. Bloomfield (Hydrogeology Journal, 2016)

Carbon cost of plant nitrogen acquisition: global carbon cycle impact from an improved plant nitrogen cycle in the Community Land Model - Mingjie Shi; Joshua B. Fisher; Edward R. Brzostek; Richard P. Phillips (Global Change Biology, 2016)
Plants typically expend a significant portion of their available carbon ( C ) on nutrient acquisition – C that could otherwise support growth. However, given that most global terrestrial biosphere models ( TBM s) do not include the C cost of nutrient acquisition, these models fail to represent current and future constraints to the land C sink. Here, we integrated a plant productivity‐optimized nutrient acquisition model – the Fixation and Uptake of Nitrogen Model – into one of the most widely used TBM s, the Community Land Model. Global plant nitrogen ( N ) uptake is dynamically simulated in the coupled model based on the C costs of N acquisition from mycorrhizal roots, nonmycorrhizal roots, N‐fixing microbes, and retranslocation (from senescing leaves). We find that at the global scale, plants spend 2.4 Pg C yr −1 to acquire 1.0 Pg N yr −1 , and that the C cost of N acquisition leads to a downregulation of global net primary production ( NPP ) by 13%. Mycorrhizal uptake represented the dominant pathway by which N is acquired, accounting for ~66% of the N uptake by plants. Notably, roots associating with arbuscular mycorrhizal ( AM ) fungi – generally considered for their role in phosphorus (P) acquisition – are estimated to be the primary source of global plant N uptake owing to the dominance of AM ‐associated plants in mid‐ and low‐latitude biomes. Overall, our coupled model improves the representations of NPP downregulation globally and generates spatially explicit patterns of belowground C allocation, soil N uptake, and N retranslocation at the global scale. Such model improvements are critical for predicting how plant responses to altered N availability (owing to N deposition, rising atmospheric CO 2 , and warming temperatures) may impact the land C sink.

Breaking out of biogeographical modules: range expansion and taxon cycles in the hyperdiverse ant genus Pheidole - Evan P. Economo; Eli M. Sarnat; Milan Janda; Ronald Clouse; Pavel B. Klimov; Georg Fischer; Benjamin D. Blanchard; Lizette N. Ramirez; Alan N. Andersen; Maia Berman; Benoit Guénard; Andrea Lucky; et al. (Journal of Biogeography, 2015)
Aim We sought to reconstruct the biogeographical structure and dynamics of a hyperdiverse ant genus, Pheidole, and to test several predictions of the taxon cycle hypothesis. Using large datasets on Pheidole geographical distributions and phylogeny, we (1) inferred patterns of biogeographical modularity (clusters of areas with similar faunal composition), (2) tested whether species in open habitats are more likely to be expanding their range beyond module boundaries, and (3) tested whether there is a bias of lineage flow from high‐ to low‐diversity areas. Location The Old World. Methods We compiled and jointly analysed a comprehensive database of Pheidole geographical distributions, the ecological affinities of different species, and a multilocus phylogeny of the Old World radiation. We used network modularity methods to infer biogeographical structure in the genus and comparative methods to evaluate the hypotheses. Results The network analysis identified eight biogeographical modules, and a suite of species with anomalous ranges that are statistically more likely to occur in open habitat, supporting the hypothesis that open habitats promote range expansion. Phylogenetic analysis shows evidence for a cascade pattern of colonization from Asia to New Guinea to the Pacific, but no ‘upstream’ colonization in the reverse direction. Main conclusions The distributions of Pheidole lineages in the Old World are highly modular, with modules generally corresponding to biogeographical regions inferred in other groups of organisms. However, some lineages have expanded their ranges across module boundaries, and these species are more likely to be adapted to open habitats rather than interior forest. In addition, there is a cascade pattern of dispersal from higher to lower diversity areas during these range expansions. Our findings are consistent with the taxon cycle hypothesis, although they do not rule out alternative interpretations.

Evaluation of microbial transport during aerobic bioaugmentation of an RDX-contaminated aquifer - Fiona H. Crocker; Karl J. Indest; Carina M. Jung; Dawn E. Hancock; Mark E. Fuller; Paul B. Hatzinger; Simon Vainberg; Jonathan D. Istok; Edward Wilson; Mandy M. Michalsen (Biodegradation, 2015)

Worldwide impacts of climate change on energy for heating and cooling - Maryse Labriet; Santosh R. Joshi; Marc Vielle; Philip B. Holden; Neil R. Edwards; Amit Kanudia; Richard Loulou; Frédéric Babonneau (Mitigation and Adaptation Strategies for Global Change, 2015)

Seascape drivers of M acrocystis pyrifera population genetic structure in the northeast P acific - Mattias L. Johansson; Filipe Alberto; Daniel C. Reed; Peter T. Raimondi; Nelson C. Coelho; Mary A. Young; Patrick T. Drake; Christopher A. Edwards; Kyle Cavanaugh; Jorge Assis; Lydia B. Ladah; Tom W. Bell; et al. (Molecular Ecology, 2015)
At small spatial and temporal scales, genetic differentiation is largely controlled by constraints on gene flow, while genetic diversity across a species' distribution is shaped on longer temporal and spatial scales. We assess the hypothesis that oceanographic transport and other seascape features explain different scales of genetic structure of giant kelp, M acrocystis pyrifera . We followed a hierarchical approach to perform a microsatellite‐based analysis of genetic differentiation in M acrocystis across its distribution in the northeast P acific. We used seascape genetic approaches to identify large‐scale biogeographic population clusters and investigate whether they could be explained by oceanographic transport and other environmental drivers. We then modelled population genetic differentiation within clusters as a function of oceanographic transport and other environmental factors. Five geographic clusters were identified: A laska/ C anada, central C alifornia, continental S anta B arbara, C alifornia C hannel I slands and mainland southern C alifornia/ B aja C alifornia peninsula. The strongest break occurred between central and southern C alifornia, with mainland S anta B arbara sites forming a transition zone between the two. Breaks between clusters corresponded approximately to previously identified biogeographic breaks, but were not solely explained by oceanographic transport. An isolation‐by‐environment ( IBE ) pattern was observed where the northern and southern C hannel I slands clustered together, but not with closer mainland sites, despite the greater distance between them. The strongest environmental association with this IBE pattern was observed with light extinction coefficient, which extends suitable habitat to deeper areas. Within clusters, we found support for previous results showing that oceanographic connectivity plays an important role in the population genetic structure of M acrocystis in the Northern hemisphere.

Cellular therapy in combination with cytokines improves survival in a xenograft mouse model of ovarian cancer - Susan B. Ingersoll; Sarfraz Ahmad; Hasina C. McGann; Robert K. Banks; Nicole M. Stavitzski; Milan Srivastava; Ghazanfar Ali; Neil J. Finkler; John R. Edwards; Robert W. Holloway (Molecular and Cellular Biochemistry, 2015)

Cardiorespiratory fitness is associated with brain structure, cognition, and mood in a middle-aged cohort at risk for Alzheimer’s disease - Elizabeth A. Boots; Stephanie A. Schultz; Jennifer M. Oh; Jordan Larson; Dorothy Edwards; Dane Cook; Rebecca L. Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; et al. (Brain Imaging and Behavior, 2015)

Science–policy processes for transboundary water governance - Derek Armitage; Rob C. de Loë; Michelle Morris; Tom W. D. Edwards; Andrea K. Gerlak; Roland I. Hall; Dave Huitema; Ray Ison; David Livingstone; Glen MacDonald; Naho Mirumachi; Ryan Plummer; et al. (Ambio, 2015)

Ecosystem’s 80th and the Reemergence of Emergence - Edward B. Rastetter; Joseph J. Vallino (Ecosystems, 2015)

Increasing In-Row Spacing Enhances Potato Virus Y and Potato Leafroll Virus Spread in Potato - Jeffrey A. Davis; Edward B. Radcliffe; David W. Ragsdale; Ian MacRae (American Journal of Potato Research, 2015)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

The Effect of Cerium Oxide Nanoparticle Valence State on Reactive Oxygen Species and Toxicity - Katherine M. Dunnick; Rajalekshmi Pillai; Kelly L. Pisane; Aleksandr B. Stefaniak; Edward M. Sabolsky; Stephen S. Leonard (Biological Trace Element Research, 2015)

Immunoglobulin VH gene diversity and somatic hypermutation during SIV infection of rhesus macaques - Kejun Guo; Kalani Halemano; Kimberly Schmitt; Miki Katuwal; Yaqiong Wang; Michael S. Harper; Karl J. Heilman; Takeo Kuwata; Edward B. Stephens; Mario L. Santiago (Immunogenetics, 2015)

Savagea faecisuis gen. nov., sp. nov., a tylosin- and tetracycline-resistant bacterium isolated from a swine-manure storage pit - Terence R. Whitehead; Crystal N. Johnson; Nisha B. Patel; Michael A. Cotta; Edward R. B. Moore; Paul A. Lawson (Antonie van Leeuwenhoek, 2015)

Association of von Willebrand factor blood levels with exercise hypertension - Sonja B. Nikolic; Murray J. Adams; Petr Otahal; Lindsay M. Edwards; James E. Sharman (European Journal of Applied Physiology, 2015)

Climate change implications in the northern coastal temperate rainforest of North America - Colin S. Shanley; Sanjay Pyare; Michael I. Goldstein; Paul B. Alaback; David M. Albert; Colin M. Beier; Todd J. Brinkman; Rick T. Edwards; Eran Hood; Andy MacKinnon; Megan V. McPhee; Trista M. Patterson; et al. (Climatic Change, 2015)

A continental‐scale analysis of feral cat diet in Australia - Tim S. Doherty; Robert A. Davis; Eddie J. B. van Etten; Dave Algar; Neil Collier; Chris R. Dickman; Glenn Edwards; Pip Masters; Russell Palmer; Sue Robinson (Journal of Biogeography, 2015)
Aim Reducing the impacts of feral cats ( Felis catus ) is a priority for conservation managers across the globe, and success in achieving this aim requires a detailed understanding of the species’ ecology across a broad spectrum of climatic and environmental conditions. We reviewed the diet of the feral cat across Australia and on Australian territorial islands, seeking to identify biogeographical patterns in dietary composition and diversity, and use the results to consider how feral cats may best be managed. Location Australia and its territorial islands. Methods Using 49 published and unpublished data sets, we modelled trophic diversity and the consumption of eight food groups against latitude, longitude, mean temperature, precipitation, environmental productivity and climate‐habitat regions. Results We recorded 400 vertebrate species that feral cats feed on or kill in Australia, including 28 IUCN Red List species. We found evidence of continental‐scale prey‐switching from rabbits to small mammals, previously recorded only at the local scale. The consumption of arthropods, reptiles, rabbits, rodents and medium‐sized native mammals varied with different combinations of latitude, longitude, mean annual precipitation, temperature and environmental productivity. The frequency of rodents and dasyurids in cats’ diets increased as rabbit consumption decreased. Main conclusions The feral cat is an opportunistic, generalist carnivore that consumes a diverse suite of vertebrate prey across Australia. It uses a facultative feeding strategy, feeding mainly on rabbits when they are available, but switching to other food groups when they are not. Control programmes aimed at culling rabbits could potentially decrease the availability of a preferred food source for cats and then lead to greater predation pressure on native mammals. The interplay between cat diet and prey species diversity at a continental scale is complex, and thus cat management is likely to be necessary and most effective at the local landscape level.

Worldwide phylogeography of the invasive ctenophore Mnemiopsis leidyi (Ctenophora) based on nuclear and mitochondrial DNA data - K. M. Bayha; M. H. Chang; C. L. Mariani; J. L. Richardson; D. L. Edwards; T. S. DeBoer; C. Moseley; E. Aksoy; M. B. Decker; P. M. Gaffney; G. R. Harbison; J. H. McDonald; et al. (Biological Invasions, 2015)

Design Control for Clinical Translation of 3D Printed Modular Scaffolds - Scott J. Hollister; Colleen L. Flanagan; David A. Zopf; Robert J. Morrison; Hassan Nasser; Janki J. Patel; Edward Ebramzadeh; Sophia N. Sangiorgio; Matthew B. Wheeler; Glenn E. Green (Annals of Biomedical Engineering, 2015)

Diversity within the genus Elymus (Poaceae: Triticeae) as investigated by the analysis of the nr5S rDNA variation in species with St and H haplomes - B. R. Baum; T. Edwards; D. A. Johnson (Molecular Genetics and Genomics, 2015)

Decadal environmental ‘memory’ in a reef coral? - B. E. Brown; R. P. Dunne; A. J. Edwards; M. J. Sweet; N. Phongsuwan (Marine Biology, 2015)

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

Admixture mapping identifies a locus at 15q21.2–22.3 associated with keloid formation in African Americans - Digna R. Velez Edwards; Krystal S. Tsosie; Scott M. Williams; Todd L. Edwards; Shirley B. Russell (Human Genetics, 2014)

Conserving the World's Finest Grassland Amidst Ambitious National Development - NYAMSUREN BATSAIKHAN; BAYARBAATAR BUUVEIBAATAR; BAZAAR CHIMED; OIDOV ENKHTUYA; DAVAA GALBRAKH; OYUNSAIKHAN GANBAATAR; BADAMJAV LKHAGVASUREN; DEJID NANDINTSETSEG; JOEL BERGER; JUSTIN M. CALABRESE; ANN E. EDWARDS; WILLIAM F. FAGAN; et al. (Conservation Biology, 2014)

Range‐wide multilocus phylogeography of the red fox reveals ancient continental divergence, minimal genomic exchange and distinct demographic histories - Mark J. Statham; James Murdoch; Jan Janecka; Keith B. Aubry; Ceiridwen J. Edwards; Carl D. Soulsbury; Oliver Berry; Zhenghuan Wang; David Harrison; Malcolm Pearch; Louise Tomsett; Judith Chupasko; et al. (Molecular Ecology, 2014)
Widely distributed taxa provide an opportunity to compare biogeographic responses to climatic fluctuations on multiple continents and to investigate speciation. We conducted the most geographically and genomically comprehensive study to date of the red fox ( Vulpes vulpes ), the world's most widely distributed wild terrestrial carnivore. Analyses of 697 bp of mitochondrial sequence in ~1000 individuals suggested an ancient Middle Eastern origin for all extant red foxes and a 400 kya ( SD = 139 kya) origin of the primary North American (Nearctic) clade. Demographic analyses indicated a major expansion in Eurasia during the last glaciation (~50 kya), coinciding with a previously described secondary transfer of a single matriline (Holarctic) to North America. In contrast, North American matrilines (including the transferred portion of Holarctic clade) exhibited no signatures of expansion until the end of the Pleistocene (~12 kya). Analyses of 11 autosomal loci from a subset of foxes supported the colonization time frame suggested by mt DNA (and the fossil record) but, in contrast, reflected no detectable secondary transfer, resulting in the most fundamental genomic division of red foxes at the Bering Strait. Endemic continental Y‐chromosome clades further supported this pattern. Thus, intercontinental genomic exchange was overall very limited, consistent with long‐term reproductive isolation since the initial colonization of North America. Based on continental divergence times in other carnivoran species pairs, our findings support a model of peripatric speciation and are consistent with the previous classification of the North American red fox as a distinct species, V. fulva .

Archaeological Evidence of Validity of Fish Populations on Unexploited Reefs as Proxy Targets for Modern Populations - KEN LONGENECKER; YVONNE L. CHAN; ROBERT J. TOONEN; DAVID B. CARLON; TERRY L. HUNT; ALAN M. FRIEDLANDER; EDWARD E. DEMARTINI (Conservation Biology, 2014)
Reef‐fish management and conservation is hindered by a lack of information on fish populations prior to large‐scale contemporary human impacts. As a result, relatively pristine sites are often used as conservation baselines for populations near sites affected by humans. This space‐for‐time approach can only be validated by sampling assemblages through time. We used archaeological remains to evaluate whether the remote, uninhabited Northwestern Hawaiian Islands (NWHI) might provide a reasonable proxy for a lightly exploited baseline in the Main Hawaiian Islands (MHI). We used molecular and morphological techniques to describe the taxonomic and size composition of the scarine parrotfish catches present in 2 archaeological assemblages from the MHI, compared metrics of these catches with modern estimates of reproductive parameters to evaluate whether catches represented by the archaeological material were consistent with sustainable fishing, and evaluated overlap between size structures represented by the archaeological material and modern survey data from the MHI and the NWHI to assess whether a space‐for‐time substitution is reasonable. The parrotfish catches represented by archaeological remains were consistent with sustainable fishing because they were dominated by large, mature individuals whose average size remained stable from prehistoric (AD approximately 1400–1700) through historic (AD 1700–1960) periods. The ancient catches were unlike populations in the MHI today. Overlap between the size structure of ancient MHI catches and modern survey data from the NWHI or the MHI was an order of magnitude greater for the NWHI comparison, a result that supports the validity of using the NWHI parrotfish data as a proxy for the MHI before accelerated, heavy human impacts in modern times. Evidencia Arqueológica de la Validez de Poblaciones de Peces en Arrecifes Sin Explotar como Objetivos de Apoderamiento para Poblaciones Actuales

Effects of climate change on the physiology of giant kelp, Macrocystis pyrifera, and grazing by purple urchin, Strongylocentrotus purpuratus - Matthew B. Brown; Matthew S. Edwards; Kwang Young Kim (Algae, 2014)

Brain Network Activation (BNA) Reveals Scopolamine-Induced Impairment of Visual Working Memory - Amit Reches; Naama Levy-Cooperman; Ilan Laufer; Revital Shani-Hershkovitch; Keren Ziv; Dani Kerem; Noga Gal; Yaki Stern; Guy Cukierman; Myroslava K. Romach; Edward M. Sellers; Amir B. Geva (Journal of Molecular Neuroscience, 2014)

Involvement of nucleus accumbens AMPA receptor trafficking in augmentation of D- amphetamine reward in food-restricted rats - Xing-Xiang Peng; Soledad Cabeza de Vaca; Edward B. Ziff; Kenneth D. Carr (Psychopharmacology, 2014)

What does the nr5S DNA multigene family tell us about the genomic relationship between Dasypyrum breviaristatum and D. villosum (Triticeae: Poaceae)? - B. R. Baum; T. Edwards; D. A. Johnson (Molecular Genetics and Genomics, 2014)

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Association of C-peptide and leptin with prostate cancer incidence in the Health Professionals Follow-up Study - Gabriel Y. Lai; Edward L. Giovannucci; Michael N. Pollak; Sarah B. Peskoe; Meir J. Stampfer; Walter C. Willett; Elizabeth A. Platz (Cancer Causes & Control, 2014)

Controls on water balance of shallow thermokarst lakes and their relations with catchment characteristics: a multi‐year, landscape‐scale assessment based on water isotope tracers and remote sensing in Old Crow Flats, Yukon (Canada) - Kevin W. Turner; Brent B. Wolfe; Thomas W. D. Edwards; Trevor C. Lantz; Roland I. Hall; Guillaume Larocque (Global Change Biology, 2014)
Many northern lake‐rich regions are undergoing pronounced hydrological change, yet inadequate knowledge of the drivers of these landscape‐scale responses hampers our ability to predict future conditions. We address this challenge in the thermokarst landscape of Old Crow Flats ( OCF ) using a combination of remote sensing imagery and monitoring of stable isotope compositions of lake waters over three thaw seasons (2007–2009). Quantitative analysis confirmed that the hydrological behavior of lakes is strongly influenced by catchment vegetation and physiography. Catchments of snowmelt‐dominated lakes, typically located in southern peripheral areas of OCF , encompass high proportions of woodland/forest and tall shrub vegetation (mean percent land cover = ca. 60%). These land cover types effectively capture snow and generate abundant snowmelt runoff that offsets lake water evaporation. Rainfall‐dominated lakes that are not strongly influenced by evaporation are typically located in eastern and northern OCF where their catchments have higher proportions of dwarf shrub/herbaceous and sparse vegetation (ca. 45%), as well as surface water (ca. 20%). Evaporation‐dominated lakes, are located in the OCF interior where their catchments are distinguished by substantially higher lake area to catchment area ratios ( LA / CA = ca. 29%) compared to low evaporation‐influenced rainfall‐dominated (ca. 10%) and snowmelt‐dominated (ca. 4%) lakes. Lakes whose catchments contain >75% combined dwarf shrub/herbaceous vegetation and surface water are most susceptible to evaporative lake‐level drawdown, especially following periods of low precipitation. Findings indicate that multiple hydrological trajectories are probable in response to climate‐driven changes in precipitation amount and seasonality, vegetation composition, and thermokarst processes. These will likely include a shift to greater snowmelt influence in catchments experiencing expansion of tall shrubs, greater influence from evaporation in catchments having higher proportions of surface water, and an increase in the rate of thermokarst lake expansion and probability of drainage. Local observations suggest that some of these changes are already underway.

Current Challenges in Bioequivalence, Quality, and Novel Assessment Technologies for Topical Products - Avraham Yacobi; Vinod P. Shah; Edward D. Bashaw; Eva Benfeldt; Barbara Davit; Derek Ganes; Tapash Ghosh; Isadore Kanfer; Gerald B. Kasting; Lindsey Katz; Robert Lionberger; Guang Wei Lu; et al. (Pharmaceutical Research, 2014)

Spontaneous onset of complex regional pain syndrome Type I in a woman infected with Bartonella koehlerae - Cristina Pérez Vera; Ricardo G. Maggi; Christopher W. Woods; Patricia E. Mascarelli; Edward B. Breitschwerdt (Medical Microbiology and Immunology, 2014)

Comparative microbiological features of Bartonella henselae infection in a dog with fever of unknown origin and granulomatous lymphadenitis - Amandine Drut; Isabelle Bublot; Edward B. Breitschwerdt; Luc Chabanne; Muriel Vayssier-Taussat; Jean-Luc Cadoré (Medical Microbiology and Immunology, 2014)

A multi‐genome analysis approach enables tracking of the invasion of a single R ussian wheat aphid ( D iuraphis noxia ) clone throughout the N ew W orld - B. Zhang; O. Edwards; L. Kang; S. Fuller (Molecular Ecology, 2014)
This study investigated the population genetics, demographic history and pathway of invasion of the Russian wheat aphid ( RWA ) from its native range in Central Asia, the Middle East and Europe to South Africa and the Americas. We screened microsatellite markers, mitochondrial DNA and endosymbiont genes in 504 RWA clones from nineteen populations worldwide. Following pathway analyses of microsatellite and endosymbiont data, we postulate that Turkey and Syria were the most likely sources of invasion to Kenya and South Africa, respectively. Furthermore, we found that one clone transferred between South Africa and the Americas was most likely responsible for the New World invasion. Finally, endosymbiont DNA was found to be a high‐resolution population genetic marker, extremely useful for studies of invasion over a relatively short evolutionary history time frame. This study has provided valuable insights into the factors that may have facilitated the recent global invasion by this damaging pest.

Animal Models for Depression Associated with HIV-1 Infection - Isabella Cristina Gomes Barreto; Patricia Viegas; Edward B. Ziff; Elisabete Castelon Konkiewitz (Journal of Neuroimmune Pharmacology, 2014)

The global contribution of forage fish to marine fisheries and ecosystems - Ellen K Pikitch; Konstantine J Rountos; Timothy E Essington; Christine Santora; Daniel Pauly; Reg Watson; Ussif R Sumaila; P Dee Boersma; Ian L Boyd; David O Conover; Philippe Cury; Selina S Heppell; et al. (Fish and Fisheries, 2014)
Forage fish play a pivotal role in marine ecosystems and economies worldwide by sustaining many predators and fisheries directly and indirectly. We estimate global forage fish contributions to marine ecosystems through a synthesis of 72 published E copath models from around the world. Three distinct contributions of forage fish were examined: (i) the ecological support service of forage fish to predators in marine ecosystems, (ii) the total catch and value of forage fisheries and (iii) the support service of forage fish to the catch and value of other commercially targeted predators. Forage fish use and value varied and exhibited patterns across latitudes and ecosystem types. Forage fish supported many kinds of predators, including fish, seabirds, marine mammals and squid. Overall, forage fish contribute a total of about $16.9 billion USD to global fisheries values annually, i.e. 20% of the global ex‐vessel catch values of all marine fisheries combined. While the global catch value of forage fisheries was $5.6 billion, fisheries supported by forage fish were more than twice as valuable ($11.3 billion). These estimates provide important information for evaluating the trade‐offs of various uses of forage fish across ecosystem types, latitudes and globally. We did not estimate a monetary value for supportive contributions of forage fish to recreational fisheries or to uses unrelated to fisheries, and thus the estimates of economic value reported herein understate the global value of forage fishes.

Interactions among resource partitioning, sampling effect, and facilitation on the biodiversity effect: a modeling approach - Pedro Flombaum; Osvaldo E. Sala; Edward B. Rastetter (Oecologia, 2014)

Syncoilin is an intermediate filament protein in activated hepatic stellate cells - E. Rossen; Z. Liu; D. Blijweert; N. Eysackers; I. Mannaerts; B. Schroyen; A. El Taghdouini; B. Edwards; K. E. Davies; E. Sokal; M. Najimi; H. Reynaert; et al. (Histochemistry and Cell Biology, 2014)

Multi‐decadal range changes vs. thermal adaptation for north east Atlantic oceanic copepods in the face of climate change - Stephanie L. Hinder; Mike B. Gravenor; Martin Edwards; Clare Ostle; Owen G. Bodger; Patricia L. M. Lee; Antony W. Walne; Graeme C. Hays (Global Change Biology, 2014)
Populations may potentially respond to climate change in various ways including moving to new areas or alternatively staying where they are and adapting as conditions shift. Traditional laboratory and mesocosm experiments last days to weeks and thus only give a limited picture of thermal adaptation, whereas ocean warming occurring over decades allows the potential for selection of new strains better adapted to warmer conditions. Evidence for adaptation in natural systems is equivocal. We used a 50‐year time series comprising of 117 056 samples in the NE Atlantic, to quantify the abundance and distribution of two particularly important and abundant members of the ocean plankton (copepods of the genus Calanus ) that play a key trophic role for fisheries. Abundance of C. finmarchicus , a cold‐water species, and C. helgolandicus , a warm‐water species, were negatively and positively related to sea surface temperature ( SST ) respectively. However, the abundance vs. SST relationships for neither species changed over time in a manner consistent with thermal adaptation. Accompanying the lack of evidence for thermal adaptation there has been an unabated range contraction for C. finmarchicus and range expansion for C. helgolandicus . Our evidence suggests that thermal adaptation has not mitigated the impacts of ocean warming for dramatic range changes of these key species and points to continued dramatic climate induced changes in the biology of the oceans.

Nitrogen dynamics in arctic tundra soils of varying age: differential responses to fertilization and warming - Yuriko Yano; Gaius R. Shaver; Edward B. Rastetter; Anne E. Giblin; James A. Laundre (Oecologia, 2013)

Brain responses to erotic and other emotional stimuli in breast cancer survivors with and without distress about low sexual desire: a preliminary fMRI study - Francesco Versace; Jeffrey M. Engelmann; Edward F. Jackson; Aurelija Slapin; Kristin M. Cortese; Therese B. Bevers; Leslie R. Schover (Brain Imaging and Behavior, 2013)

Older individuals with HIV infection have greater memory deficits than younger individuals - I. Lin Tan; B. R. Smith; Edward Hammond; Heidi Vornbrock-Roosa; Jason Creighton; O. Selnes; Justin C. McArthur; Ned Sacktor (Journal of NeuroVirology, 2013)

The effect of microhabitat feeding site selection on aphid foraging and predation risk - Carl N. Keiser; Lauren E. Sheeks; Edward B. Mondor (Arthropod-Plant Interactions, 2013)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

Sodium Acetate as a Replacement for Sodium Bicarbonate in Medical Toxicology: a Review - Mark J. Neavyn; Edward W. Boyer; Steven B. Bird; Kavita M. Babu (Journal of Medical Toxicology, 2013)

A Bayesian framework for stable isotope mixing models - Erik B. Erhardt; Edward J. Bedrick (Environmental and Ecological Statistics, 2013)

A de novo FLCN mutation in a patient with spontaneous pneumothorax and renal cancer; a clinical and molecular evaluation - Fred H. Menko; Paul C. Johannesma; R. Jeroen A. van Moorselaar; Rinze Reinhard; Jan Hein van Waesberghe; Erik Thunnissen; Arjan C. Houweling; Edward M. Leter; Quinten Waisfisz; Martijn B. van Doorn; Theo M. Starink; Pieter E. Postmus; et al. (Familial Cancer, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Transgenerational Behavioral Plasticity in a Parthenogenetic Insect in Response to Increased Predation Risk - Carl N. Keiser; Edward B. Mondor (Journal of Insect Behavior, 2013)

Anthropometric factors in relation to risk of glioma - Rebecca B. Little; Melissa H. Madden; Reid C. Thompson; Jeffrey J. Olson; Renato V. LaRocca; Edward Pan; James E. Browning; Kathleen M. Egan; L. Burton Nabors (Cancer Causes & Control, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Soil warming increases plant species richness but decreases germination from the alpine soil seed bank - Gemma L. Hoyle; Susanna E. Venn; Kathryn J. Steadman; Roger B. Good; Edward J. McAuliffe; Emlyn R. Williams; Adrienne B. Nicotra (Global Change Biology, 2013)
Global warming is occurring more rapidly above the treeline than at lower elevations and alpine areas are predicted to experience above average warming in the future. Temperature is a primary factor in stimulating seed germination and regulating changes in seed dormancy status. Thus, plant regeneration from seed will be crucial to the persistence, migration and post disturbance recruitment of alpine plants in future climates. Here, we present the first assessment of the impact of soil warming on germination from the persistent alpine soil seed bank. Contrary to expectations, soil warming lead to reduced overall germination from the soil seed bank. However, germination response to soil temperature was species specific such that total species richness actually increased by nine with soil warming. We further explored the system by assessing the prevalence of seed dormancy and germination response to soil disturbance, the frequency of which is predicted to increase under climate change. Seeds of a significant proportion of species demonstrated physiological dormancy mechanisms and germination of several species appeared to be intrinsically linked to soil disturbance. In addition, we found no evidence of subalpine species and little evidence of exotic weed species in the soil, suggesting that the soil seed bank will not facilitate their invasion of the alpine zone. In conclusion, changes in recruitment via the alpine soil seed bank can be expected under climate change, as a result of altered dormancy alleviation and germination cues. Furthermore, the alpine soil seed bank, and the species richness therein, has the potential to help maintain local species diversity, support species range shift and moderate species dominance. Implications for alpine management and areas for further study are also discussed.

Infection of human brain vascular pericytes (HBVPs) by Bartonella henselae - Mrudula Varanat; Ricardo G. Maggi; Keith E. Linder; Edward B. Breitschwerdt (Medical Microbiology and Immunology, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Serum 25-hydroxyvitamin D and breast cancer in the military: a case–control study utilizing pre-diagnostic serum - Sharif B. Mohr; Edward D. Gorham; John E. Alcaraz; Christopher I. Kane; Caroline A. Macera; J. Kellogg Parsons; Deborah L. Wingard; Ronald Horst; Cedric F. Garland (Cancer Causes & Control, 2013)

Building the niche through time: using 13,000 years of data to predict the effects of climate change on three tree species in Europe - L. Maiorano; R. Cheddadi; N. E. Zimmermann; L. Pellissier; B. Petitpierre; J. Pottier; H. Laborde; B. I. Hurdu; P. B. Pearman; A. Psomas; J. S. Singarayer; O. Broennimann; et al. (Global Ecology and Biogeography, 2013)
Aim Species distribution models (SDMs) based on current species ranges underestimate the potential distribution when projected in time and/or space. A multi‐temporal model calibration approach has been suggested as an alternative, and we evaluate this using 13,000 years of data. Location Europe. Methods We used fossil‐based records of presence for Picea abies , Abies alba and Fagus sylvatica and six climatic variables for the period 13,000 to 1000 yr bp . To measure the contribution of each 1000‐year time step to the total niche of each species (the niche measured by pooling all the data), we employed a principal components analysis (PCA) calibrated with data over the entire range of possible climates. Then we projected both the total niche and the partial niches from single time frames into the PCA space, and tested if the partial niches were more similar to the total niche than random. Using an ensemble forecasting approach, we calibrated SDMs for each time frame and for the pooled database. We projected each model to current climate and evaluated the results against current pollen data. We also projected all models into the future. Results Niche similarity between the partial and the total‐SDMs was almost always statistically significant and increased through time. SDMs calibrated from single time frames gave different results when projected to current climate, providing evidence of a change in the species realized niches through time. Moreover, they predicted limited climate suitability when compared with the total‐SDMs. The same results were obtained when projected to future climates. Main conclusions The realized climatic niche of species differed for current and future climates when SDMs were calibrated considering different past climates. Building the niche as an ensemble through time represents a way forward to a better understanding of a species' range and its ecology in a changing climate.

Factors modulating cottongrass seedling growth stimulation to enhanced nitrogen and carbon dioxide: compensatory tradeoffs in leaf dynamics and allocation to meet potassium-limited growth - Andy Siegenthaler; Alexandre Buttler; Philippe Grosvernier; Jean-Michel Gobat; Mats B. Nilsson; Edward A. D. Mitchell (Oecologia, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Environmental Lithium Exposure in the North of Chile—II. Natural Food Sources - Leonardo T. Figueroa; Blago Razmillic; Oscar Zumeata; G. Nina Aranda; Sara Ann Barton; William J. Schull; Allan H. Young; Yumi M. Kamiya; John A Hoskins; Edward B. Ilgren (Biological Trace Element Research, 2013)

Effects of mu opioid receptor antagonism on cognition in obese binge-eating individuals - Samuel R. Chamberlain; Karin Mogg; Brendan P. Bradley; Annelize Koch; Chris M. Dodds; Wenli X. Tao; Kay Maltby; Bhopinder Sarai; Antonella Napolitano; Duncan B. Richards; Edward T. Bullmore; Pradeep J. Nathan (Psychopharmacology, 2012)

Resistance to Aphids, Late Blight and Viruses in Somatic Fusions and Crosses of Solanum tuberosum L. and Solanum bulbocastanum Dun - Jeffrey A. Davis; Edward B. Radcliffe; Christian A. Thill; David W. Ragsdale (American Journal of Potato Research, 2012)

Temperature-Dependent Clustering Behavior of Aethina Tumida Murray in Apis Mellifera L. Colonies - Edward B. Atkinson; James D. Ellis (Journal of Insect Behavior, 2012)

The influence of spatial working memory on ipsilateral remembered proprioceptive matching in adults with cerebral palsy - Daniel J. Goble; Micah B. Aaron; Seth Warschausky; Jacqueline N. Kaufman; Edward A. Hurvitz (Experimental Brain Research, 2012)

Impairment of antioxidant defenses as a contributor to arsenite-induced cell transformation - Jing Wu; Anna Sowinska; Xi Huang; Catherine B. Klein; Edward Pelle; Krystyna Frenkel (BioMetals, 2012)

Carbon outcomes of major land‐cover transitions in SE Asia: great uncertainties and REDD + policy implications - Alan D. Ziegler; Jacob Phelps; Jia QI Yuen; Edward L. Webb; Deborah Lawrence; Jeff M. Fox; Thilde B. Bruun; Stephen J. Leisz; Casey M. Ryan; Wolfram Dressler; Ole Mertz; Unai Pascual; et al. (Global Change Biology, 2012)
Policy makers across the tropics propose that carbon finance could provide incentives for forest frontier communities to transition away from swidden agriculture (slash‐and‐burn or shifting cultivation) to other systems that potentially reduce emissions and/or increase carbon sequestration. However, there is little certainty regarding the carbon outcomes of many key land‐use transitions at the center of current policy debates. Our meta‐analysis of over 250 studies reporting above‐ and below‐ground carbon estimates for different land‐use types indicates great uncertainty in the net total ecosystem carbon changes that can be expected from many transitions, including the replacement of various types of swidden agriculture with oil palm, rubber, or some other types of agroforestry systems. These transitions are underway throughout Southeast Asia, and are at the heart of REDD + debates. Exceptions of unambiguous carbon outcomes are the abandonment of any type of agriculture to allow forest regeneration (a certain positive carbon outcome) and expansion of agriculture into mature forest (a certain negative carbon outcome). With respect to swiddening, our meta‐analysis supports a reassessment of policies that encourage land‐cover conversion away from these [especially long‐fallow] systems to other more cash‐crop‐oriented systems producing ambiguous carbon stock changes – including oil palm and rubber. In some instances, lengthening fallow periods of an existing swidden system may produce substantial carbon benefits, as would conversion from intensely cultivated lands to high‐biomass plantations and some other types of agroforestry. More field studies are needed to provide better data of above‐ and below‐ground carbon stocks before informed recommendations or policy decisions can be made regarding which land‐use regimes optimize or increase carbon sequestration. As some transitions may negatively impact other ecosystem services, food security, and local livelihoods, the entire carbon and noncarbon benefit stream should also be taken into account before prescribing transitions with ambiguous carbon benefits.

Incident radiation and the allocation of nitrogen within A rctic plant canopies: implications for predicting gross primary productivity - Lorna E. Street; Gaius R. Shaver; Edward B. Rastetter; Mark T. van Wijk; Brooke A. Kaye; Mathew Williams (Global Change Biology, 2012)
Arctic vegetation is characterized by high spatial variability in plant functional type ( PFT ) composition and gross primary productivity ( P ). Despite this variability, the two main drivers of P in sub‐ A rctic tundra are leaf area index ( L T ) and total foliar nitrogen ( N T ). L T and N T have been shown to be tightly coupled across PFT s in sub‐Arctic tundra vegetation, which simplifies up‐scaling by allowing quantification of the main drivers of P from remotely sensed L T . Our objective was to test the L T – N T relationship across multiple Arctic latitudes and to assess L T as a predictor of P for the pan‐ A rctic. Including PFT ‐specific parameters in models of L T – N T coupling provided only incremental improvements in model fit, but significant improvements were gained from including site‐specific parameters. The degree of curvature in the L T – N T relationship, controlled by a fitted canopy nitrogen extinction co‐efficient, was negatively related to average levels of diffuse radiation at a site. This is consistent with theoretical predictions of more uniform vertical canopy N distributions under diffuse light conditions. Higher latitude sites had higher average leaf N content by mass ( N M ), and we show for the first time that L T – N T coupling is achieved across latitudes via canopy‐scale trade‐offs between N M and leaf mass per unit leaf area ( L M ). Site‐specific parameters provided small but significant improvements in models of P based on L T and moss cover. Our results suggest that differences in L T – N T coupling between sites could be used to improve pan‐Arctic models of P and we provide unique evidence that prevailing radiation conditions can significantly affect N allocation over regional scales.

Bartonella vinsonii subsp. berkhoffii and Bartonella henselae as potential causes of proliferative vascular diseases in animals - Christiane Beerlage; Mrudula Varanat; Keith Linder; Ricardo G. Maggi; Jim Cooley; Volkhard A. J. Kempf; Edward B. Breitschwerdt (Medical Microbiology and Immunology, 2012)

Quantification of the relationship between the environment and Fusarium head blight, Fusarium pathogen density, and mycotoxins in winter wheat in Europe - Alissa B. Kriss; Pierce A. Paul; Xiangming Xu; Paul Nicholson; Fiona M. Doohan; Laszlo Hornok; Alberto Rietini; Simon G. Edwards; Laurence V. Madden (European Journal of Plant Pathology, 2012)

The effect of experimental warming and precipitation change on proteolytic enzyme activity: positive feedbacks to nitrogen availability are not universal - Edward R. Brzostek; John M. Blair; Jeffrey S. Dukes; Serita D. Frey; Sarah E. Hobbie; Jerry M. Melillo; Robert J. Mitchell; Elise Pendall; Peter B. Reich; Gaius R. Shaver; Artur Stefanski; Mark G. Tjoelker; et al. (Global Change Biology, 2012)
Nitrogen regulates the E arth's climate system by constraining the terrestrial sink for atmospheric CO 2 . Proteolytic enzymes are a principal driver of the within‐system cycle of soil nitrogen, yet there is little to no understanding of their response to climate change. Here, we use a single methodology to investigate potential proteolytic enzyme activity in soils from 16 global change experiments. We show that regardless of geographical location or experimental manipulation (i.e., temperature, precipitation, or both), all sites plotted along a single line relating the response ratio of potential proteolytic activity to soil moisture deficit, the difference between precipitation and evapotranspiration. In particular, warming and reductions in precipitation stimulated potential proteolytic activity in mesic sites – temperate and boreal forests, arctic tundra – whereas these manipulations suppressed potential activity in dry grasslands. This study provides a foundation for a simple representation of the impacts of climate change on a central component of the nitrogen cycle.

Immunocytochemical localization of short-chain family reductases involved in menthol biosynthesis in peppermint - Glenn W. Turner; Edward M. Davis; Rodney B. Croteau (Planta, 2012)

A dietary pattern that is associated with C-peptide and risk of colorectal cancer in women - Teresa T. Fung; Frank B. Hu; Matthias Schulze; Michael Pollak; Tianying Wu; Charles S. Fuchs; Edward Giovannucci (Cancer Causes & Control, 2012)

Examining the effects of former cannabis use on cerebellum-dependent eyeblink conditioning in humans - Adam B. Steinmetz; Chad R. Edwards; Jennifer M. Vollmer; Molly A. Erickson; Brian F. O’Donnell; William P. Hetrick; Patrick D. Skosnik (Psychopharmacology, 2012)

(2-Methoxyethoxy)acetic acid: a urinary biomarker of exposure for jet fuel JP-8 - Clayton B’Hymer; Patricia Mathias; Edward Krieg; Kenneth L. Cheever; Christine A. Toennis; John C. Clark; James S. Kesner; Roger L. Gibson; Mary Ann Butler (International Archives of Occupational and Environmental Health, 2012)

Linear and angular control of circular walking in healthy older adults and subjects with cerebellar ataxia - Adam D. Goodworth; Caroline Paquette; Geoffrey Melvill Jones; Edward W. Block; William A. Fletcher; Bin Hu; Fay B. Horak (Experimental Brain Research, 2012)

Russian wheat aphids ( Diuraphis noxia ) in China: native range expansion or recent introduction? - B. ZHANG; O. R. EDWARDS; L. KANG; S. J. FULLER (Molecular Ecology, 2012)
In this study, we explore the population genetics of the Russian wheat aphid (RWA) ( Diuraphis noxia ), one of the world’s most invasive agricultural pests, in north‐western China. We have analysed the data of 10 microsatellite loci and mitochondrial sequences from 27 populations sampled over 2 years in China. The results confirm that the RWAs are holocyclic in China with high genetic diversity indicating widespread sexual reproduction. Distinct differences in microsatellite genetic diversity and distribution revealed clear geographic isolation between RWA populations in northern and southern Xinjiang, China, with gene flow interrupted across extensive desert regions. Despite frequent grain transportation from north to south in this region, little evidence for RWA translocation as a result of human agricultural activities was found. Consequently, frequent gene flow among northern populations most likely resulted from natural dispersal, potentially facilitated by wind currents. We also found evidence for the long‐term existence and expansion of RWAs in China, despite local opinion that it is an exotic species only present in China since 1975. Our estimated date of RWA expansion throughout China coincides with the debut of wheat domestication and cultivation practices in western Asia in the Holocene. We conclude that western China represents the limit of the far eastern native range of this species. This study is the most comprehensive molecular genetic investigation of the RWA in its native range undertaken to date and provides valuable insights into the history of the association of this aphid with domesticated cereals and wild grasses.

Frontogenesis and Frontal Progression of a Trapping-Generated Estuarine Convergence Front and Its Influence on Mixing and Stratification - Sarah N. Giddings; Derek A. Fong; Stephen G. Monismith; C. Chris Chickadel; Kathleen A. Edwards; William J. Plant; Bing Wang; Oliver B. Fringer; Alexander R. Horner-Devine; Andrew T. Jessup (Estuaries and Coasts, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Two-Photon and Second Harmonic Microscopy in Clinical and Translational Cancer Research - Seth W. Perry; Ryan M. Burke; Edward B. Brown (Annals of Biomedical Engineering, 2012)

All Clone-mates are not Created Equal: Fitness Discounting Theory Predicts Pea Aphid Colony Structure - Keely M. Duff; Edward B. Mondor (Journal of Insect Behavior, 2012)

Migratory flyway and geographical distance are barriers to the gene flow of influenza virus among North American birds - Tommy Tsan‐Yuk Lam; Hon S. Ip; Elodie Ghedin; David E. Wentworth; Rebecca A. Halpin; Timothy B. Stockwell; David J. Spiro; Robert J. Dusek; James B. Bortner; Jenny Hoskins; Bradley D. Bales; Dan R. Yparraguirre; et al. (Ecology Letters, 2012)
Ecology Letters (2011) 14 : 24–33 Abstract Despite the importance of migratory birds in the ecology and evolution of avian influenza virus (AIV), there is a lack of information on the patterns of AIV spread at the intra‐continental scale. We applied a variety of statistical phylogeographic techniques to a plethora of viral genome sequence data to determine the strength, pattern and determinants of gene flow in AIV sampled from wild birds in North America. These analyses revealed a clear isolation‐by‐distance of AIV among sampling localities. In addition, we show that phylogeographic models incorporating information on the avian flyway of sampling proved a better fit to the observed sequence data than those specifying homogeneous or random rates of gene flow among localities. In sum, these data strongly suggest that the intra‐continental spread of AIV by migratory birds is subject to major ecological barriers, including spatial distance and avian flyway.

Wetlands as natural assets - Edward B. Barbier (Hydrological Sciences Journal, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Advances in winter pulse pathology research in Australia - Moin U. Salam; Jennifer A. Davidson; Geoff J. Thomas; Rebecca Ford; Roger A. C. Jones; Kurt D. Lindbeck; William J. MacLeod; Rohan B. E. Kimber; Jean Galloway; Nitin Mantri; Joop A. G. van Leur; Brenda A. Coutts; et al. (Australasian Plant Pathology, 2011)

Resistance to the Translation Initiation Inhibitor Silvestrol is Mediated by ABCB1/P-Glycoprotein Overexpression in Acute Lymphoblastic Leukemia Cells - Sneha V. Gupta; Ellen J. Sass; Melanie E. Davis; Ryan B. Edwards; Gerard Lozanski; Nyla A. Heerema; Amy Lehman; Xiaoli Zhang; David Jarjoura; John C. Byrd; Li Pan; Kenneth K. Chan; et al. (The AAPS Journal, 2011)

Recognizing Contemporary Roles of Swidden Agriculture in Transforming Landscapes of Southeast Asia - ALAN D. ZIEGLER; JEFF M. FOX; EDWARD L. WEBB; CHRISTINE PADOCH; STEVE J. LEISZ; ROB A. CRAMB; OLE MERTZ; THILDE B. BRUUN; TRAN DUC VIEN (Conservation Biology, 2011)

High frequency variability of the Atlantic meridional overturning circulation - B. Balan Sarojini; J. M. Gregory; R. Tailleux; G. R. Bigg; A. T. Blaker; D. R. Cameron; N. R. Edwards; A. P. Megann; L. C. Shaffrey; B. Sinha (Ocean Science, 2011)
We compare the variability of the Atlantic meridional overturning circulation (AMOC) as simulated by the coupled climate models of the RAPID project, which cover a wide range of resolution and complexity, and observed by the RAPID/MOCHA array at about 26° N. We analyse variability on a range of timescales, from five-daily to interannual. In models of all resolutions there is substantial variability on timescales of a few days; in most AOGCMs the amplitude of the variability is of somewhat larger magnitude than that observed by the RAPID array, while the time-mean is within about 10 % of the observational estimate. The amplitude of the simulated annual cycle is similar to observations, but the shape of the annual cycle shows a spread among the models. A dynamical decomposition shows that in the models, as in observations, the AMOC is predominantly geostrophic (driven by pressure and sea-level gradients), with both geostrophic and Ekman contributions to variability, the latter being exaggerated and the former underrepresented in models. Other ageostrophic terms, neglected in the observational estimate, are small but not negligible. The time-mean of the western boundary current near the latitude of the RAPID/MOCHA array has a much wider model spread than the AMOC does, indicating large differences among models in the simulation of the wind-driven gyre circulation, and its variability is unrealistically small in the models. In many RAPID models and in models of the Coupled Model Intercomparison Project Phase 3 (CMIP3), interannual variability of the maximum of the AMOC wherever it lies, which is a commonly used model index, is similar to interannual variability in the AMOC at 26° N. Annual volume and heat transport timeseries at the same latitude are well-correlated within 15–45° N, indicating the climatic importance of the AMOC. In the RAPID and CMIP3 models, we show that the AMOC is correlated over considerable distances in latitude, but not the whole extent of the North Atlantic; consequently interannual variability of the AMOC at 50° N, where it is particularly relevant to European climate, is not well-correlated with that of the AMOC at 26° N, where it is monitored by the RAPID/MOCHA array.

The Mid‐Brunhes Event and West Antarctic ice sheet stability - P. B. Holden; N. R. Edwards; E. W. Wolff; P. J. Valdes; J. S. Singarayer (Journal of Quaternary Science, 2011)
The complex cyclical nature of Pleistocene climate, driven by the evolving orbital configuration of the Earth, is well known but not well understood. A major climatic transition took place at the Mid‐Brunhes Event (MBE), ca. 430 ka ago after which the amplitude of the ca.100 ka climate oscillations increased, with substantially warmer interglacials, including periods warmer than present. Recent modelling has indicated that while the timing of these warmer‐than‐present transient (WPT) events is consistent with southern warming due to a deglaciation‐forced slowdown of the Atlantic Meridional Overturning Circulation, the magnitude of warming requires a local amplification, for which a candidate is the feedback of significant West Antarctic Ice Sheet (WAIS) retreat. We here extend this argument, based on the absence of WPTs in the early ice core record (450–800 ka ago), to hypothesize that the MBE could be a manifestation of decreased WAIS stability, triggered by ongoing subglacial erosion. Copyright © 2011 John Wiley & Sons, Ltd.

The present and future role of coastal wetland vegetation in protecting shorelines: answering recent challenges to the paradigm - Keryn B. Gedan; Matthew L. Kirwan; Eric Wolanski; Edward B. Barbier; Brian R. Silliman (Climatic Change, 2011)

Effects of age and composition of field-produced biofilms on oyster larval setting - Alaina H. Campbell; Donald W. Meritt; Rima B. Franklin; Edward L. Boone; Carol T. Nicely; Bonnie L. Brown (Biofouling, 2011)

Antioxidant phytochemicals in lettuce grown in high tunnels and open field - Myung-Min Oh; Edward E. Carey; C. B. Rajashekar (Horticulture, Environment, and Biotechnology, 2011)

A blended global snow product using visible, passive microwave and scatterometer satellite data - James L. Foster; Dorothy K. Hall; John B. Eylander; George A. Riggs; Son V. Nghiem; Marco Tedesco; Edward Kim; Paul M. Montesano; Richard E. J. Kelly; Kimberly A. Casey; Bhaskar Choudhury (International Journal of Remote Sensing, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Localization of AQP5 during development of the mouse submandibular salivary gland - Helga S. Larsen; Marit H. Aure; Sarah B. Peters; Melinda Larsen; Edward B. Messelt; Hilde Kanli Galtung (Journal of Molecular Histology, 2011)

Monitoring seasonal bat activity on a coastal barrier island in Maryland, USA - Joshua B. Johnson; J. Edward Gates; Nicolas P. Zegre (Environmental Monitoring and Assessment, 2011)

Interdecadal declines in flood frequency increase primary production in lakes of a northern river delta - SUZANNE McGOWAN; PETER R. LEAVITT; ROLAND I. HALL; BRENT B. WOLFE; THOMAS W. D. EDWARDS; TAMMY KARST‐RIDDOCH; SHEILA R. VARDY (Global Change Biology, 2011)
Human activities and climate change have greatly altered flooding regimes in many of the world's river deltas, but the impact of such changes remains poorly quantified on decadal to multidecadal timescales. This study identified the response of delta lake primary production (measured as the concentration of sedimentary pigments) to variations in flood frequency using spatial surveys and paleolimnological analyses of lakes in the Peace‐Athabasca Delta (PAD), Canada. Surveys of 61 lakes spanning a range of hydrological conditions showed that those lakes that received flood waters less frequently were associated with elevated algal production (surface sedimentary pigments) and, in some lakes, increased growth of emergent macrophytes and epiphytic diatoms. Paleolimnological analyses of five lakes corroborated the contemporary spatial survey results by showing that production of pigments from most algal groups increased during recent periods of lower flood frequency in the 20th century as determined from increases in cellulose‐inferred lake‐water oxygen isotope composition and plant macrofossils, but remained stable in a ‘reference’ basin. In general, past periods of elevated algal production coincided with the increased abundance of submerged macrophytes or emergent vegetation that provide habitat for attached algae. These results suggest that interdecadal declines in river discharge arising from increased aridity, hydrologic regulation or consumptive water use will cause long‐term increases in primary production and alter ecosystem processes (carbon sequestration, biological diversity) in aquatic delta ecosystems similar to the PAD where lakes become nutrient‐rich in the absence of flooding.

Coordinated approaches to quantify long‐term ecosystem dynamics in response to global change - YIQI LUO; JERRY MELILLO; SHULI NIU; CLAUS BEIER; JAMES S. CLARK; AIMÉE T. CLASSEN; ERIC DAVIDSON; JEFFREY S. DUKES; R. DAVE EVANS; CHRISTOPHER B. FIELD; CLAUDIA I. CZIMCZIK; MICHAEL KELLER; et al. (Global Change Biology, 2011)
Many serious ecosystem consequences of climate change will take decades or even centuries to emerge. Long‐term ecological responses to global change are strongly regulated by slow processes, such as changes in species composition, carbon dynamics in soil and by long‐lived plants, and accumulation of nutrient capitals. Understanding and predicting these processes require experiments on decadal time scales. But decadal experiments by themselves may not be adequate because many of the slow processes have characteristic time scales much longer than experiments can be maintained. This article promotes a coordinated approach that combines long‐term, large‐scale global change experiments with process studies and modeling. Long‐term global change manipulative experiments, especially in high‐priority ecosystems such as tropical forests and high‐latitude regions, are essential to maximize information gain concerning future states of the earth system. The long‐term experiments should be conducted in tandem with complementary process studies, such as those using model ecosystems, species replacements, laboratory incubations, isotope tracers, and greenhouse facilities. Models are essential to assimilate data from long‐term experiments and process studies together with information from long‐term observations, surveys, and space‐for‐time studies along environmental and biological gradients. Future research programs with coordinated long‐term experiments, process studies, and modeling have the potential to be the most effective strategy to gain the best information on long‐term ecosystem dynamics in response to global change.

Reserve design for uncertain responses of coral reefs to climate change - Peter J. Mumby; Ian A. Elliott; C. Mark Eakin; William Skirving; Claire B. Paris; Helen J. Edwards; Susana Enríquez; Roberto Iglesias‐Prieto; Laurent M. Cherubin; Jamie R. Stevens (Ecology Letters, 2011)
Ecology Letters (2011) 14: 132–140 Abstract Rising sea temperatures cause mass coral bleaching and threaten reefs worldwide. We show how maps of variations in thermal stress can be used to help manage reefs for climate change. We map proxies of chronic and acute thermal stress and develop evidence‐based hypotheses for the future response of corals to each stress regime. We then incorporate spatially realistic predictions of larval connectivity among reefs of the Bahamas and apply novel reserve design algorithms to create reserve networks for a changing climate. We show that scales of larval dispersal are large enough to connect reefs from desirable thermal stress regimes into a reserve network. Critically, we find that reserve designs differ according to the anticipated scope for phenotypic and genetic adaptation in corals, which remains uncertain. Attempts to provide a complete reserve design that hedged against different evolutionary outcomes achieved limited success, which emphasises the importance of considering the scope for adaptation explicitly. Nonetheless, 15% of reserve locations were selected under all evolutionary scenarios, making them a high priority for early designation. Our approach allows new insights into coral holobiont adaptation to be integrated directly into an adaptive approach to management.

Scaling an Instantaneous Model of Tundra NEE to the Arctic Landscape - Michael M. Loranty; Scott J. Goetz; Edward B. Rastetter; Adrian V. Rocha; Gaius R. Shaver; Elyn R. Humphreys; Peter M. Lafleur (Ecosystems, 2011)

The effects of salinity on photosynthesis and growth of the single-cell C4 species Bienertia sinuspersici (Chenopodiaceae) - Courtney P. Leisner; Asaph B. Cousins; Sascha Offermann; Thomas W. Okita; Gerald E. Edwards (Photosynthesis Research, 2010)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Slowed decomposition is biotically mediated in an ectomycorrhizal, tropical rain forest - Krista L. McGuire; Donald R. Zak; Ivan P. Edwards; Christopher B. Blackwood; Rima Upchurch (Oecologia, 2010)

Intakes of vitamins A, C, and E and use of multiple vitamin supplements and risk of colon cancer: a pooled analysis of prospective cohort studies - Yikyung Park; Donna Spiegelman; David J. Hunter; Demetrius Albanes; Leif Bergkvist; Julie E. Buring; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Lisa Harnack; Ikuko Kato; Vittorio Krogh; et al. (Cancer Causes & Control, 2010)

Pooled analyses of 13 prospective cohort studies on folate intake and colon cancer - Dong-Hyun Kim; Stephanie A. Smith-Warner; Donna Spiegelman; Shiaw-Shyuan Yaun; Graham A. Colditz; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Saxon Graham; Lisa Harnack; Eric J. Jacobs; Michael Leitzmann; et al. (Cancer Causes & Control, 2010)

A proposal to change existing virus species names to non-Latinized binomials - Marc H. V. Van Regenmortel; Donald S. Burke; Charles H. Calisher; Ralf G. Dietzgen; Claude M. Fauquet; Said A. Ghabrial; Peter B. Jahrling; Karl M. Johnson; Michael R. Holbrook; Marian C. Horzinek; Günther M. Keil; Jens H. Kuhn; et al. (Archives of Virology, 2010)

A probabilistic calibration of climate sensitivity and terrestrial carbon change in GENIE-1 - Philip B. Holden; N. R. Edwards; K. I. C. Oliver; T. M. Lenton; R. D. Wilkinson (Climate Dynamics, 2010)

Age independent and position-dependent alterations in motor unit activity of the biceps brachii - B. Harwood; D. L. Edwards; J. M. Jakobi (European Journal of Applied Physiology, 2010)

Mechanisms of failed apoptotic cell clearance by phagocyte subsets in cardiovascular disease - Edward B. Thorp (Apoptosis, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Massive Ethylene Glycol Ingestion Treated with Fomepizole Alone—A Viable Therapeutic Option - Jennie A. Buchanan; Mohammed Alhelail; Edward W. Cetaruk; Tammi H. Schaeffer; Robert B. Palmer; Ken Kulig; Jeffrey Brent (Journal of Medical Toxicology, 2010)

On scientists’ discomfort in fisheries advisory science: the example of simulation‐based fisheries management‐strategy evaluations - Sarah B M Kraak; Ciaran J Kelly; Edward A Codling; Emer Rogan (Fish and Fisheries, 2010)
Scientists feel discomfort when they are asked to create certainty, where none exists, for use as an alibi in policy‐making. Recently, the scientific literature has drawn attention to some pitfalls of simulation‐based fisheries management‐strategy evaluation (MSE). For example, while estimates concerning central tendencies of distributions of simulation outcomes are usually fairly robust because they are conditioned on ample data, estimates concerning the tails of distributions (such as the probability of falling below a critical biomass) are usually conditional on few data and thus often rely on assumptions that have no strong knowledge base. The clients of scientific advice, such as the European Commission, are embracing the mechanization of the evaluation of proposed Harvest Control Rules against the precautionary principle and management objectives. Where the fisheries management institutions aim for simple answers from the scientists, giving ‘green/red light’ to a proposed management strategy, the scientists are forced into a split position between satisfying the demands of their advisory role and living up to the standards of scientific rigour. We argue against the mechanization of scientific advice that aims to incorporate all relevant processes into one big model algorithm that, after construction, can be run without circumspection. We rather encourage that fisheries advice should be a dynamic process of expert judgement, incorporating separate parallel concurrent, lines of scientific evidence, from quantitative and qualitative modelling exercises and factual knowledge of the biology and the fishery dynamics. This process can be formalized to a certain degree and can easily accommodate stakeholder viewpoints.

Molecular keys unlock the mysteries of variable survival responses of blue crabs to hypoxia - Geoffrey W. Bell; David B. Eggleston; Edward J. Noga (Oecologia, 2010)

Historical and paleolimnological evidence for expansion of Lake Athabasca (Canada) during the Little Ice Age - R. Niloshini Sinnatamby; Yi Yi; Michael A. Sokal; Kenneth P. Clogg-Wright; Taro Asada; Sheila R. Vardy; Tammy L. Karst-Riddoch; William M. Last; John W. Johnston; Roland I. Hall; Brent B. Wolfe; Thomas W. D. Edwards (Journal of Paleolimnology, 2010)

The high value of logged tropical forests: lessons from northern Borneo - Nicholas J. Berry; Oliver L. Phillips; Simon L. Lewis; Jane K. Hill; David P. Edwards; Noel B. Tawatao; Norhayati Ahmad; David Magintan; Chey V. Khen; M. Maryati; Robert C. Ong; Keith C. Hamer (Biodiversity and Conservation, 2010)

Population synchrony of a native fish across three Laurentian Great Lakes: evaluating the effects of dispersal and climate - David B. Bunnell; Jean V. Adams; Owen T. Gorman; Charles P. Madenjian; Stephen C. Riley; Edward F. Roseman; Jeffrey S. Schaeffer (Oecologia, 2010)

Conserved synteny at the protein family level reveals genes underlying Shewanella species’ cold tolerance and predicts their novel phenotypes - Tatiana V. Karpinets; Anna Y. Obraztsova; Yanbing Wang; Denise D. Schmoyer; Guruprasad H. Kora; Byung H. Park; Margrethe H. Serres; Margaret F. Romine; Miriam L. Land; Terence B. Kothe; Jim K. Fredrickson; Kenneth H. Nealson; et al. (Functional & Integrative Genomics, 2010)

Estimating Uncertainty in Ecosystem Budget Calculations - Ruth D. Yanai; John J. Battles; Andrew D. Richardson; Corrie A. Blodgett; Dustin M. Wood; Edward B. Rastetter (Ecosystems, 2010)

Comparative genomics based on massive parallel transcriptome sequencing reveals patterns of substitution and selection across 10 bird species - AXEL KÜNSTNER; JOCHEN B. W. WOLF; NICLAS BACKSTRÖM; OSCEOLA WHITNEY; CHRISTOPHER N. BALAKRISHNAN; LAINY DAY; SCOTT V. EDWARDS; DANIEL E. JANES; BARNEY A. SCHLINGER; RICHARD K. WILSON; ERICH D. JARVIS; WESLEY C. WARREN; et al. (Molecular Ecology, 2010)
Next‐generation sequencing technology provides an attractive means to obtain large‐scale sequence data necessary for comparative genomic analysis. To analyse the patterns of mutation rate variation and selection intensity across the avian genome, we performed brain transcriptome sequencing using Roche 454 technology of 10 different non‐model avian species. Contigs from de novo assemblies were aligned to the two available avian reference genomes, chicken and zebra finch. In total, we identified 6499 different genes across all 10 species, with ∼1000 genes found in each full run per species. We found evidence for a higher mutation rate of the Z chromosome than of autosomes (male‐biased mutation) and a negative correlation between the neutral substitution rate ( d S ) and chromosome size. Analyses of the mean d N / d S ratio (ω) of genes across chromosomes supported the Hill–Robertson effect (the effect of selection at linked loci) and point at stochastic problems with ω as an independent measure of selection. Overall, this study demonstrates the usefulness of next‐generation sequencing for obtaining genomic resources for comparative genomic analysis of non‐model organisms.

Molecular identification of Na + –H + exchanger isoforms (NHE2) in the gills of the euryhaline teleost Fundulus heteroclitus - S. L. Edwards; J. C. Weakley; A. W. Diamanduros; J. B. Claiborne (Journal of Fish Biology, 2010)
In the current study, reverse‐transcription polymerase chain reaction (RT‐PCR) and rapid amplification of cDNA ends (RACE) PCR were used to clone full‐length putative Na + –H + exchanger isoforms (NHE2a) cDNA from the gills of Fundulus heteroclitus. The 2480 bp cDNA includes a coding region for a protein that shows a 57% amino acid homology to rabbit NHE2. These sequences allowed data mining of available fish genome data, which revealed at least three NHE2 subtypes in some teleost species.

Ecosystem Services as a Common Language for Coastal Ecosystem‐Based Management - ELISE F. GRANEK; STEPHEN POLASKY; CARRIE V. KAPPEL; DENISE J. REED; DAVID M. STOMS; EVAMARIA W. KOCH; CHRIS J. KENNEDY; LORI A. CRAMER; SALLY D. HACKER; EDWARD B. BARBIER; SHANKAR ASWANI; MARY RUCKELSHAUS; et al. (Conservation Biology, 2010)
Ecosystem‐based management is logistically and politically challenging because ecosystems are inherently complex and management decisions affect a multitude of groups. Coastal ecosystems, which lie at the interface between marine and terrestrial ecosystems and provide an array of ecosystem services to different groups, aptly illustrate these challenges. Successful ecosystem‐based management of coastal ecosystems requires incorporating scientific information and the knowledge and views of interested parties into the decision‐making process. Estimating the provision of ecosystem services under alternative management schemes offers a systematic way to incorporate biogeophysical and socioeconomic information and the views of individuals and groups in the policy and management process. Employing ecosystem services as a common language to improve the process of ecosystem‐based management presents both benefits and difficulties. Benefits include a transparent method for assessing trade‐offs associated with management alternatives, a common set of facts and common currency on which to base negotiations, and improved communication among groups with competing interests or differing worldviews. Yet challenges to this approach remain, including predicting how human interventions will affect ecosystems, how such changes will affect the provision of ecosystem services, and how changes in service provision will affect the welfare of different groups in society. In a case study from Puget Sound, Washington, we illustrate the potential of applying ecosystem services as a common language for ecosystem‐based management.

Infection and replication of Bartonella species within a tick cell line - Sarah A. Billeter; Pedro Paulo V. P. Diniz; James M. Battisti; Ulrike G. Munderloh; Edward B. Breitschwerdt; Michael G. Levy (Experimental and Applied Acarology, 2009)

Cognitive enhancing effects of ghrelin receptor agonists - Zeenat Atcha; Woei-Shin Chen; Agnes B. Ong; Fong-Kuan Wong; Aveline Neo; Edward R. Browne; Jason Witherington; Darrel J. Pemberton (Psychopharmacology, 2009)

CXCR4 and CXCL12 Expression is Increased in the Nigro-Striatal System of Parkinson’s Disease - Mika Shimoji; Fernando Pagan; Edward B. Healton; Italo Mocchetti (Neurotoxicity Research, 2009)

Linking stream and landscape trajectories in the southern Appalachians - Edward P. Gardiner; Andrew B. Sutherland; Rebecca J. Bixby; Mark C. Scott; Judy L. Meyer; Gene S. Helfman; E. Fred Benfield; Cathy M. Pringle; Paul V. Bolstad; David N. Wear (Environmental Monitoring and Assessment, 2009)

Uptake of Allochthonous Dissolved Organic Matter from Soil and Salmon in Coastal Temperate Rainforest Streams - Jason B. Fellman; Eran Hood; Richard T. Edwards; Jeremy B. Jones (Ecosystems, 2009)

Characterization of 22 microsatellite marker loci in the Madagascar rousette (Rousettus madagascariensis) - Andoniaina R. Andrianaivoarivelo; Gary D. Shore; Susie M. McGuire; Richard K. B. Jenkins; Olga Ramilijaona; Edward E. Louis; Rick A. Brenneman (Conservation Genetics, 2009)

Targetable HPMA Copolymer–Aminohexylgeldanamycin Conjugates for Prostate Cancer Therapy - Mark P. Borgman; Abhijit Ray; Rohit B. Kolhatkar; Edward A. Sausville; Angelika M. Burger; Hamidreza Ghandehari (Pharmaceutical Research, 2009)

Planter Skips and Impaired Stand Favors Potato Virus Y Spread in Potato - Jeffrey A. Davis; Edward B. Radcliffe; David W. Ragsdale (American Journal of Potato Research, 2009)

Effect of stocking on juvenile wood stiffness for three Eucalyptus species - Edward Warren; R. Geoff B. Smith; Luis Alejandro Apiolaza; John C. F. Walker (New Forests, 2009)

The effect of temperature on the coupling between phosphorus and growth in lacustrine bacterioplankton communities - Edward K. Hall; Andrew R. Dzialowski; Samuel M. Stoxen; James B. Cotner (Limnology and Oceanography, 2009)
Phosphorus (P) routinely limits microbial growth in freshwater ecosystems. The growth rate hypothesis (GRH) relates growth to biomass P content mechanistically through changes in ribosomal ribonucleic acid (rRNA). Although the GRH has been shown in cultured bacteria, less well understood is how GRH relationships are affected by interactions with environmental parameters such as temperature. To address this, we evaluated the relationship between bacterial biomass P, RNA: deoxyribonucleic acid (DNA) ratio, and growth rate in 47 northern temperate lakes. Although RNA:DNA ratio was positively correlated with bacterial biomass P : carbon (C), we found no correlation between growth rate and RNA:DNA or between growth rate and biomass P : C. There was, however, a significant effect of temperature on biomass P : C. We investigated the effect of temperature more directly using filter‐separated bacterial communities from two lakes during two seasons while experimentally manipulating temperature and resources. For the summer communities, bacterial production (BP) and biomass P were positively correlated, and the slope of that relationship increased with increasing temperature. In winter communities, BP and biomass P were again positively correlated; however, the slope of that relationship decreased with increasing temperature. The slope of the relationship between BP and biomass P is a metric of nutrient use efficiency and was strongly influenced by temperature. More importantly, bacterioplankton demonstrated seasonal acclimation or adaptation to in situ temperature, suggesting that studies evaluating multiple communities in time and space fail to find a clear relationship between temperature and bacterial metabolism because bacterial communities are locally adapted to in situ temperature.

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Regulating intensity using perceived exertion: effect of exercise duration - Jie Kang; Edward C. Chaloupka; Gregory B. Biren; M. Alysia Mastrangelo; Jay R. Hoffman (European Journal of Applied Physiology, 2009)

Assessing the extent and diversity of riparian ecosystems in Sonora, Mexico - Michael L. Scott; Pamela L. Nagler; Edward P. Glenn; Carlos Valdes-Casillas; Joseph A. Erker; Elizabeth W. Reynolds; Patrick B. Shafroth; Euduardo Gomez-Limon; Cory L. Jones (Biodiversity and Conservation, 2009)

Border Treatment to Reduce Insecticide Use in Seed Potato Production: Biological, Economic, and Managerial Analysis - Matthew W. Carroll; Edward B. Radcliffe; Ian V. MacRae; David W. Ragsdale; Kent D. Olson; Thaddee Badibanga (American Journal of Potato Research, 2009)

Lemur Diversity in Madagascar - Russell A. Mittermeier; Jörg U. Ganzhorn; William R. Konstant; Kenneth Glander; Ian Tattersall; Colin P. Groves; Anthony B. Rylands; Andreas Hapke; Jonah Ratsimbazafy; Mireya I. Mayor; Edward E. Louis; Yves Rumpler; et al. (International Journal of Primatology, 2008)

Reproduction in the sea pen Pennatula phosphorea (Anthozoa: Pennatulacea) from the west coast of Scotland - D. C. B. Edwards; C. G. Moore (Marine Biology, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Age- and sex-related differences in muscle activation for a discrete functional task - B. Harwood; D. L. Edwards; J. M. Jakobi (European Journal of Applied Physiology, 2008)

Relationship of predation potential to mortality of Calanus finmarchicus on Georges Bank, northwest Atlantic - Mark D. Ohman; Edward G. Durbin; Jeffrey A. Runge; Barbara K. Sullivan; David B. Field (Limnology and Oceanography, 2008)
Based on 29 cruises on Georges Bank between January and June, conducted as part of the U.S. Global Ocean Ecosystem Dynamics program, we describe seasonal and spatial variability of early life history mortality for the planktonic copepod Calanus finmarchicus and relate mortality to an index of predation potential from a suite of suspension‐feeding predators. Emphasis is placed on the earliest life history phase wherein peak mortality occurs. Instantaneous mortality rates for a combined egg‐through‐nauplius‐3 stage show a recurrent seasonal pattern of a modest elevation in January followed by a seasonal peak in May of all 5 study yr. Spatial differences exist in mortality rates, with a higher probability of mortality on the southern flank in winter and a pronounced seasonal maximum on the bank crest in May. Three hypotheses associated, respectively, with egg hatching success, advection, and invertebrate predation were evaluated to account for the seasonal and spatial mortality patterns. Variations in egg‐hatching success are inconsistent with the observed seasonal patterns of loss. Off‐bank advection, particularly on the southern flank, appears to be the dominant loss term in January. Apart from this winter period, egg mortality is associated with predation potential. Comparison of an index of daily rates of egg loss with an index of consumption rates of eggs by suspended hydroids, hydromedusae, and five species of planktonic copepods show general agreement between mortality and predation in both seasonal variation and spatial patterns. Of the predator taxa, late copepodid and adult C. finmarchicus , supplemented by planktonic hydroids, appear to have the largest quantitative predation effect.

Carbon allocation in boreal black spruce forests across regions varying in soil temperature and precipitation - JASON G. VOGEL; BEN P. BOND‐LAMBERTY; EDWARD A. G. SCHUUR; STITH T. GOWER; MICHELLE C. MACK; KARI E. B. O'CONNELL; DAVID W. VALENTINE; ROGER W. RUESS (Global Change Biology, 2008)
A common hypothesis for northern ecosystems is that low soil temperatures inhibit plant productivity. To address this hypothesis, we reviewed how separate components of ecosystem carbon (C) cycling varied along a soil temperature gradient for nine well‐drained, relatively productive boreal black spruce ( Picea mariana Mill. [B.S.P.]) forests in Alaska, USA, and Saskatchewan and Manitoba, Canada. Annual soil temperature [expressed as soil summed degree days (SDD)] was positively correlated with aboveground net primary productivity (ANPP), while negatively correlated with total belowground carbon flux (TBCF). The partitioning of C to ANPP at the expense of root processes represented a nearly 1 : 1 tradeoff across the soil temperature gradient, which implied that the amount of C cycling through these black spruce ecosystems was relatively insensitive to variation in SDD. Moreover, the rate at which C accumulated in the ecosystem since the last stand replacing fire was unrelated to SDD, but SDD was positively correlated to the ratio of spruce‐biomass : forest‐floor‐mass. Thus, plant partitioning of C and the distribution of ecosystem C were apparently affected by soil temperature, although across regions, precipitation co‐varied with soil temperature. These two factors likely correlated with one another because of precipitation's influence on soil heat balance, suggesting that a soil temperature–precipitation interaction could be responsible for the shifts in C allocation. Nonetheless, our results highlight that for this boreal ecosystem, ANPP and TBCF can be negatively correlated. In tropical and temperate forests, TBCF and ANPP have been reported as positively correlated, and our results may reflect the unique interactions between soil temperature, forest floor accumulation, rooting depth, and nutrient availability that characterize the black spruce forest type.

Distribution and activity of bats at local and landscape scales within a rural–urban gradient - Joshua B. Johnson; J. Edward Gates; W. Mark Ford (Urban Ecosystems, 2008)

Return of Salmon-Derived Nutrients from the Riparian Zone to the Stream during a Storm in Southeastern Alaska - Jason B. Fellman; Eran Hood; Rick T. Edwards; David V. D’Amore (Ecosystems, 2008)

Zoning of phosphorus in igneous olivine - Margaret S. Milman-Barris; John R. Beckett; Michael B. Baker; Amy E. Hofmann; Zachary Morgan; Meghan R. Crowley; Daniel Vielzeuf; Edward Stolper (Contributions to Mineralogy and Petrology, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Autumn migration and wintering of northern fulmars (Fulmarus glacialis) from the Canadian high Arctic - Mark L. Mallory; Jason A. Akearok; Darryl B. Edwards; Kieran O’Donovan; Cynthia D. Gilbert (Polar Biology, 2008)

Effects of nutrient and CO2 availability on tolerance to herbivory in Brassica rapa - Carolyn B. Marshall; Germán Avila-Sakar; Edward G. Reekie (Plant Ecology, 2008)

Standpunkte, Praktiken und Kenntnisstand zur Ferkelkastration in Europa (PIGCAS) – Projektziele und erste Ergebnisse - Eberhard von Borell; M. Oliver; B. Fredriksen; S. Edwards; M. Bonneau (Journal of Consumer Protection and Food Safety, 2008)

Prediction uncertainty of environmental change effects on temperate European biodiversity - Carsten F. Dormann; Oliver Schweiger; P. Arens; I. Augenstein; St. Aviron; Debra Bailey; J. Baudry; R. Billeter; R. Bugter; R. Bukácek; F. Burel; M. Cerny; et al. (Ecology Letters, 2008)
Observed patterns of species richness at landscape scale (gamma diversity) cannot always be attributed to a specific set of explanatory variables, but rather different alternative explanatory statistical models of similar quality may exist. Therefore predictions of the effects of environmental change (such as in climate or land cover) on biodiversity may differ considerably, depending on the chosen set of explanatory variables. Here we use multimodel prediction to evaluate effects of climate, land‐use intensity and landscape structure on species richness in each of seven groups of organisms (plants, birds, spiders, wild bees, ground beetles, true bugs and hoverflies) in temperate Europe. We contrast this approach with traditional best‐model predictions, which we show, using cross‐validation, to have inferior prediction accuracy. Multimodel inference changed the importance of some environmental variables in comparison with the best model, and accordingly gave deviating predictions for environmental change effects. Overall, prediction uncertainty for the multimodel approach was only slightly higher than that of the best model, and absolute changes in predicted species richness were also comparable. Richness predictions varied generally more for the impact of climate change than for land‐use change at the coarse scale of our study. Overall, our study indicates that the uncertainty introduced to environmental change predictions through uncertainty in model selection both qualitatively and quantitatively affects species richness projections.

Macroinvertebrate drift density in relation to abiotic factors in the Missouri River - Christopher H. Hay; Thomas G. Franti; David B. Marx; Edward J. Peters; Larry W. Hesse (Hydrobiologia, 2008)

Contrasting success in the restoration of plant and phytophagous beetle assemblages of species-rich mesotrophic grasslands - B. A. Woodcock; A. R. Edwards; C. S. Lawson; D. B. Westbury; A. J. Brook; S. J. Harris; V. K. Brown; S. R. Mortimer (Oecologia, 2008)

The influence of dissolved organic carbon on bacterial phosphorus uptake and bacteria‐phytoplankton dynamics in two Minnesota lakes - Edward G. Stets; James B. Cotner (Limnology and Oceanography, 2008)
The balance of production in any ecosystem is dependent on the flow of limiting nutrients into either the autotrophic or heterotrophic components of the food web. To understand one of the important controls on the flow of inorganic nutrients between phytoplankton and bacterioplankton in lakes, we manipulated dissolved organic carbon (DOC) in two lakes of different trophic status. We hypothesized that labile DOC additions would increase bacterial phosphorus (P) uptake and decrease the response of phytoplankton to nutrient additions. Supplemental nutrients and carbon (C), nitrogen (N, 1.6 µmol NH 4 Cl L −1 d −1 ), P (0.1 µmol KH 2 PO 4 L −1 d −1 ), and DOC (glucose, 15 µmol C L −1 d −1 ) were added twice daily to 8‐liter experimental units. We tested the effect of added DOC on chlorophyll concentration, bacterial production, biomass, and P uptake using size‐fractionated 33 P‐PO 4 uptake. In the oligotrophic lake, DOC additions stimulated bacterial production and increased bacterial biomass‐specific P uptake. Bacteria consumed added DOC, and chlorophyll concentrations were significantly lower in carboys receiving DOC additions. In the eutrophic lake, DOC additions had less of a stimulatory effect on bacterial production and biomass‐specific P uptake. DOC accumulated over the time period, and there was little evidence for a DOC‐induced decrease in phytoplankton biomass. Bacterial growth approached the calculated µ max and yet did not accumulate biomass, indicating significant biomass losses, which may have constrained bacterial DOC consumption. Excess bacterial DOC consumption in oligotrophic lakes may result in greater bacterial P affinity and enhanced nutrient uptake by the heterotrophic compartment of the food web. On the other hand, constraints on bacterial biomass accumulation in eutrophic lakes, from either viral lysis or bacterial grazing, can allow labile DOC to accumulate, thereby negating the effect of excess DOC on the planktonic food web.

Atlantic reef fish biogeography and evolution - S. R. Floeter; L. A. Rocha; D. R. Robertson; J. C. Joyeux; W. F. Smith‐Vaniz; P. Wirtz; A. J. Edwards; J. P. Barreiros; C. E. L. Ferreira; J. L. Gasparini; A. Brito; J. M. Falcón; et al. (Journal of Biogeography, 2008)
Aim To understand why and when areas of endemism (provinces) of the tropical Atlantic Ocean were formed, how they relate to each other, and what processes have contributed to faunal enrichment. Location Atlantic Ocean. Methods The distributions of 2605 species of reef fishes were compiled for 25 areas of the Atlantic and southern Africa. Maximum‐parsimony and distance analyses were employed to investigate biogeographical relationships among those areas. A collection of 26 phylogenies of various Atlantic reef fish taxa was used to assess patterns of origin and diversification relative to evolutionary scenarios based on spatio‐temporal sequences of species splitting produced by geological and palaeoceanographic events. We present data on faunal (species and genera) richness, endemism patterns, diversity buildup (i.e. speciation processes), and evaluate the operation of the main biogeographical barriers and/or filters. Results Phylogenetic (proportion of sister species) and distributional (number of shared species) patterns are generally concordant with recognized biogeographical provinces in the Atlantic. The highly uneven distribution of species in certain genera appears to be related to their origin, with highest species richness in areas with the greatest phylogenetic depth. Diversity buildup in Atlantic reef fishes involved (1) diversification within each province, (2) isolation as a result of biogeographical barriers, and (3) stochastic accretion by means of dispersal between provinces. The timing of divergence events is not concordant among taxonomic groups. The three soft (non‐terrestrial) inter‐regional barriers (mid‐Atlantic, Amazon, and Benguela) clearly act as ‘filters’ by restricting dispersal but at the same time allowing occasional crossings that apparently lead to the establishment of new populations and species. Fluctuations in the effectiveness of the filters, combined with ecological differences among provinces, apparently provide a mechanism for much of the recent diversification of reef fishes in the Atlantic. Main conclusions Our data set indicates that both historical events (e.g. Tethys closure) and relatively recent dispersal (with or without further speciation) have had a strong influence on Atlantic tropical marine biodiversity and have contributed to the biogeographical patterns we observe today; however, examples of the latter process outnumber those of the former.

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

History of mercury inputs to Minnesota lakes: Influences of watershed disturbance and localized atmospheric deposition - Daniel R. Engstrom; Steven J. Balogh; Edward B. Swain (Limnology and Oceanography, 2007)
The history of mercury (Hg) inputs to 55 Minnesota (U.S.A.) lakes was reconstructed from 210 Pb (lead‐210)‐ dated sediment cores to determine if erosion of soils from agriculture and urbanization contributes a significant loading of Hg to lakes, and whether lakes near Hg‐emitting facilities receive appreciable local atmospheric deposition. Modern (1994–1997) Hg accumulation and Hg flux ratios (modern : preindustrial) increase significantly with the percentage of watershed area under urban or agricultural land‐use. Both past and modern Hg accumulation rates are strongly correlated with the flux of total aluminum (Al), a tracer for soil erosion. Modern Hg accumulation rates are substantially higher in the Minneapolis‐St. Paul metropolitan area and in agriculturally dominated south‐central Minnesota than in the forested northeastern part of the state, largely because of erosional inputs of soil‐bound Hg from disturbed catchments. Modern Hg loading from direct atmospheric deposition is also greater in the metropolitan region than in the rural areas of south‐central or northeastern Minnesota. However, some of the excess loading to urban lakes may also be a legacy of formerly high Hg deposition to urban watersheds. A decline in local Hg emissions from peak levels in the 1970s coupled with reduced erosional inputs has cut Hg loading to many metro‐area lakes by more than half.

KILLER WHALES, WHALING, AND SEQUENTIAL MEGAFAUNAL COLLAPSE IN THE NORTH PACIFIC: A COMPARATIVE ANALYSIS OF THE DYNAMICS OF MARINE MAMMALS IN ALASKA AND BRITISH COLUMBIA FOLLOWING COMMERCIAL WHALING - Andrew W. Trites; Volker B. Deecke; Edward J. Gregr; John K.B. Ford; Peter F. Olesiuk (Marine Mammal Science, 2007)
The hypothesis that commercial whaling caused a sequential megafaunal collapse in the North Pacific Ocean by forcing killer whales to eat progressively smaller species of marine mammals is not supported by what is known about the biology of large whales, the ecology of killer whales, and the patterns of ecosystem change that took place in Alaska, British Columbia, and elsewhere in the world following whaling. A comparative analysis shows that populations of seals, sea lions, and sea otters increased in British Columbia following commercial whaling, unlike the declines noted in the Gulf of Alaska and Aleutian Islands. The declines of seals and sea lions that began in western Alaska around 1977 were mirrored by increases in numbers of these species in British Columbia. A more likely explanation is that the seal and sea lion declines and other ecosystem changes in Alaska stem from a major oceanic regime shift that occurred in 1977. Killer whales are unquestionably a significant predator of seals, sea lions, and sea otters—but not because of commercial whaling.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Do exaptations facilitate mutualistic associations between invasive and native species? - Edward B. Mondor; John F. Addicott (Biological Invasions, 2007)

Prescribed fire and cutting as tools for reducing woody plant succession in a created salt marsh - Alaina B. Owens; C. Edward Proffitt; James B. Grace (Wetlands Ecology and Management, 2007)

Invasive aphids attack native Hawaiian plants - Russell H. Messing; Michelle N. Tremblay; Edward B. Mondor; Robert G. Foottit; Keith S. Pike (Biological Invasions, 2007)

Psychiatric safety of ketamine in psychopharmacology research - Edward B. Perry; Joyce A. Cramer; Hyun-Sang Cho; Ismene L. Petrakis; Laurence P. Karper; Angelina Genovese; Elizabeth O’Donnell; John H. Krystal; D. Cyril D’Souza (Psychopharmacology, 2007)

Copper entry into human cells: progress and unanswered questions - Edward B. Maryon; Shannon A. Molloy; Adriana M. Zimnicka; Jack H. Kaplan (BioMetals, 2007)

Resistance to green peach aphid,Myzus persicae (Sulzer), and potato aphid,Macrosiphum euphorbiae (Thomas), in potato cultivars - Jeffrey A. Davis; Edward B. Radcliffe; David W. Ragsdale (American Journal of Potato Research, 2007)

Measuring RNA:DNA ratios in individual Acartia tonsa (Copepoda) - Christa L. Speekmann; B. Scott Nunez; Edward J. Buskey (Marine Biology, 2007)

Influence of environment and substrate quality on root decomposition in naturally regenerating and restored Atlantic white cedar wetlands - Edward R. Crawford; Frank P. Day; Robert B. Atkinson (Wetlands, 2007)

Complexation of oxoanions and cationic metals by the biscatecholate siderophore azotochelin - Jean-Philippe Bellenger; Françoise Arnaud-Neu; Zouhair Asfari; Satish C. B. Myneni; Edward I. Stiefel; Anne M. L. Kraepiel (JBIC Journal of Biological Inorganic Chemistry, 2007)

Spatio-temporal patterns in county-level incidence and reporting of Lyme disease in the northeastern United States, 1990–2000 - Lance A. Waller; Brett J. Goodwin; Mark L. Wilson; Richard S. Ostfeld; Stacie L. Marshall; Edward B. Hayes (Environmental and Ecological Statistics, 2007)

Progress in isotope paleohydrology using lake sediment cellulose - Brent B. Wolfe; Matthew D. Falcone; Ken P. Clogg-Wright; Cherie L. Mongeon; Yi Yi; Bronwyn E. Brock; Natalie A. St. Amour; William A. Mark; Thomas W. D. Edwards (Journal of Paleolimnology, 2007)

Improving Data Reliability Using a Non-Compliance Detection Method versus Using Pharmacokinetic Criteria - Smita A. Kshirsagar; Terrence F. Blaschke; Lewis B. Sheiner; M. Krygowski; Edward P. Acosta; Davide Verotta (Journal of Pharmacokinetics and Pharmacodynamics, 2007)

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Morphological and ecological traits promoting aphid colonization of the Hawaiian Islands - Edward B. Mondor; Michelle N. Tremblay; Russell H. Messing (Biological Invasions, 2006)

Diversity and expression of nitrogenase genes ( nifH ) from ectomycorrhizas of Corsican pine ( Pinus nigra ) - Hironari Izumi; Ian C. Anderson; Ian J. Alexander; Ken Killham; Edward R. B. Moore (Environmental Microbiology, 2006)
Summary The diversity of bacterial nitrogenase genes ( nifH ) and their mRNA transcription in ectomycorrhizas of Corsican pine ( Pinus nigra ) were examined. DNA and RNA were extracted from surface‐sterilized and non‐sterilized Corsican pine roots colonized by the ectomycorrhizal (ECM) fungi, Suillus variegatus and Tomentellopsis submollis . DNA‐derived nifH polymerase chain reaction (PCR) products were obtained from all samples, but only a few reverse transcription PCRs for nifH mRNA were successful, suggesting that nitrogenase genes were not always transcribed. Several different nifH sequences were detected and the bacteria actively transcribing nifH were different from those whose genes were detected through DNA‐based PCR. Putative nitrogenase amino acid sequences revealed that more than half of the nifH products were derived from methylotrophic bacteria, such as Methylocella spp. The next most frequent sequence types were similar to those from Burkholderia .

Greater vulnerability to the amnestic effects of ketamine in males - Celia J. A. Morgan; Edward B. Perry; Hyung-Sang Cho; John H. Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2006)

Nutritional status of four species of giant land snails in Nigeria - O. Fagbuaro; J. A. Oso; J. B. Edward; R. F. Ogunleye (Journal of Zhejiang University-SCIENCE B, 2006)

Specific Selection Pressure at the Third Codon Positions: Contribution to 10- to 11-Base Periodicity in Prokaryotic Genomes - Amir B. Cohanim; Edward N. Trifonov; Yechezkel Kashi (Journal of Molecular Evolution, 2006)

Temporal and spatial appearance of wall polysaccharides during cellularization of barley (Hordeum vulgare) endosperm - Sarah M. Wilson; Rachel A. Burton; Monika S. Doblin; Bruce A. Stone; Edward J. Newbigin; Geoffrey B. Fincher; Antony Bacic (Planta, 2006)

The Influence of Habitat Variables on Bird Communities in Forest Remnants in Costa Rica - Robert B. Matlock; Peter J. Edwards (Biodiversity and Conservation, 2006)

Empirical Bayes estimation of gene-specific effects in micro-array research - Jode W. Edwards; Grier P. Page; Gary Gadbury; Moonseong Heo; Tsuyoshi Kayo; Richard Weindruch; David B. Allison (Functional & Integrative Genomics, 2006)

Interactions between Widely Spaced Young Poplars (Populus spp.) and the Understorey Environment - G. B. Douglas; A. S. Walcroft; S. E. Hurst; J. F. Potter; A. G. Foote; L. E. Fung; W. R. N. Edwards; C. van den Dijssel (Agroforestry Systems, 2006)

Conservation Benefits of Temperate Marine Protected Areas: Variation among Fish Species - ROBERT E. BLYTH‐SKYRME; MICHEL J. KAISER; JAN G. HIDDINK; GARETH EDWARDS‐JONES; PAUL J. B. HART (Conservation Biology, 2006)
Marine protected areas, and other fishery management systems that impart partial or total protection from fishing, are increasingly advocated as an essential management tool to ensure the sustainable use of marine resources. Beneficial effects for fish species are well documented for tropical and reef systems, but the effects of marine protected areas remain largely untested in temperate waters. We compared trends in sport‐fishing catches of nine fish species in an area influenced by a large (500‐km 2 ) towed‐fishing‐gear restriction zone and in adjacent areas under conventional fishery management controls. Over the period 1973–2002 the mean reported weight of above‐average‐sized (trophy) fish of species with early age at maturity and limited home range was greatest within the area influenced by the fishing‐gear restriction zone. The reported weight of trophy fish of species that mature early also declined less and more slowly over time within the area influenced by the fishing‐gear restriction zone. Importantly, the mean reported weight of trophy fish of species that mature late and those that undertake extensive spatial movements declined at the same rate in all areas. Hence these species are likely to require protected areas >500 km 2 for effective protection. Our results also indicated that fish species with a localized distribution or high site fidelity may require additional protection from sport fishing to prevent declines in the number or size of fish within the local population.

Diet After Diagnosis and the Risk of Prostate Cancer Progression, Recurrence, and Death (United States) - June M. Chan; Crystal N. Holick; Michael F. Leitzmann; Eric B. Rimm; Walter C. Willett; Meir J. Stampfer; Edward L. Giovannucci (Cancer Causes & Control, 2006)

Two-locus genome-wide linkage scan for prostate cancer susceptibility genes with an interaction effect - Bao-Li Chang; Ethan M. Lange; Latchezar Dimitrov; Christopher J. Valis; Elizabeth M. Gillanders; Leslie A. Lange; Kathleen E. Wiley; Sarah D. Isaacs; Fredrik Wiklund; Agnes Baffoe-Bonnie; Carl D Langefeld; S. Lilly Zheng; et al. (Human Genetics, 2006)

Oracle-based optimization applied to climate model calibration - Cesar Beltran; N. R. Edwards; A. B. Haurie; J.-P. Vial; D. S. Zachary (Environmental Modeling & Assessment, 2006)

Interactions between Widely Spaced Young Poplars (Populus spp.) and Introduced Pasture Mixtures - G. B. Douglas; A. S. Walcroft; S. E. Hurst; J. F. Potter; A. G. Foote; L. E. Fung; W. R. N. Edwards; C. van den Dijssel (Agroforestry Systems, 2006)

Phosphodiesterase inhibition by sildenafil citrate attenuates a maze learning impairment in rats induced by nitric oxide synthase inhibition - Bryan D. Devan; Jonna L. Bowker; Kara B. Duffy; Ila S. Bharati; Mariana Jimenez; Demetrio Sierra-Mercado; Christopher M. Nelson; Edward L. Spangler; Donald K. Ingram (Psychopharmacology, 2006)

Resistance to insect pests: What do legumes have to offer? - Owain Edwards; Karam B. Singh (Euphytica, 2006)

(−)-Menthol biosynthesis and molecular genetics - Rodney B. Croteau; Edward M. Davis; Kerry L. Ringer; Mark R. Wildung (The Science of Nature, 2005)

Altered genotypic and phenotypic frequencies of aphid populations under enriched CO 2 and O 3 atmospheres - Edward B. Mondor; Michelle N. Tremblay; Caroline S. Awmack; Richard L. Lindroth (Global Change Biology, 2005)
Environmental change is anticipated to negatively affect both plant and animal populations. As abiotic factors rapidly change habitat suitability, projections range from altered genetic diversity to wide‐spread species loss. Here, we assess the degree to which changes in atmospheric composition associated with environmental change will influence not only the abundance, but also the genotypic/phenotypic diversity, of herbivore populations. Using free‐air CO 2 and O 3 enrichment (FACE) technology, we assess numerical responses of pea aphids ( Acyrthosiphon pisum ) exhibiting a pink–green genetic polymorphism and an environmentally determined wing polyphenism on broad bean plants ( Vicia faba ) under enriched CO 2 and/or O 3 atmospheres, over multiple generations. We show that these two greenhouse gases alter not only aphid population sizes, but also genotypic and phenotypic frequencies. As the green genotype was positively influenced by elevated CO 2 levels, but the pink genotype was not, genotypic frequencies (pink morph : green morph) ranged from 1 : 1 to 9 : 1. These two genotypes also displayed marked differences in phenotypic frequencies. The pink genotype exhibited higher levels of wing induction under all atmospheric treatments, however, this polyphenism was negatively influenced by elevated O 3 levels. Resultantly, frequencies of winged phenotypes (pink morph : green morph) varied from 10 : 1 to 332 : 1. Thus, atmospheric conditions associated with environmental change may alter not just overall population sizes, but also genotypic and phenotypic frequencies of herbivore populations, thereby influencing community and ecosystem functioning.

Development of baroreflex and endocrine responses to hypotensive stress in newborn foals and lambs - S. J. O’Connor; D. S. Gardner; J. C. Ousey; N. Holdstock; P. Rossdale; C. M. B. Edwards; A. L. Fowden; D. A. Giussani (Pflügers Archiv - European Journal of Physiology, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Nitrogen/phosphorus leaf stoichiometry and the scaling of plant growth - Karl J. Niklas; Thomas Owens; Peter B. Reich; Edward D. Cobb (Ecology Letters, 2005)
We adopted previous N : P stoichiometric models for zooplankton relative growth to predict the relative growth rates of the leaves μ L of vascular plants assuming that annual leaf growth in dry mass is dictated by how leaf nitrogen N L is allocated to leaf proteins and how leaf phosphorus P L is allocated to rRNA. This model is simplified provided that N L scales as some power function of P L across the leaves of different species. This approach successfully predicted the μ L of 131 species of vascular plants based on the observation that, across these species, N L scaled, on average, as the 3/4 power of P L , i.e. N L ∝ P . When juxtaposed with prior allometric theory and observations, our findings suggest that a transformation in N : P stoichiometry occurs when the plant body undergoes a transition from primary to secondary growth.

Soybean aphid,Aphis glycines Matsumura, a new vector ofPotato virus Y in potato - Jeffrey A. Davis; Edward B. Radcliffe; David W. Ragsdale (American Journal of Potato Research, 2005)

Beringia as a glacial refugium for boreal trees and shrubs: new perspectives from mapped pollen data - Linda B. Brubaker; Patricia M. Anderson; Mary E. Edwards; Anatoly V. Lozhkin (Journal of Biogeography, 2005)
Aim Beringia, far north‐eastern Siberia and north‐western North America, was largely unglaciated during the Pleistocene. Although this region has long been considered an ice‐age refugium for arctic herbs and shrubs, little is known about its role as a refugium for boreal trees and shrubs during the last glacial maximum (LGM, c . 28,000–15,000 calibrated years before present). We examine mapped patterns of pollen percentages to infer whether six boreal tree and shrub taxa ( Populus , Larix , Picea , Pinus , Betula , Alnus/Duschekia ) survived the harsh glacial conditions within Beringia. Methods Extensive networks of pollen records have the potential to reveal distinctive temporal–spatial patterns that discriminate between local‐ and long‐distance sources of pollen. We assembled pollen records for 149 lake, peat and alluvial sites from the Palaeoenvironmental Arctic Sciences database, plotting pollen percentages at 1000‐year time intervals from 21,000 to 6000 calibrated years before present. Pollen percentages are interpreted with an understanding of modern pollen representation and potential sources of long‐distance pollen during the glacial maximum. Inferences from pollen data are supplemented by published radiocarbon dates of identified macrofossils, where available. Results Pollen maps for individual taxa show unique temporal‐spatial patterns, but the data for each taxon argue more strongly for survival within Beringia than for immigration from outside regions. The first increase of Populus pollen percentages in the western Brooks Ranges is evidence that Populus trees survived the LGM in central Beringia. Both pollen and macrofossil evidence support Larix survival in western Beringia (WB), but data for Larix in eastern Beringia (EB) are unclear. Given the similar distances of WB and EB to glacial‐age boreal forests in temperate latitudes of Asia and North America, the widespread presence of Picea pollen in EB and Pinus pollen in WB indicates that Picea and Pinus survived within these respective regions. Betula pollen is broadly distributed but highly variable in glacial‐maximum samples, suggesting that Betula trees or shrubs survived in restricted populations throughout Beringia. Alnus/Duschekia percentages show complex patterns, but generally support a glacial refugium in WB. Main conclusions Our interpretations have several implications, including: (1) the rapid post‐glacial migration rate reported for Picea in western Canada may be over estimated, (2) the expansion of trees and shrubs within Beringia should have been nearly contemporaneous with climatic change, (3) boreal trees and shrubs are capable of surviving long periods in relatively small populations (at the lower limit of detection in pollen data) and (4) long‐distance migration may not have been the predominant mode of vegetation response to climatic change in Beringia.

Absence of behavioral sensitization in healthy human subjects following repeated exposure to ketamine - Hyun-Sang Cho; Deepak C. D’Souza; Ralitza Gueorguieva; Edward B. Perry; Steven Madonick; Laurence P. Karper; Anissa Abi-Dargham; Aysenil Belger; Walid Abi-Saab; Deborah Lipschitz; Alexandre Bennet; John P. Seibyl; et al. (Psychopharmacology, 2005)

DFNB48, a new nonsyndromic recessive deafness locus, maps to chromosome 15q23-q25.1 - Jamil Ahmad; Shaheen N. Khan; Shahid Y. Khan; Khushnooda Ramzan; Saima Riazuddin; Zubair M. Ahmed; Edward R. Wilcox; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2005)

Reconstructing the phylogeny of the Sipuncula - Anja Schulze; Edward B. Cutler; Gonzalo Giribet (Hydrobiologia, 2005)

Predator-induced transgenerational phenotypic plasticity in the cotton aphid - Edward B. Mondor; Jay A. Rosenheim; John F. Addicott (Oecologia, 2005)

INHIBITION OF MICRO-RNA–INDUCED RNA SILENCING BY 2′-O-METHYL OLIGONUCLEOTIDES IN DROSOPHILA S2 CELLS - EDWARD M. BERGER; EDWARD B. DUBROVSKY; LARA APPLEBY; VERONICA DUBROVSKAYA (In Vitro Cellular & Developmental Biology - Animal, 2005)

A new locus for nonsyndromic deafness DFNB49 maps to chromosome 5q12.3-q14.1 - Khushnooda Ramzan; Rehan S. Shaikh; Jamil Ahmad; Shaheen N. Khan; Saima Riazuddin; Zubair M. Ahmed; Thomas B. Friedman; Edward R. Wilcox; Sheikh Riazuddin (Human Genetics, 2005)

Empirical Bayes estimation of gene-specific effects in micro-array research - Jode W. Edwards; Grier P. Page; Gary Gadbury; Moonseong Heo; Tsuyoshi Kayo; Richard Weindruch; David B. Allison (Functional & Integrative Genomics, 2005)

Diversity of arbuscular mycorrhizal fungi across a fragmented forest in Panama: insular spore communities differ from mainland communities - Scott A. Mangan; Ahn-Heum Eom; Gregory H. Adler; Joseph B. Yavitt; Edward A. Herre (Oecologia, 2004)

Dietary patterns and risk of colon cancer and adenoma in a cohort of men (United States) - Kana Wu; Frank B. Hu; Charles Fuchs; Eric B. Rimm; Walter C. Willett; Edward Giovannucci (Cancer Causes & Control, 2004)

Oxygen uptake kinetics and maximal aerobic power are unaffected by inspiratory muscle training in healthy subjects where time to exhaustion is extended - A. M. Edwards; C. B. Cooke (European Journal of Applied Physiology, 2004)

Cataract Extraction and Risk of Breast Cancer - Shumin M. Zhang; Walter C. Willett; Frank B. Hu; Edward L. Giovannucci; JoAnn E. Manson; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2004)

Divergent pheromone‐mediated insect behaviour under global atmospheric change - Edward B. Mondor; Michelle N. Tremblay; Caroline S. Awmack; Richard L. Lindroth (Global Change Biology, 2004)
While the effects of global atmospheric changes on vegetation and resulting insect populations(‘bottom‐up interactions’) are being increasingly studied, how these gases modify interactions among insects and their natural enemies (‘top‐down interactions’) is less clear. As natural enemy efficacy is governed largely by behavioural mechanisms, altered prey finding and prey defence may change insect population dynamics. Here we show that pheromone‐mediated escape behaviours, and hence the vulnerability of insects to natural enemies, are divergent under atmospheric conditions associated with global climate change. Chaitophorus stevensis , a common aphid on trembling aspen trees, Populus tremuloides , have diminished escape responses in enriched carbon dioxide (CO 2 ) environments, while those in enriched ozone (O 3 ) have augmented escape responses, to alarm pheromone. These results suggest that divergent pheromone‐mediated behaviours could alter predator–prey interactions in future environments.

Transgenerational phenotypic plasticity under future atmospheric conditions - Edward B. Mondor; Michelle N. Tremblay; Richard L. Lindroth (Ecology Letters, 2004)
Organisms often exhibit transgenerational phenotypic changes in response to an increased risk of parasitism or predation. Shifts in global atmospheric composition could modify these phenotypic effects through changes in either nutrient quantity/quality or altered interactions with higher trophic levels. Here we show that future atmospheric conditions alter a natural enemy‐induced wing polyphenism in aphids. Winged offspring production by Uroleucon nigrotuberculatum aphids on goldenrod ( Solidago canadensis var. scabra ) does not differ in enriched CO 2 and/or O 3 atmospheres. However, proportionally more winged offspring are produced in response to search cues from both coccinellid predators ( Coccinella septempunctata ) and hymenopteran parasitoids ( Aphidius polygonaphis ) relative to plants not searched by natural enemies. Moreover, the magnitude of this response differs under enriched CO 2 and O 3 environments. Aphids produce more winged offspring in response to predators under elevated CO 2 , but produce more winged offspring in response to parasitoids under elevated O 3 . Thus, global atmospheric changes influence natural enemy‐mediated phenotypic expression, with potentially far‐reaching consequences for trophic dynamics.

P-glycoprotein Expression, Localization, and Function in Sandwich-Cultured Primary Rat and Human Hepatocytes: Relevance to the Hepatobiliary Disposition of a Model Opioid Peptide - Keith A. Hoffmaster; Ryan Z. Turncliff; Edward L. LeCluyse; Richard B. Kim; Peter J. Meier; Kim L. R. Brouwer (Pharmaceutical Research, 2004)

SURVIVAL ESTIMATES FOR FLORIDA MANATEES FROM THE PHOTO‐IDENTIFICATION OF INDIVIDUALS - Catherine A. Langtimm; Cathy A. Beck; Holly H. Edwards; Kristin J. Fick‐Child; Bruce B. Ackerman; Sheri L. Barton; Wayne C. Hartley (Marine Mammal Science, 2004)
A bstract We estimated adult survival probabilities for the endangered Florida manatee ( Trichechus manatus latirostris ) in four regional populations using photoidentification data and open‐population capture‐recapture statistical models. The mean annual adult survival probability over the most recent 10‐yr period of available estimates was as follows: Northwest ‐ 0.956 (SE 0.007), Upper St. Johns River ‐ 0.960 (0.011), Atlantic Coast ‐ 0.937 (0.008), and Southwest ‐ 0.908 (0.019). Estimates of temporal variance independent of sampling error, calculated from the survival estimates, indicated constant survival in the Upper St. Johns River, true temporal variability in the Northwest and Atlantic Coast, and large sampling variability obscuring estimates for the Southwest. Calf and subadult survival probabilities were estimated for the Upper St. Johns River from the only available data for known‐aged individuals: 0.810 (95% CI 0.727–0.873) for 1st year calves, 0.915 (0.827–0.960) for 2nd year calves, and 0.969 (0.946–0.982) for manatee 3 yr or older. These estimates of survival probabilities and temporal variance, in conjunction with estimates of reproduction probabilities from photoidentification data can be used to model manatee population dynamics, estimate population growth rates, and provide an integrated measure of regional status.

QTL controlling partial resistance to Stagonospora nodorum leaf blotch in winter wheat cultivar Alba - Edward Arseniuk; Pawel C. Czembor; Andrzej Czaplicki; Qijian Song; Perry B. Cregan; David L. Hoffman; Peter P. Ueng (Euphytica, 2004)

Species Diversity Across Nutrient Gradients: An Analysis of Resource Competition in Model Ecosystems - Darrell A. Herbert; Edward B. Rastetter; Laura Gough; Gaius R. Shaver (Ecosystems, 2004)

Quantitative trait locus analysis of fungal disease resistance factors on a molecular map of grapevine - B. M. Fischer; I. Salakhutdinov; M. Akkurt; R. Eibach; K. J. Edwards; R. Töpfer; E. M. Zyprian (Theoretical and Applied Genetics, 2004)

Hydrologic variability, water chemistry, and phytoplankton biomass in a large floodplain of the Sacramento River, CA, U.S.A. - Laurence Edward Schemel; Ted R. Sommer; Anke B. Müller-Solger; William C. Harrell (Hydrobiologia, 2004)

Properties of human motor units after prolonged activity at a constant firing rate - K. V. B. Johnson; S. C. Edwards; C. Van Tongeren; P. Bawa (Experimental Brain Research, 2004)

Epstein-Barr virus-mediated protection against etoposide-induced apoptosis in BJA-B B cell lymphoma cells: role of Bcl-2 and caspase proteins - A. Blood; C. J. Edwards; H. H. Ishii; B. K. Pat; G. Bryson; T. B. Sculley; G. C. Gobe (Archives of Virology, 2004)

EXPLANT-CELL CULTURE OF PRIMARY MAMMARY TUMORS FROM MMTV-c-Myc TRANSGENIC MICE - XU FANG PEI; MARCIA S. NOBLE; MARIA ANTONIETTA DAVOLI; EDWARD ROSFJORD; MADDALENA T. TILLI; PRISCILLA A. FURTH; ROBERT RUSSELL; MICHAEL D. JOHNSON; ROBERT B. DICKSON (In Vitro Cellular & Developmental Biology - Animal, 2004)

GROWTH, IMMORTALIZATION, AND DIFFERENTIATION POTENTIAL OF NORMAL ADULT HUMAN PROXIMAL TUBULE CELLS - DAVID E. OROSZ; PHILIP G. WOOST; ROBERT J. KOLB; MARGARET B. FINESILVER; WENWU JIN; PHYLLIS S. FRISA; CHEE-KEONG CHOO; CHUNG-FAI YAU; KWOK-WAH CHAN; MARTIN I. RESNICK; JANICE G. DOUGLAS; JOHN C. EDWARDS; et al. (In Vitro Cellular & Developmental Biology - Animal, 2004)

Distribution, host range and phenology of the rust fungus Puccinia myrsiphylli in South Africa - Catharina A. Kleinjan; Louise Morin; Penelope B. Edwards; Alan R. Wood (Australasian Plant Pathology, 2004)

Above- and Belowground Competition from Longleaf Pine Plantations Limits Performance of Reintroduced Herbaceous Species - Timothy B. Harrington; Christa M. Dagley; M.Boyd Edwards (Forest Science, 2003)
Although overstory trees limit the abundance and species richness of herbaceous vegetation in longleaf pine (Pinus palustris Mill.) plantations, the responsible mechanisms are poorly understood because of confounding among limiting factors. In fall 1998, research was initiated to determine the separate effects of above- and belowground competition and needlefall from overstory pines on understory plant performance. Three 13- to 15-yr-old plantations near Aiken, SC, were thinned to 0, 25, 50, or 100% of nonthinned basal area (19.5 m2 ha-1). Combinations of trenching (to eliminate root competition) and needlefall were applied to areas within each plot, and containerized seedlings of 14 perennial herbaceous species and longleaf pine were planted within each. Overstory crown closure ranged from 0 to 81%, and soil water and available nitrogen varied consistently with pine stocking, trenching, or their combination. Cover of planted species decreased an average of 16.5 and 14.1% as a result of above- and belowground competition, respectively. Depending on species, needlefall effects were positive, negative, or negligible. Results indicate that understory restoration will be most successful when herbaceous species are established within canopy openings (0.1–0.2 ha) managed to minimize negative effects from above- and belowground competition and needlefall.

Explaining Agricultural Expansion, Resource Booms and Growth in Latin America - Edward B. Barbier (Environment, Development and Sustainability, 2003)

The Tagliamento River: A model ecosystem of European importance - Klement Tockner; James V. Ward; David B. Arscott; Peter J. Edwards; Johannes Kollmann; Angela M. Gurnell; Geoffrey E. Petts; Bruno Maiolini (Aquatic Sciences, 2003)

Abundance and distribution of planktonic Archaea and Bacteria in the waters west of the Antarctic Peninsula - Matthew J. Church; Edward F. DeLong; Hugh W. Ducklow; Markus B. Karner; Christina M. Preston; David M. Karl (Limnology and Oceanography, 2003)
Polyribonucleotide probes targeting planktonic archaeal (Group I and II) and bacterial rRNA revealed that Archaea comprised a significant fraction of total prokaryote cell abundance in the marine waters west of the Antarctic Peninsula. Determinations of Archaea and Bacteria cell abundances were made during two research cruises to the Palmer Long‐Term Ecological Research region during the austral winter and summer of 1999. During the austral summer, surface water abundances of Group I (GI) Archaea were generally low, averaging 4.7 x 10 3 cells ml −1 and accounting for 1% of the total picoplankton assemblage. The abundance of GI Archaea increased significantly with depth, averaging 2.1 X 10 4 cells ml −1 and comprising 9–39% of the total picoplankton abundance in the meso‐ (150–1,000 m) and bathypelagic (1,000–3,500 m) circumpolar deep water (CDW). Relative to summertime distributions, GI cells were more evenly distributed throughout the water column during the winter, averaging 10% of the picoplankton in the surface waters and 13% in the CDW. Surface water GI abundance increased 44% between the summer and winter, coincident with a fivefold decrease in GI abundance in the deeper waters. The abundance of Group II (GII) Archaea was persistently 5 cells ml −1 and comprised 89% of the total picoplankton assemblage. Generally, GI Archaea varied seasonally in the deeper waters, whereas bacterial abundance varied more in the upper waters. The observed variability in bacterial and archaeal abundance suggests that these two groups of marine picoplankton are dynamic components of Southern Ocean microbial food webs.

Iron requirements for dinitrogen‐ and ammonium‐supported growth in cultures of Trichodesmium (IMS 101): Comparison with nitrogen fixation rates and iron: carbon ratios of field populations - Adam B. Kustka; Sergio A. Sañudo‐Wilhelmy; Edward J. Carpenter; Douglas Capone; James Burns; William G. Sunda (Limnology and Oceanography, 2003)
We quantified the relationships among the specific growth rate, intracellular iron content, and steady state iron uptake rate for cultures of the marine diazotrophic cyanobacterium Trichodesmium (IMS 101) grown under differing conditions of Fe and N availability. The Fe quotas necessary to support a moderately Fe‐limited growth rate (70% mmax) of 0.1 d −1 under diazotrophy and ammonium were 38 and 8 µmol mol −1 , indicating a fivefold increased Fe cost for diazotrophy. This increased demand reflects the influences of both the ninefold lower marginal use efficiency and the greater maintenance Fe :C requirement at zero growth rate under diazotrophy (13.5 versus 5.2 µmol mol −1 ). For diazotrophic growth at µ = 0.1 d −1 , we estimate that 19%–53% of the cellular Fe is bound in nitrogenase. Trichodesmium is capable of luxury uptake of at least 13‐fold greater amounts of Fe than needed for moderately Fe‐limited growth. At least half of the populations sampled from the continental shelf of northern Australia had Fe :C ratios within the range of iron limitation of laboratory cultures. Bottle incubations showed that, after 3–4 d with added iron, a low Fe :C population (21 µmol mol −1 ) had higher N2 fixation rates than controls, whereas a high Fe :C population (78 µmol mol −1 ) showed no response. The cellular N: P quotas and N2 fixation rates were compared to those previously reported for the Atlantic Ocean. Empirically, these data suggest a critical N: P ratio ~40–50 for the onset of P limitation of growth. Only 10% of the Trichodesmium populations from coastal Australia had N: P ratios within the putative P‐limitation range (>40), whereas 40% the Atlantic populations fell within this range. These comparisons, along with those for N fixation versus colony Fe :C ratio, suggest that Fe limitation is more prevalent in the Australia Trichodesmium populations, while P limitation predominates in the Atlantic populations.

Conspicuous extra‐floral nectaries are inducible in Vicia faba - Edward B. Mondor; John F. Addicott (Ecology Letters, 2003)
Mutualistic interactions are dynamic associations that vary depending on the costs and benefits to each of the interacting parties. Phenotypic plasticity in mutualistic interactions allows organisms to produce rewards to attract mutualists when the benefits of their presence outweigh the costs of producing the rewards. In ant–plant defensive mutualisms, defences are indirect as plants produce extra‐floral nectaries (EFN) to attract predatory ants to deter herbivores. Here we demonstrate that in broad bean, Vicia faba , the overall number of EFNs on a plant increases dramatically following leaf damage. In two damage treatments, removal of: (1) one‐third of one leaf in a single leaf pair or (2) one‐third of both halves of a single leaf pair, resulted in a 59 and 106% increase in the number of EFNs on the plants, respectively, over 1 week. We suggest that the increased production of visually conspicuous EFNs is an adaptive inducible response, to attract predatory arthropods when risk of herbivory increases.

Creatine supplementation during college football training does not increase the incidence of cramping or injury - Michael Greenwood; Richard B. Kreider; Charlie Melton; Christopher Rasmussen; Stacy Lancaster; Edward Cantler; Purvis Milnor; Anthony Almada (Molecular and Cellular Biochemistry, 2003)

Long-term creatine supplementation does not significantly affect clinical markers of health in athletes - Richard B. Kreider; Charles Melton; Christopher J. Rasmussen; Michael Greenwood; Stacy Lancaster; Edward C. Cantler; Pervis Milnor; Anthony L. Almada (Molecular and Cellular Biochemistry, 2003)

Control of hyperhydricity in Eucalyptus axillary shoot cultures grown in liquid medium - Adam B. Whitehouse; Timothy R. Marks; Glyn A. Edwards (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

Changes in Individual Allometry Can Lead to Species Coexistence without Niche Separation - Edward B. Rastetter; Göran I. gren (Ecosystems, 2002)

Does the cerebellum play a role in podokinetic adaptation? - Gammon M. Earhart; William A. Fletcher; Fay B. Horak; Edward W. Block; Kimberly D. Weber; Oksana Suchowersky; Geoffrey Melvill Jones (Experimental Brain Research, 2002)

Aphid-transmitted potato viruses: The importance of understanding vector biology - Edward B. Radcliffe; David W. Ragsdale (American Journal of Potato Research, 2002)

Genetic mapping of 66 new microsatellite (SSR) loci in bread wheat - P. Gupta; H. Balyan; K. Edwards; P. Isaac; V. Korzun; M. Röder; M.–F. Gautier; P. Joudrier; A. Schlatter; J. Dubcovsky; R. De la Pena; M. Khairallah; et al. (Theoretical and Applied Genetics, 2002)

On birth and death in the sea - Mark D. Ohman; Jeffrey A. Runge; Edward G. Durbin; David B. Field; Barbara Niehoff (Hydrobiologia, 2002)

Nonsyndromic recessive deafness DFNB18 and Usher syndrome type IC are allelic mutations of USHIC - Zubair M. Ahmed; Tenesha N. Smith; Saima Riazuddin; Tomoko Makishima; Manju Ghosh; Sirosh Bokhari; Puthezhath S. Menon; Dilip Deshmukh; Andrew J. Griffith; Sheikh Riazuddin; Thomas B. Friedman; Edward R. Wilcox (Human Genetics, 2002)

Microsatellite Markers for the Paddlefish (Polyodon spathula) - Edward J. Heist; Erica H. Nicholson; Justin T. Sipiorski; Devon B. Keeney (Conservation Genetics, 2002)

Tick–Host–Borrelia Population Interactions: Long-Term Records in Eastern Europe - Edward I. Korenberg; Yury V. Kovalevskii; Nataliya B. Gorelova (Experimental and Applied Acarology, 2002)

Subglacial, phonolitic volcanism at Hoodoo Mountain volcano, northern Canadian Cordillera - Edwards B.; Russell J.; Anderson R. (Bulletin of Volcanology, 2002)

Decoding of a motor command vector from distributed activity in superior colliculus - Jeremy B. Badler; Edward L. Keller (Biological Cybernetics, 2002)

Stoichiometric food quality and herbivore dynamics - Erik B. Muller; Roger M. Nisbet; Sebastiaan A. L. M. Kooijman; James J. Elser; Edward McCauley (Ecology Letters, 2001)
Herbivores may grow with nutrient or energy limitation, depending on food abundance and the chemical composition of their food. We present a model that describes herbivore growth as a continuous function of two limiting factors. This function uses the synthesizing unit concept, has the hyperbolic Monod model as a limiting case, and has the same number of parameters as the Monod model coupled to Liebig’s discontinuous minimum rule. We use the model to explore nutrient‐limited herbivore growth in a closed system with algae, Daphnia and phosphorus as the limiting nutrient. Phosphorus in algae may substantially influence Daphnia growth. This influence changes over time and is most pronounced when algae and Daphnia populations fluctuate strongly. Relative to classic models that only consider food quantity as a determinant of Daphnia growth, our model shows richer dynamical behaviour. In addition to the standard positive equilibrium, which may be stable or unstable depending on nutrient availability, a new positive equilibrium may arise in our model when mortality rates are relatively high. This equilibrium is unstable and reduces the likelihood of long‐term persistence of Daphnia in the system.

Tropical Deforestation, Tenure Insecurity, and Unsustainability - Edward B. Barbier; Joanne C. Burgess (Forest Science, 2001)
This article explores the effects of tenure insecurity on the migrant's decision to convert tropical frontier forestland to unsustainable agriculture. We develop and extend a Faustmann model to explore the effects of insecure property rights and unsustainability on the migrant's decision to convert tropical forestland to crop production, to maintain it for long-term timber production, or to mine the forest for timber and then abandon the land. We then provide a numerical simulation of the migrant's land-use decision based on data from the Amazon to compare the returns to mahogany plantation as opposed to agricultural conversion or timber mining. Increasing insecurity of land tenure leads to a decline in the value of timber relative to agricultural production land, thus creating an incentive for forest conversion. However, when land is easily degraded and tenure insecurity is high, timber mining and land abandonment may be a particular problem. Finally, we examine the role of private and government investment in establishing and maintaining secure land tenure. Once government “arrives” at the frontier, it can encourage sustainable timber production through providing secure harvesting rights and setting an optimal concession fee. FOR. SCI. 47(4):497–509.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VI. The pioneer arthropod community of Motmot - John S. Edwards; Ian W. B. Thornton (Journal of Biogeography, 2001)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)
Location, aims Long Island's biota was destroyed by volcanic eruption in c. 1645, and Motmot, an emergent island in its caldera lake, was re‐created in 1968, providing a nested pair of natural colonization sequences. In 1999 we surveyed the plants and vertebrates of Long and the entire biota of Motmot for comparison with previous surveys of Long (1932, 1972, birds only) and Motmot (1969–88). Results The known flora of Long is 305 vascular plants (thirty‐two pteridophytes, 273 spermatophytes), including thirty‐one Ficus species, the sixteen fruiting all having pollinating wasps, and there were eleven species of effective fig dispersers. There were two frog species, a crocodile, a monitor, seven skinks, four geckos, a boid snake, fifty species non‐migrant land birds, seven bats, two rats, a cuscus (probably introduced) and feral pigs, dogs, cats and chickens. Most of Motmot's surface was barren or sparsely vegetated ash, cinder and lava fields. There were seven pteridophyte and thirty‐eight spermatophyte species, including eight Ficus , and the cumulative known flora comprises eleven pteridophytes and fifty‐one spermatophytes, mainly zoochorous and anemochorous, with sedges, grasses and herbs predominating. All Ficus individuals but one were small; three plants of two species bore syconia but had not been pollinated and had not set seed. Motmot's known invertebrate fauna comprises thirty‐five species, mainly predators and scavengers; two spider and one ant species dominating. An insectivorous bat and eight land bird species (three breeding) were the only vertebrates. Main conclusions Long's biota comprised mainly widely distributed species with broad ecological tolerances, well‐adapted for colonizing species‐poor islands. The mid‐level caldera plateau, as in 1932, was covered in fairly open forest of similar‐sized trees with a few much larger individuals and little or no understorey. Primary rain forest tree species from the region were under‐represented or absent but secondary forest species were common. There were few regional endemic Ficus species. The avifauna comprised species with good dispersal ability, lacked endemic subspecies and probably for at least the past seven decades has been held at a quasi‐equilibrium of fifty species, fourteen below the theoretical number. More than half the fifty‐four resident land birds known from Long (and three of the seven bats) are high class tramps in the sense of Diamond; only two birds are high‐S species. Turnover has been low and none of the bird super tramps has been replaced. The non‐avian fauna comprised mostly high‐category tramptype species with relatively broad habitat requirements and extensive geographical ranges. Non‐volant vertebrates comprised a number of highly vagile species associated with humans. Several groups, especially snakes and amphibians, were depauperate compared with the fauna of other islands in the area. Long's biota is evidently held at an arrested stage of development by some physical factor, possibly the extremely porous substratum and relatively dry climate. The allochthonous input of lake insects to Motmot evidently provides the major energy source for its animal communities, with a very minor contribution from organic flotsam. Reflecting Motmot's very isolated situation, plant colonization has been slow, but when more fig individuals mature and fig–wasp populations become established fruit production should attract frugivores and start a positive feedback process which will accelerate the growth of Motmot's community. Long's colonization shows similarities with that of Krakatau (Sunda Strait, Indonesia) after the 1883 eruption, and species shared by the two include a high proportion of pioneer species. Motmot's triple isolation (sea, land and fresh‐water barriers) means that its colonization differs markedly from those on two marine emergent islands of the region, Tuluman (Admiralty Group) and Anak Krakatau.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VI. The pioneer arthropod community of Motmot - John S. Edwards; Ian W. B. Thornton (Journal of Biogeography, 2001)
Aim To evaluate the arthropod community of Motmot in relation to primary colonization of young volcanic surfaces. Location Motmot, an island in Lake Wisdom which occupies the caldera of Long Island, Papua New Guinea. Methods Arthropod sampling by means of pitfall, water and tube traps, fallout collectors, and hand collecting. Results At least thirty‐five species of arthropod were collected in 6 days between 23 June and 3 July 1999. Lycosid spiders and ants dominated in all areas. The predator‐scavenger arthropod population is largely or entirely dependent on allochthonous input of aquatic insects from the surrounding lake. Main conclusions Major changes in the arthropod fauna since the pioneer surveys of Ball and his colleagues in the 1970s are the loss of a strand flotsam community as the island has eroded to form a predominantly cliffed coastline. Ant and spider diversity has increased. The current colonists include a number of widespread ‘tramp' species sensu Diamond.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)

The test-retest reliability of gas exchange kinetics in humans using a pseudo random binary sequence exercise test - A. M. Edwards; N. V. Challis; J. H. Chapman; D. B. Claxton; M. L. Fysh (European Journal of Applied Physiology, 2001)

A prospective study on intake of animal products and risk of prostate cancer - Dominique S. Michaud; Katarina Augustsson; Eric B. Rimm; Meir J. Stampfer; Walter C. Willett; Edward Giovannucci (Cancer Causes & Control, 2001)

The Downstream Activation Sequence of the Strict Late Herpes Simplex Virus Type 1 UL38 Promoter Interacts With hTAFII70, a Component of TFIID - Matthew D. Petroski; Gayathri B. Devi-Rao; Marcia K. Rice; Edward K. Wagner (Virus Genes, 2001)

Agonistic behavior in naïve juvenile lobsters depleted of serotonin by 5,7-dihydroxytryptamine - Sarah B. Doernberg; Stuart I. Cromarty; Ralf Heinrich; Barbara S. Beltz; Edward A. Kravitz (Journal of Comparative Physiology A, 2001)

Physiological comparisons among three maximal treadmill exercise protocols in trained and untrained individuals - Jie Kang; Edward C. Chaloupka; M. Alysia Mastrangelo; Gregory B. Biren; Robert J. Robertson (European Journal of Applied Physiology, 2001)

Tissue distribution and functional expression of the human voltage-gated sodium channel β3 subunit - Edward B. Stevens; Peter J. Cox; Bhaval S. Shah; Alistair K. Dixon; Peter J. Richardson; Robert D. Pinnock; Kevin Lee (Pflügers Archiv - European Journal of Physiology, 2001)

Ontogeny of Alarm Pheromone Secretion in Pea Aphid, Acyrthosiphon pisum - Edward B. Mondor; D. Scott Baird; K. N. Slessor; B. D. Roitberg (Journal of Chemical Ecology, 2000)

Characterization of nuclear microsatellites in Pinus halepensis Mill. and their inheritance in P. halepensis and Pinus brutia Ten. - R. N. Keys; A. Autino; K. J. Edwards; B. Fady; C. Pichot; G. G. Vendramin (Molecular Ecology, 2000)

Characterization of nuclear microsatellites in Pinus halepensis Mill. and their inheritance in P. halepensis and Pinus brutia Ten. - R. N. Keys; A. Autino; K. J. Edwards; B. Fady; C. Pichot; G. G. Vendramin (Molecular Ecology, 2000)

The controls on net ecosystem productivity along an Arctic transect: a model comparison with flux measurements - Mathew Williams; Werner Eugster; Edward B. Rastetter; Joseph P. Mcfadden; F. Stuart Chapin Iii (Global Change Biology, 2000)
Summary Assessments of carbon (C) fluxes in the Arctic require detailed data on both how and why these fluxes vary across the landscape. Such assessments are complicated because tundra vegetation has diverse structure and function at both local and regional scales. To investigate this diversity, the Arctic Flux Study has used the eddy covariance technique to generate ecosystem CO 2 ‐exchange data along a transect in northern Alaska. We use an extant process‐based model of the soil–plant–atmosphere continuum to make independent predictions of gross photosynthesis and foliar respiration at 9 of the sites along the transect, using data on local canopy structure and meteorology. We make two key assumptions: (i) soil respiration is constant throughout the flux measurement period, so that the diurnal cycle in CO 2 exchange is driven by canopy processes only (except at two sites where a soil respiration–temperature relationship was indicated in the data); and (ii) mosses and lichens play an insignificant role in ecosystem C exchange, even though in some locations their live biomass exceeds 300 g m −2 . We found that even with these assumptions the model could explain much of the dynamics of net ecosystem production (NEP) at sites with widely differing vegetation structure and moss/lichen cover. Errors were mostly associated with the predictions of maximum NEP; the likely cause of such discrepancies was (i) a mismatch between vegetation sampled for characterizing the canopy structure and that contained within the footprint of the eddy covariance flux measurements, or (ii) an increase in daytime soil and root respiration. Thus the model results tended to falsify our first assumption but not our second. We also note evidence for an actual reduction in NEP caused by water stress on warm, dry days at some sites. The model–flux comparison also suggests that photosynthesis may be less sensitive to low temperatures than leaf‐level gas‐exchange measurements have indicated.

The Potato Association of America - Steven R. James; Lori Wing; Ronald Knight; Barbara Harrity; Devid H. Lambert; Bud Platt; Al Reeves; Bill Bohl; Lind Sanford; Alexander D. Pavlista; Ed Plissey; Richard Sawyer; et al. (American Journal of Potato Research, 2000)

MIGRATION AND POPULATION STRUCTURE OF NORTHEASTERN PACIFIC WHALES OFF COASTAL BRITISH COLUMBIA: AN ANALYSIS OF COMMERCIAL WHALING RECORDS FROM 1908‐1967 - Edward J. Gregr; Linda Nichol; John K. B. Ford; Graeme Ellis; Andrew W. Trites (Marine Mammal Science, 2000)
A bstract Data recorded from 24,862 whales killed by British Columbia coastal whaling stations between 1908 and 1967 revealed trends in the abundance, sex ratios, age structure, and distribution of sperm ( Physeter macrocephalus ), fin ( Balaenoptera physalus ), sei ( Balaenoptera borealis ), humpback ( Megaptera novaeangliae ), and blue ( Balaenoptera musculus ) whales. The catch data were analyzed using annual and monthly mean values. Monthly and annual variation in whaling effort was deduced from accounts of the history of British Columbia coastal whaling, and biases arising from changes in effort were considered in the interpretation of the results. During the later years of whaling (1948‐1967), the mean lengths of captured whales declined significantly and pregnancy rates dropped to near zero in fin, sei, and blue whales. Monthly patterns in numbers killed revealed a summer migration of sei and blue whales past Vancouver Island, and confirms anecdotal suggestions that local populations of fin and humpback whales once spent extended periods in the coastal waters of British Columbia. Furthermore, the data strongly suggest that sperm whales mated (April‐May) and calved (July‐August) in British Columbia's offshore waters. The historic whaling records reveal much about the migratory behavior and distribution of the large whales species as they once were, and may continue to be, in the northeastern Pacific. Verifying the persistence of these trends in the remnant populations is a necessary and logical next step.

Construction and analysis of bacterial artificial chromosome libraries from a marine microbial assemblage - Oded Béjà; Marcelino T. Suzuki; Eugene V. Koonin; L. Aravind; Andrew Hadd; Linh P. Nguyen; Rachel Villacorta; Mojgan Amjadi; Corey Garrigues; Stevan B. Jovanovich; Robert A. Feldman; Edward F. DeLong (Environmental Microbiology, 2000)
Cultivation‐independent surveys of ribosomal RNA genes have revealed the existence of novel microbial lineages, many with no known cultivated representatives. Ribosomal RNA‐based analyses, however, often do not provide significant information beyond phylogenetic affiliation. Analysis of large genome fragments recovered directly from microbial communities represents one promising approach for characterizing uncultivated microbial species better. To assess further the utility of this approach, we constructed large‐insert bacterial artificial chromosome (BAC) libraries from the genomic DNA of planktonic marine microbial assemblages. The BAC libraries we prepared had average insert sizes of ≈ 80 kb, with maximal insert sizes > 150 kb. A rapid screening method assessing the phylogenetic diversity and representation in the library was developed and applied. In general, representation in the libraries agreed well with previous culture‐independent surveys based on polymerase chain reaction (PCR)‐amplified rRNA fragments. A significant fraction of the genome fragments in the BAC libraries originated from as yet uncultivated microbial species, thought to be abundant and widely distributed in the marine environment. One entire BAC insert, derived from an uncultivated, surface‐dwelling euryarchaeote, was sequenced completely. The planktonic euryarchaeal genome fragment contained some typical archaeal genes, as well as unique open reading frames (ORFs) suggesting novel function. In total, our results verify the utility of BAC libraries for providing access to the genomes of as yet uncultivated microbial species. Further analysis of these BAC libraries has the potential to provide significant insight into the genomic potential and ecological roles of many indigenous microbial species, cultivated or not.

Echiura from Antarctic and adjacent waters - José I. Saiz-Salinas; Harlan K. Dean; Edward B. Cutler (Polar Biology, 2000)

The effects of 3000-m swimming on subsequent 3-h cycling performance: implications for ultraendurance triathletes - Paul B. Laursen; Edward C. Rhodes; Robert H. Langill (European Journal of Applied Physiology, 2000)

Phylogeny of Marine Bacillus Isolates from the Gulf of Mexico - Janet L. Siefert; Maia Larios-Sanz; Lawrence K. Nakamura; Ralph A. Slepecky; John H. Paul; Edward R. B. Moore; George E. Fox; Peter Jurtshuk, Jr. (Current Microbiology, 2000)

Proportion of colon cancer risk that might be preventable in a cohort of middle-aged US men - Elizabeth A. Platz; Walter C. Willett; Graham A. Colditz; Eric B. Rimm; Donna Spiegelman; Edward Giovannucci (Cancer Causes & Control, 2000)

Angiostatin and Endostatin: Endogenous Inhibitors of Tumor Growth - B. Kim Lee Sim; Nicholas J. MacDonald; Edward R. Gubish (Cancer and Metastasis Reviews, 2000)

Has the Attraction of Predatory Coccinellids to Cornicle Droplets Constrained Aphid Alarm Signaling Behavior? - Edward B. Mondor; Bernard D. Roitberg (Journal of Insect Behavior, 2000)

Isolation and Identification of Ruminal Methanogens from Grazing Cattle - Graeme N. Jarvis; Carsten Strömpl; Diana M. Burgess; Lucy C. Skillman; Edward R. B. Moore; Keith N. Joblin (Current Microbiology, 2000)

Pollen‐based biomes for Beringia 18,000, 6000 and 0 14 C yr bp † - M. E. Edwards; P. M. Anderson; L. B. Brubaker; T. A. Ager; A. A. Andreev; N. H. Bigelow; L. C. Cwynar; W. R. Eisner; S. P. Harrison; F.‐S. Hu; D. Jolly; A. V. Lozhkin; et al. (Journal of Biogeography, 2000)
The objective biomization method developed by Prentice et al . (1996) for Europe was extended using modern pollen samples from Beringia and then applied to fossil pollen data to reconstruct palaeovegetation patterns at 6000 and 18,000 14 C yr bp . The predicted modern distribution of tundra, taiga and cool conifer forests in Alaska and north‐western Canada generally corresponds well to actual vegetation patterns, although sites in regions characterized today by a mosaic of forest and tundra vegetation tend to be preferentially assigned to tundra. Siberian larch forests are delimited less well, probably due to the extreme under‐representation of Larix in pollen spectra. The biome distribution across Beringia at 6000 14 C yr bp was broadly similar to today, with little change in the northern forest limit, except for a possible northward advance in the Mackenzie delta region. The western forest limit in Alaska was probably east of its modern position. At 18,000 14 C yr bp the whole of Beringia was covered by tundra. However, the importance of the various plant functional types varied from site to site, supporting the idea that the vegetation cover was a mosaic of different tundra types.

An evaluation of terminal‐restriction fragment length polymorphism (T‐RFLP) analysis for the study of microbial community structure and dynamics - A. Mark Osborn; Edward R. B. Moore; Kenneth N. Timmis (Environmental Microbiology, 2000)
A systematic evaluation of the value and potential of terminal‐restriction fragment length polymorphism (T‐RFLP) analysis for the study of microbial community structure has been undertaken. The reproducibility and robustness of the method has been assessed using environmental DNA samples isolated directly from PCB‐polluted or pristine soil, and subsequent polymerase chain reaction (PCR) amplification of total community 16S rDNA. An initial investigation to assess the variability both within and between different polyacrylamide gel electrophoresis (PAGE) runs showed that almost identical community profiles were consistently produced from the same sample. Similarly, very little variability was observed as a result of variation between replicate restriction digestions, PCR amplifications or between replicate DNA isolations. Decreasing concentrations of template DNA produced a decline in both the complexity and the intensity of fragments present in the community profile, with no additional fragments detected in the higher dilutions that were not already present when more original template DNA was used. Reducing the number of cycles of PCR produced similar results. The greatest variation between profiles generated from the same DNA sample was produced using different Taq DNA polymerases, while lower levels of variability were found between PCR products that had been produced using different annealing temperatures. Incomplete digestion by the restriction enzyme may, as a result of the generation of partially digested fragments, lead to an overestimation of the overall diversity within a community. The results obtained indicate that, once standardized, T‐RFLP analysis is a highly reproducible and robust technique that yields high‐quality fingerprints consisting of fragments of precise sizes, which, in principle, could be phylogenetically assigned, once an appropriate database is constructed.

Occurrence of C3 and C4 photosynthesis in cotyledons and leaves of Salsola species (Chenopodiaceae) - Vladimir I. Pyankov; Elena V. Voznesenskaya; Alexander N. Kuz'min; Maurice S. B. Ku; Eric Ganko; Vincent R. Franceschi; Clanton C. Black; Gerald E. Edwards (Photosynthesis Research, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

A General Method for Constrained Analysis of Fluorescence Anisotropy Decay: Application of the Steady-State Anisotropy - Edward L. Rachofsky; Barnabas Wolf; Carl N. Bialik; J. B. Alexander Ross; William R. Laws (Journal of Fluorescence, 1999)

Photosynthetic acclimation of maize to growth under elevated levels of carbon dioxide - João P. Maroco; Gerald E. Edwards; Maurice S. B. Ku (Planta, 1999)

Identification of the metabolically active members of a bacterial community in a polychlorinated biphenyl‐polluted moorland soil - Balbina Nogales; Edward R. B. Moore; Wolf‐Rainer Abraham; Kenneth N. Timmis (Environmental Microbiology, 1999)
The presumptive metabolically active members of a bacterial community in a moorland soil in Germany, highly polluted with polychlorinated biphenyls (PCBs), were identified by sequencing of cloned reverse transcription–polymerase chain reaction (RT–PCR) amplification products of 16S rRNA generated from total RNA extracts. Analysis of the 16S rRNA clone library revealed a considerable diversity of metabolically active bacteria in the soil, despite the acidic pH and high concentrations of PCBs. Cloned sequence types clustered within the Proteobacteria (34% alpha‐, 33% beta‐ and 7% gamma‐subclasses), the Holophaga – Acidobacterium phylum (14%), the Actinobacteria (6.5%) and the Planctomycetales (2%). Three cloned sequence types were not affiliated to any described phylogenetic group. An unusual feature of this soil was the abundance of sequence types within the beta‐subclass of the Proteobacteria , most of which were similar to the 16S rRNA gene sequences of species from only two genera, Burkholderia and Variovorax . Three other numerous 16S rRNA sequence types were similar to the sequences of Sphingomonas species, members of the Rhodopila globiformis group and Acidobacterium capsulatum . Some of the sequence types retrieved were similar to the 16S rRNA sequences of bacterial isolates able to degrade a variety of organic pollutants, including PCBs. As the PCB contamination is the major source of measurable carbon in this soil, some of the 16S rRNA sequence types detected and presumed to represent the metabolically active members of the community indicate the organisms likely to be involved, directly or indirectly, in the utilization of the PCBs as carbon and energy sources.

Choosing a Forest Vision - Donald W. Floyd; Kelsey Alexander; Charles Burley; Arthur W. Cooper; Arthur DuFault; Ross W. Gorte; Sharon G. Haines; Bruce B. Hronek; Chadwick D. Oliver; Edward W. Shepard (Journal of Forestry, 1999)
It is unlikely, given the often-contentious history of the national forests, that incremental change in their administration can resolve fundamental differences in values. So concludes a task force appointed by the Society of American Foresters (SAF) to review federal forest management; its analysis and recommendations have been published in Forest of Discord: Options for Governing Our National Forests and Federal Public Lands. Whereas the Committee of Scientists was asked to stay within the framework of current laws and regulations, the SAF analysts were not so constrained. The following excerpts from Forest of Discord summarize the reasons that fundamental legislative and regulatory change is warranted and consider the purpose of having national forests and public lands.

Assessing Trace Element Uptake by Vegetation on a Coal Fly Ash Landfill - Peter B. Woodbury; Gail Rubin; D. C. McCune; Leonard H. Weinstein; Edward F. Neuhauser (Water, Air, & Soil Pollution, 1999)

Towards elucidation of microbial community metabolic pathways: unravelling the network of carbon sharing in a pollutant‐degrading bacterial consortium by immunocapture and isotopic ratio mass spectrometry - Oliver Pelz; Michael Tesar; Rolf‐Michael Wittich; Edward R. B. Moore; Kenneth N. Timmis; Wolf‐Rainer Abraham (Environmental Microbiology, 1999)
Although much information on metabolic pathways within individual organisms is available, little is known about the pathways operating in natural communities in which extensive sharing of nutritional resources is the rule. In order to analyse such a consortium pathway, we have investigated the flow of 4‐chlorosalicylate as carbon substrate within a simple chemostat microbial community using 13 C‐labelled metabolites and isotopic ratio mass spectrometric analysis of label enrichment in immunocaptured member populations of the community. A complex pathway network of carbon sharing was thereby revealed, involving two different metabolic routes, one of which is completely novel and involves the toxic metabolite protoanemonin. The high stability of the community results, at least in part, from interdependencies based on carbon sharing and the rapid removal of toxic metabolites.

A Revised Assessment of Species Redundancy and Ecosystem Reliability - Edward B. Rastetter; Laura Gough; Anne E. Hartley; Darrell A. Herbert; Knute J. Nadelhoffer; Mathew Williams (Conservation Biology, 1999)

Chloroplast DNA restriction site data support a narrowed interpretation ofEupatorium (Asteraceae) - Edward E. Schilling; Jose L. Panero; Patricia B. Cox (Plant Systematics and Evolution, 1999)

CO2 and O2 dependence of PS II activity in C4 plants having genetically produced deficiencies in the C3 or C4 cycle - João P. Maroco; Maurice S. B. Ku; Robert T. Furbank; Peter J. Lea; Richard C. Leegood; Gerald E. Edwards (Photosynthesis Research, 1998)

Effect of environmental temperature on the interactive developmental toxicity of radiofrequency radiation and 2-methoxyethanol in rats - B. K. Nelson; D. L. Conover; E. F. Krieg Jr; D. L. Snyder; R. M. Edwards (International Archives of Occupational and Environmental Health, 1998)

Gut length, food transit time and diving habit in phocid seals - Per-Erik Mårtensson; Erling S. Nordøy; Edward B. Messelt; Arnoldus Schytte Blix (Polar Biology, 1998)

Effects of experimental fire regimes on the population dynamics of shape Schwalbea americana L. - L. Katherine Kirkman; Mark B. Drew; Don Edwards (Plant Ecology, 1998)

Host Searching and Oviposition by Leschenaultia exul, a Tachinid Parasitoid of the Forest Tent Caterpillar, Malacosoma disstria - Edward B. Mondor; Jens Roland (Journal of Insect Behavior, 1998)

The variability in total and extractable soil phosphorus under a grazed pasture - E. Fisher; B. Thornton; G. Hudson; A.C. Edwards (Plant and Soil, 1998)

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)

Functional Expression of p64, an Intracellular Chloride Channel Protein - J.C. Edwards; B. Tulk; P.H. Schlesinger (The Journal of Membrane Biology, 1998)

Crystal structure of Escherichia coli manganese superoxide dismutase at 2.1-Å resolution - Ross A. Edwards; Heather M. Baker; M. M. Whittaker; James W. Whittaker; Geoffrey B. Jameson; E. N. Baker (JBIC Journal of Biological Inorganic Chemistry, 1998)

Diabetes mellitus and risk of prostate cancer (United States) - Edward Giovannucci; Eric B. Rimm; Meir J. Stampfer; Graham A. Colditz; Walter C. Willett (Cancer Causes & Control, 1998)

Potato fungicides interfere with entomopathogenic fungi impacting population dynamics of green peach aphid - Abdelaziz Lagnaoui; Edward B. Radcliffe (American Journal of Potato Research, 1998)

Microbial Reduction of Iodate - Terry B. Councell; Edward R. Landa; Derek R. Lovley (Water, Air, & Soil Pollution, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Hydrologic control on the oxygen-isotope relation between sediment cellulose and lake water, western Taimyr Peninsula, Russia: Implications for the use of surface-sediment calibrations in paleolimnology - Brent B. Wolfe; Thomas W. D. Edwards (Journal of Paleolimnology, 1997)

Immunoreactivity for the Fas ligand in the mammalian enteric nervous system - Edward J. Parr; Erica B. Myles; Menachem Hanani; Dan Seror; Karl T. Riabowol; Keith A. Sharkey (Cell and Tissue Research, 1997)

Influence of organic by-products and nitrogen source on chemical and microbiological status of an agricultural soil - J. A. Entry; B. H. Wood; J. H. Edwards; C. W. Wood (Biology and Fertility of Soils, 1997)

Relation between delayed impairment of cerebral energy metabolism and infarction following transient focal hypoxia-ischaemia in the developing brain - R. M. Blumberg; E. B. Cady; J. S. Wigglesworth; J. E. McKenzie; A. D. Edwards (Experimental Brain Research, 1997)

Geographic distribution of insect resistance in potatoes - Kathy L. Flanders; Edward B. Radcliffe; John G. Hawkes (Euphytica, 1997)

A computer-controlled aortic and mitral valve occluder - Steven B. Solomon; Srdjan D. Nikolic; Robert W. M. Frater; Edward L. Yellin (Annals of Biomedical Engineering, 1997)

Book Review: Formation and deformation of glacial deposits. Eds. W.P. Warren and D.C. Croot. A.A. Balkema, Rotterdam, 1994. 223pp. L40.00 ISBN 90‐5410‐096‐6 - Edward B. Evenson (Journal of Quaternary Science, 1996)

Potato leafroll virus spread in differentially resistant potato cultivars under varying aphid densities - Christina D. DiFonzo; David W. Ragsdale; Edward B. Radcliffe (American Journal of Potato Research, 1995)

High level production of potyvirus-like particles in insect cells infected with recombinant baculovirus - S. J. Edwards; M. B. Hayden; R. C. Hamilton; J. A. Haynes; I. T. Nisbet; M. N. Jagadish (Archives of Virology, 1994)

Expression and characterisation of equine herpesvirus 1 glycoprotein H using a recombinant baculovirus - E. M. McGowan; M. B. Hayden; S. J. Edwards; D. Pye; D. N. Love; J. M. Whalley (Archives of Virology, 1994)

Valuing environmental functions in developing countries - Bruce Aylward; Edward B. Barbier (Biodiversity and Conservation, 1992)

Indoor air mercury concentrations following application of interior latex paint - Kathy M. Beusterien; Ruth A. Etzel; Mary M. Agocs; Grace M. Egeland; Edward M. Socie; Mary A. Rouse; B. Kim Mortensen (Archives of Environmental Contamination and Toxicology, 1991)

On the statistics of binned neural point processes: the Bernoulli approximation and AR representation of the PST histogram - B. W. Edwards; G. H. Wakefield (Biological Cybernetics, 1990)

Use of enzyme-linked immunosorbent assay to detect potato leafroll virus in field grown potato, cv. Russet Burbank - Kathy L. Flanders; David W. Ragsdale; Edward B. Radcliffe (American Journal of Potato Research, 1990)

Use of enzyme-linked immunosorbent assay to detect potato leafroll virus in field grown potato, cv. Russet Burbank - Kathy L. Flanders; David W. Ragsdale; Edward B. Radcliffe (American Journal of Potato Research, 1990)

Protonmotive force in Brevibacterium flavum: the lack of intracellular pH homeostasis - Uldis Z. Kalnenieks; Juris B. Saulitis; Nina I. Galinina; Edward E. Liepinś; Juris E. Shivinka (Archives of Microbiology, 1989)

Primary irritant contact dermatitis from synthetic pyrethroid insecticide exposure - Stephen A. Flannigan; Stephen B. Tucker; Marcus M. Key; Charles E. Ross; Edward J. Fairchild; Barbara A. Grimes; Ronald B. Harrist (Archives of Toxicology, 1985)

The chronic toxicity of 3-chloro-4-methyl benzamine HCl to birds - Edward W. Schafer; Ronald B. Brunton; Donald J. Cunningham; Norman F. Lockyer (Archives of Environmental Contamination and Toxicology, 1977)

Simple vs. complex inheritance of inducible aryl hydrocarbon hydroxylase in mouse tissues - Kurt Brki; A. G. Liebelt; Edward Bresnick (Biochemical Genetics, 1975)

Identification of maize seedling mutants lacking starch accumulation capacity - Edward L. Cox; David B. Dickinson (Biochemical Genetics, 1971)

Annual heat budgets and thermal stability in small Mountain Lakes, Colorado, USA - Edward B. Reed (Aquatic Sciences, 1970)

Evolutionary evidence for a regulator gene controlling the lactate dehydrogenase B gene in rodent erythrocytes - Thomas B. Shows; Edward J. Massaro; Frank H. Ruddle (Biochemical Genetics, 1969)

Bibliography the after-cooking discoloration of potatoes - Eugene A. Talley; Mary V. Zaehringer; Roger M. Reeve; R. B. Hyde; Donald H. Dinkel; Edward G. Heisler; Russell Pressey (American Journal of Potato Research, 1969)

Effect of soil temperatures at harvest on the bruise resistance of potatoes - Edward F. Johnston; J. B. Wilson (American Journal of Potato Research, 1969)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)